Micro-aeration unlocks endogenous nitrogen removal in anaerobic digesters via metabolically versatile fermentative bacteria - Linpei Han; Lei Li; Wenjie Ye; Jiaqi Huang; Yongli Liu; Chaoran Duan; Bin Zhan; Shangbang Guo; Xuya Peng (Water Research, 2027)

Buckling behavior of CIPP liners spanning separated joints in reinforced concrete pipes - Hao Hu; Bin Li; Jiajun Chu; Xiaoxiang Guo; Baoyong Liao; Zhongsen Ti (Tunnelling and Underground Space Technology, 2027)

Tracing carbon in the wind: A forward trajectory framework and regional environmental governance - Weibing Sun; Jia Liu; Bin Fu; Chunyan Yang; Mingxuan Liang; Yingman Guo; Yuan Li; Duanfang Lu; Xiao Ma (Environmental Impact Assessment Review, 2027)

High-resolution carbon isotope chemostratigraphy of the upper Cambrian from the East Tarim Basin and implications for global correlation and paleoenvironment reconstruction - Xiao-Jun Zuo; Bo Chen; Hong-Xing Wei; Zhi-Xin Sun; Xin-Sheng Luo; Guo-Xiang Li; Zhi-Bin Huang; Miao Lu; Yong-Quan Chen; Ai-Hua Yang; Fang-Chen Zhao; Mao-Yan Zhu (Palaeoworld, 2026)

Indole alkaloids from the roots of Nauclea officinalis and their chemotaxonomic significance - Shan-Ze Yin; Bao-Chan Liu; Guo-Lan Ma; Jiu-Wei Ma; Xi-Yang Lei; Bin-Bao Wang; Rui Li; Shao-Jie Lu; Wei-Min Gao; Pei-Gang Ouyang; Cai-Feng Ding (Biochemical Systematics and Ecology, 2026)

Regional contrasts in phytoplankton communities and organic carbon pools: Hydrographic forcing and zooplankton grazing in the Cosmonaut and Cooperation Seas - Cuiting Li; Dong Li; Jun Zhao; Ji Hu; Xinliang Wang; Guijun Guo; Jianming Pan; Bin Wu; Peisong Yu; Weiping Sun; Guanbei Wu; Haifeng Zhang; et al. (Marine Pollution Bulletin, 2026)

Single-cell transcriptomic profiling identifies TIMP1 as a diagnostic marker linked to macrophage ferroptosis in ulcerative colitis - Wen-Hao Xiong; Shuo Huang; Yan-Hong Liu; Guo-Shan Chen; Dan-Zhou Li; Yong-Cheng Di; Wen-Bin Song; Yong-Chao Zhang; Yi-Fan Wang; Feng Qi (Tissue and Cell, 2026)

Association of combined exposure to polycyclic aromatic hydrocarbons, BTX and metals with metabolic syndrome risk - Xiaoyu Hao; Xiangkai Zhao; Zhiguang Gu; Bin Yang; Di Zhang; Rui Zhao; Xu Guo; Zhe Cheng; Gang Wang; Xiaohui Li; Junfeng Zhao; Zhiheng Li; et al. (Environmental Pollution, 2026)

A deep learning and generative modeling pipeline for mining and engineering alkaline-stsable xylanases - Ruohan Zhang; Yiyang Zhang; Zhonghao Deng; Pengtao Wang; Lingxi Fan; Feng Guo; Huiying Luo; Yuan Wang; Tao Tu; Bin Yao; Jian Tian; Huoqing Huang; et al. (Bioresource Technology, 2026)

Investigation of electrode-free, room temperature, flexible NH3 sensors with high stability and sensitivity using MXene@PANI-MWCNTs ink - Jiahui Zheng; Bochao Ma; Xiaoqing Cui; Rui Wang; Li An; Bin Guo; Hongyan Zhang (Analytica Chimica Acta, 2026)

Plastic fragments impair soil organic carbon persistence through reshaping microbial metabolism and decreasing plant carbon supply in dryland ecosystems - Meng-Ying Li; Wei Wang; Yudi M. Lozano; Jia-Yao Yang; Yue Ma; Xiao-Bin Xiong; Shuang-Jin Huang; Muhammad Ashraf; Jian-Ming Li; Yun-Li Xiao; Zheng-Guo Cheng; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

1,12-cyclic-apelin-12 counters vascular smooth muscle cell proliferation and atherosclerosis through inhibiting aerobic glycolysis - Ruirui Lu; Xiaosi Zhou; Huimei Liu; Sisi Fan; Xiaohui Huang; Fengting Guo; Bin Huang; Linxi Chen; Lanfang Li (Toxicology and Applied Pharmacology, 2026)

A salt-tolerant dual-network hydrogel based on tea waste biochar for efficient seawater desalination - Kun-Xiu Liu; Yi-Bin Li; Lei Xu; Cai-Hua Liu; Zhu-Long Yu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2026)

Biodegradable polylactic acid microplastics affect nutrient cycling during the entire crop growth cycle: Implications for soil ecosystem multifunctionality - Qian Cui; Feilong Wang; Xiaoling Shan; Ling Ding; Xinran Qiu; Bin Zhang; Xian Li; Xujun Liang; Xuetao Guo (Environmental Pollution, 2026)

Crustal differentiation driven by long-lived UHT metamorphism in Central Gondwana: A review and synthesis of new data - Sanjeewa P.K. Malaviarachchi; Lei Zhao; Prasanna Lakshitha Dharmapriya; Yan-Bin Zhang; Jinghui Guo; Xian-Hua Li (Earth-Science Reviews, 2026)

Kinetic modeling of sorption-enhanced methane steam reforming in a PdAg membrane reactor for sustainable H2 production - Jiaqi Ruan; Ke Guo; Bin Wang; Xiao Li; Mengzhu Sun; Yilin Li; Mingkai Liu; Yong Hao; Hongguang Jin (Chemical Engineering Journal, 2026)

The dual role of Ni: From promotion to suppression of hydrodesulfurization in NiMoW catalysts - Fengyu Tian; Guangzheng Sun; Xianfu Zeng; Jingjing Liu; Yuhao Liang; Yuan Pan; Bin Dong; Yichuan Li; Yanpeng Li; Hailing Guo; Bin Liu; Chenguang Liu; et al. (Chemical Engineering Journal, 2026)

A photothermal-enhanced nanozyme hydrogel with stimuli-responsive biofactor delivery for diabetic bone regeneration - Renxin Chen; Zouwei Li; Guang Shi; Haoran Lu; Mengyue Zhu; Zhuowen Hao; Zijian Wu; Luhao Li; Jiayao Chen; Zheyuan Zhang; Lanhong Guo; Tian Luan; et al. (Chemical Engineering Journal, 2026)

Reduction stagnation in cold-bonded magnetite pellets during hydrogen reduction: Mechanistic insights into microstructure-kinetics coupling - Xuyang Lu; Desheng Li; Jian Shi; Bin Chen; Qiang Xu; Liejin Guo (Chemical Engineering Journal, 2026)

Effects of body fat percentage on thermal responses during exercise and recovery phases under different temperatures - Bin Yang; Yamin Kang; Xuechen Zhang; Yuemei Wang; Zhe Li; Miao Guo; Junjiang Wang (Building and Environment, 2026)

Soil deposition reduces bacterial network complexity and stability by shifts in life-history strategies on the Loess Plateau of China - Yanqing Guo; Hailun Zhang; Shunxiang Yao; Bin Zhu; Rui Ma; Xiuling Li; Qianjin Liu; Qiqi Sun; Shengli Guo; Yaxian Hu; Lanlan Du (Applied Soil Ecology, 2026)

Regulatory mechanisms underlying dynamic variation of DHA, EPA, and odd-chain fatty acids content in Auran tiochytrium sp. SZ13 - Rui Luo; Buwen Sun; Jiaxing Li; Nannan Zhang; Meihan Chen; Ziyu Du; Shuo Li; Jialin Guo; Bin Liu; Dongzhe Sun (Algal Research, 2026)

Associations of pedogenic carbonate accumulation with soil organic-inorganic carbon coupling in arid croplands - Tongping Lu; Yuling Li; Xuhui Wang; Hui Guo; Bin He; Muhammad Shoaib Rana; Jie Ma; Changyan Tian; Jianfei Shi; Yugang Wang; Xiujun Wang (Agriculture, Ecosystems & Environment, 2026)

In vitro regeneration via indirect organogenesis from aseptic seedling-derived explants of the rare Tibetan medicinal shrub Sibiraea angustata - Mengting Pi; Xue Yu; Hongchang Li; Yali Guo; Wuyang Lai; Leipeng Cao; Tao Jiang; Lingxia Xu; Fuhua Peng; Hongdong Liu; Fei Wang; Jianguo Hu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Unsupervised keypoint detection for automated livestock phenotyping: A multi-species approach based on pre-trained foundation models - Bingxue Wei; Mengxiao Tian; Bin Li; Yiwei Wang; Andrea Pezzuolo; Huawei Su; Hao Guo (Computers and Electronics in Agriculture, 2026)

Apatite fingerprints the magmatic-hydrothermal processes of the Wajilitag alkaline‑carbonatite complex, NW China - Li-Peng Qin; Wu-Bin Yang; Guo-Feng Xu; Pan Qu; He-Cai Niu (Lithos, 2026)

Identifying optimal green plot ratio thresholds for mitigating PM2.5 in street canyons: Integrating LiDAR, CFD, and explainable machine learning - Bin Guo; Hailong Chen; Zheng Wang; Miaoyi Chen; Lu Li; Puhao Chen; Lin Pei; Tengyue Guo; Xuying Ma; Rongming Hu; Xiaowei Zhu (Journal of Hazardous Materials, 2026)

Deciphering the carrier potential of microplastics aged in freeze-thaw soils: Multiscale insights into mechanisms for antibiotic adsorption amplification - Wen-hao Yang; Jian-yong Wu; Kong-yan Luo; Ling-li Ma; Bin Yan; Jin-song Guo; Jie Zeng; Yi-zhi Pei; Jun-min Gao (Journal of Hazardous Materials, 2026)

Synergistic stabilization of DHA algal oil via amyloid fibril-anchored Haematococcus pluvialis protein/PVA core-shell nanofibers - Yangyang Guo; Xingru Yan; Yujuan Zhu; Bin Li; Yinxu Zhang; Wentao Su (Food Chemistry, 2026)

Thermally activated persulfate-driven rapid abiotic carbon source production of food waste: Performance, organic matter evolution and denitrification potential - Xu Xing; Xiupeng Jiang; Xiaoya Li; Yanyan Guo; Xiaochan Su; Youcai Zhao; Bin Xu; Tao Zhou (Environmental Research, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Deep reinforcement learning-enabled HVAC control for thermal comfort, indoor CO2 concentration and energy performance in multizone office building during heatwave - Bilal Ahmed; Ateeque Ahmed; Anjukan Kathirgamanathan; Jun-Liang Guo; Xiao-Bin Li; Kai-Yang Qu; Feng-Chen Li (Building and Environment, 2026)

Maternal and Neonatal Factors Impacting the Volume and Cellular Composition of Umbilical Cord Blood - Yu Li; Jia Liu; Ming Li; Chunyu He; Bin Guo; Ye Yang; Rongzhen Jiang (Stem Cell Reviews and Reports, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Metabolic rewiring and transcriptional interference underlie the biocontrol efficacy of Burkholderia arboris BB417 against Ralstonia solanacearum species complex - Shanwen Ding; Juan Zhang; Yang Wang; Guobing Lan; Lin Yu; Yafei Tang; Zhenggang Li; Bin Guo; Zifu He; Xiaoman She (Pesticide Biochemistry and Physiology, 2026)

Unraveling the role of plastic polymers in PAHs emissions from municipal solid waste incineration: Quantifying contributions, synergy, and source tracers - Shuangxi Zhou; Xinyu Huang; Zhanbo Hong; Yufan Wang; Bin Zhang; Tianyang Su; Jiajia Pu; Tian Zhang; Yanlin Li; Xinran Qiu; Ling Ding; Xian Li; et al. (Journal of Hazardous Materials, 2026)

A triplex-readout CRISPR-Cas12a multimodal biosensing platform for point-of-care detection of avian influenza H5N1 - Bin Guo; Yang Li; Mengxin Shi; Jingyu Zhang; Qingqing Wu; Xiaokang Wu; Ruifang An; Fu Wang (Journal of Hazardous Materials, 2026)

Beyond pathogens: Emerging contaminant risks following the potomac sewer spill in the United States - Xiaopei Li; Qing Feng; Zhenheng Long; Kunyu Guo; Bin Liu; Peng Gao; Shan Niu; Gang Yu (Journal of Environmental Sciences, 2026)

Micro-nano bubble-assisted fasting improves the meat quality of Pelodiscus sinensis by modulating gut microbiota and metabolic profiles - Weifa Su; Hongjie Fan; Yifan Zheng; Tao Wang; Yuezhen Li; Jingjing Fan; Saiqin Guo; Yuanzhi Cheng; Bin Zheng; Xingwei Xiang (Food Chemistry, 2026)

Two-step pyrolysis enabled by bentonite catalysis for the co-production of bioactive humic acid and functional carbon-clay composites - Huanhuan Li; Jiarun Duan; Lijuan Zhang; Yong Wen; Yun Xiang; Chen Qiu; Junmei An; Zhiguo Guo; Yidong Cai; Changchun Ge; Xiaona Ren; Xinjiang Zhou; et al. (Environmental Research, 2026)

Deciphering Er3+ energy level population in La2Sn2O7 nanocrystals via tailored short-range energy transfer for multidimensional applications - Jiamei Ren; Bin Duan; Kejie Li; Jiaqi Zhao; Dongxu Guo; Ruiying Lu; Tianqi Sheng; Zuoling Fu (Chemical Engineering Journal, 2026)

Short-run Re-coupling of CO2 emissions and socioeconomic development after COVID-19 in a BRI country: Evidence from Kyrgyzstan - Jingpeng Guo; Yinghui Zhao; Bin Geng; Zehao Li; Xinyang Zhang; Frank Yonghong Li (Atmospheric Pollution Research, 2026)

Identification of stripe rust resistance loci in Gansu wheat landraces using genome-wide association analysis - Zhe Zhang; Yu Zhang; Ying Guo; Xinyi Ye; Rongguang Wu; Xining Zhang; Haozhen Yang; Ping Jin; Shunda Li; Ravi P. Singh; Bin Bai; Fangping Yang; et al. (Theoretical and Applied Genetics, 2026)

Liposome-iRGD loaded with astragaloside IV alleviates the functional damage of endothelial progenitor cells via the Hippo-YAP/TAZ signaling pathway - Churuo Zeng; Qinxia Li; Dongwei Guo; Wu Xiong; Xiaoling Zou; Wei Li; Jie Bin; Xiuping Wang; Zihao Zhang; Bingqian Xue; Ruowei Hu; Xi Zhang (In Vitro Cellular & Developmental Biology - Animal, 2026)

Influence of Planting Density on Shoot Branching Regulated by Photosynthetic Activity and Hormonal Signaling in the Maize-Soybean Intercropping System - Irshan Ahmad; Jie Chen; Noman Shoaib; Sajad Hussain; Muhammad Arshad; Bin Cheng; Li Wang; Mei Xu; Yali Guo; Wenyan Wang; Yao Zhao; Weiguo Liu (Journal of Plant Growth Regulation, 2026)

Failure characteristics and development mechanism of time-delayed rockburst in a tunnel excavated via the drilling and blasting method: A case study - Lei Hu; Wen-Fei Chang; Ben-Guo He; Wei Zhang; Jun Zhao; Zhi-Bin Yao; Meng-Fei Jiang; Hong-Pu Li; Lian-Jie Fu (Tunnelling and Underground Space Technology, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Genetic dissection of seed quality traits in mungbean through QTL-seq of recombinant inbred line populations - Chunxiu Ren; Jiaqi Qiao; Lipan Qiao; Bin Li; Xiaopeng Hao; Xin Guo; Fan Yang; Dongao Huo (Journal of Plant Physiology, 2026)

Optimizing conservation strategies: Incorporating ecosystem services into the proposed Asian Elephant National Park in China - Junyu Peng; Peng Liu; Wenwen Li; Xiaoyu Guo; Bin Wang; Li Zhang (Journal of Environmental Management, 2026)

Field experiment study of well-group control and exploitation in Fuyu oil shale using topochemical heat in-situ conversion technology - Bin Zhu; Wei Guo; Youhong Sun; Sunhua Deng; Chaofan Zhu; Haipeng Liu; Qiang Li (Fuel, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Optimization of nitrogen and potassium fertilizer application to promote canopy development and enhance dry matter allocation and grain yield in japonica rice - Bin Wang; Yanzhao Lei; Yu Zhang; Jiangtao Li; Chen Guo; Jiping Xu; Yin Wang; Qiang Gao; Wenfeng Hou (Field Crops Research, 2026)

Biomimetic platform integrating therapeutic exosomes and stretch reverses lumbar disc herniation through multi-targeting accurate regulation - Yang Xu; Yu-Da Liu; Jia-Wen Zhan; Hao-Bin Wang; Xiao-Feng Li; Li-Guo Zhu; Li-Hua Peng (Chemical Engineering Journal, 2026)

A comprehensive review of blue, green, and grey space studies for improving urban microclimate - Xuelin Zhang; Qiusheng Li; Benshuo Wang; Xingyu Qian; Wenbing Liu; Yaojia Guo; Zhen Wu; Ziyong Cao; Chichuan Qin; Jiaru Zhai; Bin Lu (Building and Environment, 2026)

8-Me-PIQ Expands Cord Blood CD34+ Hematopoietic Stem and Progenitor Cells via Metabolic Suppression and Inhibition of Ribosome Biogenesis - Yu Li; Mengmeng Li; Bin Guo; Rongzhen Jiang (Stem Cell Reviews and Reports, 2026)

Correction: Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

Overlooked Effects of Nighttime Vapor Pressure Deficit on Extratropical Northern Hemisphere Vegetation Productivity - Tiewei Li; Hans W. Chen; Deliang Chen; Lanlan Guo; Lianyou Liu; Wenping Yuan; Huan Zheng; Ziqian Zhong; Bin He (Global Change Biology, 2026)
The impact of elevated atmospheric vapor pressure deficit (VPD) on vegetation productivity is well‐documented at monthly and annual scales. However, the influence of daytime VPD (VPD day ) and nighttime VPD (VPD night ) is often overlooked. Using multiple long‐term remote sensing proxies of vegetation productivity, we reveal distinct effects of VPD day and VPD night on growing season vegetation productivity over the extratropical Northern Hemisphere (> 25° N). VPD day was negatively associated with vegetation productivity in 73.2% of vegetated pixels, and robustness analyses across alternative datasets and methods yielded a range of 67.4%–75.6%. By contrast, positive effects of VPD night were detected in 51.8% of vegetated pixels, with corresponding estimates ranging from 36.5% to 55.7% across robustness analyses. This contrast was strongly related to aridity conditions. Vegetation productivity in drylands is more vulnerable to the double negative effects of high VPD day and VPD night , while in humid regions, it benefits from increased VPD night . Sap‐flow observations helped explain this contrast from the perspective of plant hydraulic transport. In humid regions, relatively ample soil moisture allowed nocturnal water transport to be maintained under elevated VPD night , helping restore plant water status overnight and providing favorable hydraulic conditions for daytime carbon uptake and vegetation productivity. In drylands, sap flow declined more strongly under high atmospheric demand and limited moisture during both daytime and nighttime, suggesting stronger hydraulic limitation and reduced overnight recovery, and thereby creating less favorable hydraulic conditions for vegetation productivity. These findings underscore the different roles of VPD day and VPD night in regulating vegetation productivity and highlight the importance of incorporating both into models to improve predictions of climate change impacts on terrestrial ecosystems.

Phage-Display Identification of Urate-Binding Cyclic Peptides with Preliminary Urate-Lowering Activity in Adenine-Induced Hyperuricemic Rats - Mi Ai; Zhi-Ming Wang; Wei-Lin Guo; Xue-Qi Li; Li-Ting Xiao; Yan-Shan Mai; Hong-Bin Zhang (International Journal of Peptide Research and Therapeutics, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Global material flow analysis of scandium from 2000 to 2024: Insights into supply, stocks, and circularity gaps - Qiang-Feng Li; Yi-Ding Wu; Lu Wang; Dan Lai; Qi-Ming Guo; Zong-Bin Shi; Shen Zhao; Qian-Qian Wang; Wei-Qiang Chen (Resources, Conservation and Recycling, 2026)

Rapid bactericidal and nematicidal activity of a ternary quaternary ammonium formulation via membrane disruption in bacteria and cuticle damage in Bursaphelenchus xylophilus - Mengyao Li; Yuewen Dou; Yongchao Zheng; Lingce Kong; Yan Cui; Likun Chen; Bin Wu; Kai Guo; Chonglin Zhao; Shaojie Han (Pesticide Biochemistry and Physiology, 2026)

Recyclable hygroscopic hydrogels with dynamic networks enable efficient solar-driven atmospheric water harvesting - Fu-Yao Zhong; Chen-Xi Li; Lu-Bin Zhong; Chao-Yang Guo; George Zheng Chen; Bo Weng; Jun He; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2026)

Impacts of climate, cryosphere and vegetation changes on blue and green water in the Qinghai-Tibetan Plateau - Wendong Kang; Genxu Wang; Kai Li; Xiangyang Sun; Bin Yong; Juying Sun; Linmao Guo; Peng Huang; Jiapei Ma; Zhao Deng; Haoyu Wang; Shouqin Sun (Journal of Environmental Management, 2026)

Resonant effects of seismicity on substance migration in rock fractures - Zhi-Jie Che; Jia-Qing Zhou; Li-Guo Guo; Fu-Shuo Gan; Hong-Bin Liu; Changdong Li; Yi-Feng Chen (International Journal of Rock Mechanics and Mining Sciences, 2026)

Lead exposure acts as a risk factor of PCOS development via SOD2-mediated mtDNA leakage - Qiaoling Zhang; Yinfei Xing; Shijie Li; Zhanqing Yang; Baiyu Li; Lilei Zhao; Liang Yue; Bin Guo (Chemico-Biological Interactions, 2026)

A Novel Indigenous Probiotic, Clostridium moniliforme G18, Confers Health Benefits to Mud Crabs (Scylla paramamosain) - Taoqiu Deng; Zhinuo Du; Huifen Liang; Dexin Jiao; Jinkun Li; Yuqing Zheng; Ming Zhang; Bin Zhang; Yongzhen Zhao; Zhixun Guo; Ngoc Tuan Tran; Shengkang Li (Probiotics and Antimicrobial Proteins, 2026)

The improvement of long-chain polyunsaturated fatty acids (LC-PUFAs) content and its relationship with intestinal microbiota modulation by Bdellovibrio and like organisms (BALOs) supplementation in American eels (Anguilla rostrata) - Yanbiao Guo; Jingyin Liu; Lingxiao Li; Huixiang Chen; Jintao Lǚ; Bin Jiang; Haifu Zhang; Guiying Kuang (Animal Feed Science and Technology, 2026)

Synergistic engineering of a MYB transcription factor boosts fucoxanthin and biomass co-production in the diatom Phaeodactylum tricornutum - Ting-Bin Hao; Mei-Qi Li; Rongxiang Guo; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Algal Research, 2026)

Probabilistic Retrieval of All-Day Overlapping Cloud Microphysical Properties - Jingwei Li; Baoxiang Pan; Feng Zhang; Bin Guo; Wenwen Li; Geng-Ming Jiang; Xin Wu; Quan Wang (Advances in Atmospheric Sciences, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

AI weather prediction toward multi-scale earth system prediction: status and pathways - Jinglin Zhang; Qinghui Chen; Feng Zhang; Zeyi Niu; Zekai Zhang; Fenghua Ling; Bin Guo; Hailong Liu; Cong Bai; Gang Li; Renhe Zhang (Science Bulletin, 2026)

Sustainable and ultra-stable biochar–hydroxyapatite composites for synergistic adsorption of Cu(II) and Ni(II) from simulated electroplating wastewater - Shiyun Guo; Bin Wang; Zhiju Chen; Yueli Wen; Maohong Fan; Xugang Li; Haodong Yang; Wei Huang; Abuliti Abudula (Process Safety and Environmental Protection, 2026)

The improving effect of airflow on thermal comfort in moderately hot environment: a comparative study based on populations with different exercise backgrounds - Bin Yang; Mengyang Zhou; Yuemei Wang; Miao Guo; Zhe Li; Junjiang Wang (Journal of Thermal Biology, 2026)

Rethinking the role of driving factors in developing carbon mitigation strategies: Evidence from the central heating sector in China - Guanying Huang; Hongzhe Yue; Bin Shui; Dezhi Li; Zhengyu Guo (Journal of Cleaner Production, 2026)

Speciated emissions of full-volatility organic compounds from plastic manufacturing: atmospheric impacts and toxicity generation - Dongyang Wu; Qing’e Sha; Luyun Liu; Citao Zhang; Shan Jiang; Qing Guo; Junhao Xu; Jialin Song; Renjun Li; Liufen Cai; Haoqi Chen; Guanghui Li; et al. (Journal of Environmental Sciences, 2026)

Characterization of volatile aroma profiles and identification of key stale odorants in albino green tea during accelerated shelf-life storage - Yi-Ming Yang; Bin-Hui Liao; Jin-Miao Zhao; Ying-Gou Zhao; Xiao-Gan Chen; Wen-Han Fan; Li-Qing Mei; Si-Qi Zhang; Hao-Wei Guo; Shu-Ying Gong; Jing-Fei Zhang; Fang-Yuan Fan (Food Control, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Intelligent ROS-triggered NO and isotretinoin co-delivery hydrogel dressings for microenvironment modulation and rapid repair of diabetic wounds - Bin Lu; Hanzhang Wang; Junyi Zhou; Jieying Lai; Xue Zheng; Shuang-Zhuang Guo; Li-Ming Zhang (Chemical Engineering Journal, 2026)

In-site fabrication of pheromone-loaded core-sheath fibers via handheld emulsion electrospinning with natural surfactants for Apolygus lucorum attraction - Hai-yan Ye; Wen-jie Shangguan; Han Wu; Jing Zhao; Liu-bin Xiao; De-jin Xu; Guang-chun Xu; Qi-liang Huang; Guo-hui Zhang; Li-dong Cao; Yong-an Tan (Chemical Engineering Journal, 2026)

Combined thermal-electrochemical analysis uncovers the dominant cracking mechanisms in Ni-rich layered cathodes - Yang Li; Liubin Ben; Mengyu Tian; Bin Liu; Yongxue Duan; Qianlong Sun; Bo Wang; Zhongzhu Liu; Aimin Guo; Luanna Parreira; Robson Monteiro; Rogerio M. Ribas; et al. (Chemical Engineering Journal, 2026)

Hollow mesoporous silica nanoparticles loaded with deer antler–derived bioactive factors enhance osseointegration of porous titanium scaffolds under bone defect conditions - Shipu Jia; Wenbo Yang; Jiaxin Zhang; Guokun Zhang; Jing Shang; Haowen Xue; Xiang Yue; Lanfeng Song; Shiwei Lu; Wenzhong Liu; Zijun Shen; Jiatai Li; et al. (Chemical Engineering Journal, 2026)

Multifunctional starch-based eutectogels with high mechanical properties, adhesion, self-healing, fatigue resistance and degradability for flexible wearable sensing - Dadong Sun; Zhihua Xu; Li Guo; Bin Yu; Lu Lu; Bo Cui; Xuemin Kang; Zhijun Zhang; Fanfu Meng; Chenghai Li; Guowei Cai (Carbohydrate Polymers, 2026)

Exposure to magnesium oxide nanoparticles induces mitochondrial dysfunction and apoptosis in fish Megalobrama amblycephala by disrupting magnesium homeostasis - Ling Zhang; Zi-Shang Liu; Si-Si Xiong; Yan-Zou Dong; Yue-Yun Guo; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu; Xiang-Fei Li (Aquatic Toxicology, 2026)

Identification of the BvCDPK gene family in sugar beet (Beta vulgaris L.) at a genome-wide level and analysis of the function of BvCDPK8 under salt conditions - Yan Nan; Min Li; Bin Cheng; Ming Wei; Guo-Qiang Wu (Physiology and Molecular Biology of Plants, 2026)

Endoplasmic Reticulum Stress in the Keratinocytes Contributes to Chronic Itch by Activation of Lipocalin 2/MC4R/TRPV1 Pathway - Wei Ge; Yu Feng; Li Zhang; Qian-Liang Wang; Cheng-Wei Zhang; Zhi-Hong Wang; Guo-Kun Zhou; Shi-Yu Sun; Xiu-Hua Miao; Tong Liu; Bin Wu; Jun Yan (Neuroscience Bulletin, 2026)

A state-of-the-art review of accurate and rapid prediction methods for thermal striping phenomenon in nuclear reactors - Mohsin Raza; Ikram UI Haq; Waqar ul Hassan; Jun-Liang Guo; Hong-Na Zhang; Xiao-Bin Li; Yue Wang; Wei-Hua Cai; Shu-Qi Meng; Fang Chen; Yu-Long Mao; Feng-Chen Li (Annals of Nuclear Energy, 2026)

A novel TaqMan-based RT-qPCR assay for the detection of PEDV and discrimination of the G2c subtype - Yicong Fan; Xiang Li; Jiawen Mo; Liang Weng; Shiyu Liu; Xu Song; Rongli Guo; Wei Wang; Mi Hu; Shanshan Yang; Yongxiang Zhao; Baochao Fan; et al. (Archives of Virology, 2026)

The catalytic subunit of cAMP-dependent protein kinase in Taenia solium cysticerci (TsPKA-c): A promising molecular target for the development of novel anti-cysticercosis therapeutics - Li-Qun Wang; Guang-Xue Liu; Pan-Hong Liang; Li Li; Tao-Shan Li; Ai-Ming Guo; Tharheer Oluwashola Amuda; Ke-Ke Wu; Yi-Xuan Wu; Hong Yin; Hong-Bin Yan; Xue-Nong Luo (Veterinary Parasitology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Design optimization and hydrodynamic performance analysis of bidirectional horizontal-axis tidal turbine - Shuqi Wang; Shuxian Li; Baifu Bian; Zijun Zhang; Bin Guo; Hui Tang (Ocean Engineering, 2026)

W-modified unsupported MoNiP catalysts synergistically enhancing palm oil hydrodeoxygenation-isomerization to low-freezing-point biofuels - Changlong Yin; Xinyue Li; Zhenjing Li; Yihang Han; Yongqiang Guo; Zhe Ma; Xiang Li; Dong Liu; Huiji Zhao; Bin Liu; Yongming Chai; Chenguang Liu (Fuel, 2026)

Synergistic regulation of chalkiness reduction in ratoon season rice by ABA and ascorbic acid: A physiological perspective - Hailong Xu; Bianhong Zhang; Xin Wu; Yijiang Hu; Americ Allison; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Anqi Li; Qingyang Zhang; et al. (Field Crops Research, 2026)

Future temperature-related labour loss due to premature deaths: a multi-country study - Bo Wen; Zanfina Ademi; Yao Wu; Rongbin Xu; Pei Yu; Yanming Liu; Wenhua Yu; Tingting Ye; Wenzhong Huang; Zhengyu Yang; Yiwen Zhang; Yuxi Zhang; et al. (Environmental Research, 2026)

High electron storage MXene-based adsorption membrane electrode for rapid remediation of uranium-containing wastewater - Mengfei Gao; Xin Lu; Wenxiang Li; Xin Gao; Shibing Shi; Bin Xing; Hua Zhao; Jian Li; Xuan Guo; Yanbiao Liu; Yi Wang (Chemical Engineering Journal, 2026)

A novel all-weather photo–electric synergistic process for inactivating alga in fresh waters: Performance and mechanism - Tiantian Chen; Bin Qi; Xueze Guo; Ruixue Jiang; Erqin Yin; Shouping Zhou; Wenming Zhang; Xiaochen Li (Water, Air, & Soil Pollution, 2026)

Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

Opening a new chapter in in-situ research on microscopic mechanisms of shale organic matter pore evolution - Wenren Zeng; Weikun Chen; Zi Wang; Ronghui Fang; Yi Guo; Yuan Zhang; Cong Zhang; Bin Zhang; Haohan Li; Borjigin Tenger (Science China Earth Sciences, 2026)

Exploring the mechanism of Cucurbitacin B against myocardial ischemia reperfusion injury based on network pharmacology and experimental validation - Xingdong Cheng; Dengyan Zhu; Haizhou Guo; Tianliang Zheng; Bin Wu; Yinliang Sheng; Feng Li; Guangcheng Sun; Song Zhao; Li Ke; Zhuoyu Gu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Maternal 3-NPA-induced oxidative stress impairs offspring ovarian function via glutamine metabolic dysregulation and NF-κB-mediated inflammation - Lu Guo; Wenkai Yu; Bin Li; Xiaocheng Liu; Jiarong Zhang; Wenbin Tang (Reproductive Toxicology, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

A numerical simulation investigation into the hydrodynamic behavior of propellers considering the effects of longitudinal vibration of the shafting system - Yakun Lu; Changlin Meng; Donghua Wang; Zhixiang Li; Yibin Guo; Bin Chen; Mingming Wang; Jiapeng Yu; Hanzhang Xu; Wanyou Li (Ocean Engineering, 2026)

Dual-mode regulation of cyclohexylamine biodegradation by dissolved oxygen: Metabolic trade-offs and community stability mechanisms - Cheng Qiu; Jingfeng Ding; Minwen Guo; Can Chen; Wenwu Zhang; Bin Yang; Yang Hou; Zhongjian Li (Journal of Water Process Engineering, 2026)

Molecular and functional characterization of cold-adaptive phage LPCS39 for effective control of Cronobacter sakazakii in refrigerated foods - Libère Ndayishimiye; Hanbing Wu; Ranfeng Ye; Yating Guo; Geng Zou; Yue Zhang; Yang Zhou; Miao Lei; Haoyu Guo; Zhiyong Song; Renwei Wu; Haixiang Guo; et al. (Food Research International, 2026)

An improved real-time quantitative PCR assay for the differentiation of major Listeria monocytogenes serovars - Jing Wang; Fei Dong; Yuchen Wang; Hui Li; Bin Hu; Jingliang Qin; Yijia Wang; Hongxia Wu; Xi Guo (Food Microbiology, 2026)

Biomineralization induced by Shigella dysenteriae JS3: The mechanism, and the differences between biotic and abiotic whewellite and struvite - Na Guo; Jizheng Qiao; Shuhua Zhang; Shengzhe Gao; Yanhong Zhao; Chao Han; Hui Zhao; Yanyang Zhao; Xiao Gao; Ruirui Meng; Bin Cao; Yu Li; et al. (Chemical Geology, 2026)

ESIRA, a novel framework integrating efficacy and safety for evaluating first-line treatments in advanced hepatocellular carcinoma - Hai-Long Li; Hui Zhou; Yi-Yang Zhang; Jin-Ting Lai; Zhen-Zhong Zhou; Jing-Yi Huang; Song-Bin Guo; Yu Wang; Wei-Juan Huang; Xiao-Peng Tian (Science China Life Sciences, 2026)

Impact of extracellular polymeric substances from Skeletonema costatum on the combined toxicity of microplastics and antibiotics in estuarine environment - Jie Lai; Jianhuang Su; Zongling Li; Yan Zheng; Dinglin Hou; Zifeng Zhou; Jiabao Zhu; Bin Lin; Peiyong Guo (Marine Pollution Bulletin, 2026)

Physics-constrained neural network for stress prediction in concrete pipes - Bin Li; Jingrun Zhang; Yuanlin Li; Xiaoxiang Guo; Hongyuan Fang; Niannian Wang; Xueming Du; Kejie Zhai (Tunnelling and Underground Space Technology, 2026)

Crustal structure and tectonic implications of the Southern Central Asian Orogenic Belt: New insights from gravity, magnetic, and magnetotelluric imaging - Chutong Chen; Na Li; Lingxiao Zhang; Hongying An; Chang’an Guo; Xing Fu; Songda Lei; Guicai Yang; Junjie Fan; Weiheng Yuan; Hao Wang; Bin Wang; et al. (Tectonophysics, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Silica reversal reveals the lithium super-enrichment during the extreme differentiation of granitic magmas - Chun-Li Guo; Roberto F. Weinberg; Fu-Yuan Wu; Jun-Xing Zhao; Xiao-Chi Liu; Bin-Wu Zhang (Lithos, 2026)

Volatile methyl siloxanes in electric vehicle cabin air: The first investigation of occurrence, influencing factors, and inhalation risks - Yujiao An; Yue Li; Xiaoliang Li; Zhendong Zhang; Jian Tang; Yu Ma; Kunyu Guo; Jianjie Chen; Shan Niu; Bin Liu; Chunzhao Chen; Gang Yu (Journal of Hazardous Materials, 2026)

Artificial sweeteners and antibiotics enhance the dissemination and diversity of antibiotic resistance genes in a soil-water continuum - Chen-Xi Fu; Qian Xiang; Ran Li; Na-Qi Cui; Bin Guo; Dong Zhu; Min Qiao (Journal of Environmental Chemical Engineering, 2026)

Unexploded ordnance detection with deep learning: A LSTM-based approach with multi-factor analysis - Yizhou Lu; Bin Ma; Qingyun Wang; Jianxing Zhang; Lei Ai; Weifan Mao; Zhao Li; Zhuting Yu; Yinglin Guo (Journal of Applied Geophysics, 2026)

Ferrocene carboxylic acid doped nickel iron hydroxide with strong built-in electric field for oxygen evolution reaction - Xin-Jie Tian; Ruo-Xin Wang; Yi-Lin Dong; Yue-Ming Li; Si-Jia Guo; Na Xu; Guanqun Han; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Toxic effects of microplastics on extracellular polymeric substances (EPS) in estuarine microalgae under stress conditions - Jianhuang Su; Jiabao Zhu; Dinglin Hou; Yan Zheng; Zongling Li; Bin Lin; Zifeng Zhou; Jie Lai; Peiyong Guo (Environmental Pollution, 2026)

A morphology-disorder dual parameter to design Ni-rich layered cathode materials - Bin Liu; Liubin Ben; Mengyu Tian; Kuiyong Liu; Yang Li; Yongxue Duan; Qianlong Sun; Bo Wang; Zhongzhu Liu; Aimin Guo; Luanna Parreira; Robson Monteiro; et al. (Chemical Engineering Journal, 2026)

Cadmium exposure impaired the uterine decidualization through inducing the imbalance of mitochondrial fusion and fission - Yin-Fei Xing; Liang Yue; Chen-Hao Wang; Cai-Jiao Zhou; Jia-Qi Ye; Shi-Jie Li; Bin Guo (Chemico-Biological Interactions, 2026)

Bulk metagenomics and machine learning unravels nitrogen metabolism patterns in extreme-temperature marine environments - Zheng Guo; Yong-Guang Li; Xiao-Lin Liu; Zhao-Jie Teng; Qi-Long Qin; Qian-Qian Cha; Zhi-Bin Wang; Shou-Qing Ni (Bioresource Technology, 2026)

Determination of fumonisins in grains and feed: an efficient clean-up method combined with lC-MS/mS - Xin Zhou; Qiang Hou; Bin Qu; Xinyu Guo; Xuesong Wang; Canping Pan; Baiqin Zheng; Aijun Li (Food Additives & Contaminants: Part A, 2026)

Assessment of dynamic drought risk and transition characteristics by combining an indicator-based approach and Markov chain model - Bin Huang; Tao Peng; Tianyi Fan; Vijay P. Singh; Xiaohua Dong; Qingxia Lin; Wenjuan Chang; Ji Liu; Yan Huang; Jiali Guo; Yinghai Li; Dan Yu (Natural Hazards, 2026)

Machine learning based thermal response study of university students under summer outdoor military training - Bin Yang; Luting Bai; Miao Guo; Zhe Li (International Journal of Biometeorology, 2026)

Denitrification in Hangzhou Bay: The role of nutrient dynamics in a tidal and human-impacted estuarine system - Yuang Guo; Xue Wu; Yangjie Li; Bin Wang; Zhi Yang; Menglu Li; Yixing Zhang; Xin Zhao; Weifang Gu; Zhihao Xu; Hongliang Li; Jianfang Chen (Marine Pollution Bulletin, 2026)

Isolation and application of Bdellovibrio and like organisms (BALOs) for controlling Aeromonas hydrophila in the American eel (Anguilla rostrata) rearing water - Yanbiao Guo; Bin Jiang; Huixiang Chen; Haifu Zhang; Jingyin Liu; Jintao lǚ; Lingxiao Li; Wenxi Zhong; Shichao Wen; Chunlan Liang; Yi Huang; Zhiping Liang; et al. (Aquaculture, 2026)

From AI modelling to validation: A 10-day pipeline for potential lead compounds validation - Bin Chen; Yuan Hu; Wen He; Guo Li; Ruiqi Liu; Jiawei Li; Xiujuan Li; Lingling Wei; Aiguo Gu; Song Yang; Changyang Chen; Xiushi Song; et al. (Pesticide Biochemistry and Physiology, 2026)

Melatonin attenuates heat stress-induced oxidative stress and apoptosis in mouse testicular Leydig cells via the KEAP1-NRF2 pathway - Xiaoyu Yu; Changping Li; Ruixi Ming; Bin Wang; Hongzhou Guo; Bin Li (Journal of Thermal Biology, 2026)

Crafting advantageous root traits by combining root restriction and dry-wet circulation to enhance rhizosphere effect and pollutant removal in constructed wetlands - Dun Guo; Jingying Zhang; Wei Bian; Bin Li; Lei Yang; Jun Lan; Yongxiang Ren (Journal of Cleaner Production, 2026)

Efficient removal of diclofenac sodium from water by chitosan/microcrystalline cellulose@polyethyleneimine hydrogel beads: Adsorption performance and mechanism study - Hongyu Wang; Henglin Xiao; Yi Xie; Xibei Tan; Wenbin Guo; Lu Li; Rongfan Chen; Bin Wang; Mingfei Wang; Dao Zhou (Journal of Environmental Sciences, 2026)

Increasing climate variability makes Southeast Asian forests more vulnerable to anthropogenic and environmental stressors - Yang Chu; Lanlan Guo; Guoyan Yang; Hongtao Xu; Tiewei Li; Xiangqi He; Huan Zheng; Shiyu Yao; Hairui Liu; Bin He (Global and Planetary Change, 2026)

α-Octene grafting modification of discarded polypropylene masks and its resource utilization in heavy crude oil - Jingying Liang; Bin Li; Xiaolei Guo; Chenrui Jiang; Xia Wang; Yunlei Zang; Yefei Wang; Gang Chen (Fuel, 2026)

Core-Shell structural regulation and freshness indicating-keeping functions of starch-based Fiber membrane and its application in fresh-cut kiwifruits - Yao Ma; Yahua Xiao; Yuxi Lang; Yiwen Bao; Jiaxin Li; Yifan Guo; Honglin Jiang; Xinwei Wang; Chunting Qu; Wenzhuo Jin; Bin Li; Xu Si (Food Research International, 2026)

A double-package delivery system based on κ-carrageenan hydrogels and vitamin E/highly branched cyclic dextrin composites: Structural characteristics and release behavior - Wentao Ma; Wei Liu; Chao Yuan; Bo Cui; Yaqi Liu; Li Guo; Bin Yu; Meng Zhao; Feixue Zou (Food Chemistry, 2026)

Integrated metabolomic and transcriptomic analysis reveals functional compound dynamics in Rosa rugosa ‘Mohong’ flowers - Huafeng Wu; Bin Liu; YinZhu Cao; GuanPeng Ma; XiaoWen Zheng; Hang Guo; Yuan Chen; Junfei Zhang; Zheng Li; ShunZhao Sui (Food Bioscience, 2026)

Associations of PM2.5 carbonaceous and ionic constituents with fractional exhaled nitric oxide (FeNO): A panel study with 16 follow-up visits over 4 years - Nan Zhang; Yuqi Guo; Deyan Wu; Zinuo Li; Jialin Wang; Nan Zhang; Jia Xu; Xueli Yang; Qiang Zhang; Changping Li; Shi Zhao; Xumei Zhang; et al. (Environmental Research, 2026)

Quantifying the vulnerability of karst groundwater to emerging organic compounds in southwest China - Rui An; Bin Li; Jie Li; Shengpin Li; Qianying Zhu; Xiaoyu Liu; Huaming Guo; Wenpeng Li; Kun Liu (Environmental Pollution, 2026)

Estimation of grassland aboveground biomass in the Three-Rivers Source Region with explainable machine learning - Zhe Wang; Xiuying Wang; Baocheng Wei; Qiang Bie; Yaowen Xie; Ruixiang Xiao; Xiaoyun Wang; Xiaodong Li; Binrong Zhou; Zecheng Guo; Bin Qiao (Environmental Modelling & Software, 2026)

Elimination of buried-interface voids by suppressing solvent residue towards high-efficiency CsPbI2Br perovskite solar cells - Haoxuan Guo; Ruoyuan Xie; Changqian Li; Junhui Ran; Xiaoxue Ren; Yongbo Yuan; Bin Yang (Chemical Engineering Journal, 2026)

Nitrosocosmicus AOA-driven anammox bacteria enrichment in counter-current aerated biofilters: Unraveling the start-up mechanism of the novel autotrophic nitrification–denitrification process - Kehuan Guo; Dong Li; Bin Ji; Luyao Teng; Shuai Li; Huiping Zeng; Jie Zhang (Bioresource Technology, 2026)

Exploring the mediating role of oxidative stress in the relationship between PM2.5 components and adverse pregnancy outcomes: Impacts on nucleic acids, proteins, and lipids - Yan Jiang; Deyan Wu; Yuqi Guo; Jia Xu; Hongjuan Liu; Aifeng Jia; Chen Li; Duan Ju; Liqiong Guo; Xueli Yang; Qiang Zhang; Bin Han; et al. (Atmospheric Pollution Research, 2026)

Dominant environmental influencing factors of carbon dioxide fluxes in lakes and reservoirs at different time scales - Xiangqi He; Ankur Desai; Ivan Mammarella; Xixi Lu; Xiaoyan Li; Huizhi Liu; Uwe Spank; Lanlan Guo; Hongtao Xu; Yang Chu; Xingming Hao; Bin He (Science China Earth Sciences, 2026)

Synthesis and fungicidal evaluation of novel 2-phenyl thiazole derivatives - Xiaofeng Guo; Han Wang; Bin Zhao; Zhijin Fan; He Li (Pesticide Biochemistry and Physiology, 2025)

Seismic behavior of a jacket-type offshore substation with inclined pile foundations on liquefiable seabed - Ling-Yu Xu; Qiang Ma; Bin Li; Ye-Jun Sun; Jun Wang; Guo-Xing Chen; Fei Cai (Ocean Engineering, 2025)

Optimizing thinning intensity for large-diameter poplar plantations: A UAV-LiDAR-based growth assessment - Tianle Li; Chenyan Lv; Qiang Guo; Dongdong Li; Bin Dong; Xuehai Tang; Junlong Liu; Tingting Miao; Changjun Ding; Youquan Jiao; Xiang Gao (Forest Ecology and Management, 2025)

Bioactive pterostilbene encapsulated in zein via an in-situ co-precipitation strategy for efficient antimicrobial and fruit preservative - Chunli Fang; Zhinan Fu; Nan Wei; Jia Wei; Shuying Li; Ting Feng; Zicheng Tan; Junyou Wang; Bin Wu; Xuhong Guo (Food Hydrocolloids, 2025)

Associations between residential greenness exposure during pregnancy and bone mineral density in early childhood - Yibing Zhu; Linxi Tang; Yudiyang Ma; Bin Sun; Haibo Li; Feipeng Cui; Jingmin Guo; Yaohua Tian; Chong Miao (Environmental Research, 2025)

Effects of surface polarity on ferromagnetic properties and magnetic anisotropy of Gd-implanted GaN wafers - Sen Chen; Wei Cheng; Chungang Guo; Zeyu Yin; Qian Li; Jiangfeng Ren; Bin Liao; Minju Ying (Chemical Engineering Journal, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

Effect of turbulence induced shear on continuous synthesis of imidazolium ionic liquid 1-butyl-3-methylimidazolium bromide ([BMIM]Br) in a high shear rate Taylor-Couette flow reactor - Rui Jiang; Guang Li; Bin Li; Yanhong Guo; Xiaogang Yang (Chemical Engineering Journal, 2025)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

Research and application of CMA numerical weather prediction in meteorological support for the Beijing Winter Olympics (2022) - Guo Deng; Xueshun Shen; Huiling Yuan; Jiandong Gong; Hua Tong; Liantang Deng; Zhifang Xu; Jing Chen; Jian Sun; Yong Wang; Mingxuan Chen; Jianjie Wang; et al. (Science China Earth Sciences, 2025)

Influence of Trapping Forces on the Morphological Redistribution of DNAPL During Surfactant Enhanced Aquifer Remediation - Huiying Li; Xin Huang; Bin Yang; Zongze Shen; Bin Wu; Guanlin Guo; Yuanyuan Li (International Journal of Environmental Research, 2025)

Detection of mercury in single mammalian cells at attogram level by SC-ICP-MS - Xueyan Wang; Po Tang; Hao Liu; Yingying Li; Hua Guo; Pengyang Li; Deming Han; Nian Liu; Lihong Liu; Bin He; Ligang Hu; Guibin Jiang (Analytica Chimica Acta, 2025)

Research on the Mechanism of Complex Water-flooded Layers and Well Logging Evaluation Methods in the M Oilfield - Wen-Yuan He; Ya-Dong Wu; Li-Xiang Feng; Chang-Xi Li; Jin-Bin Wan; Guo-Hui Ni (Applied Geophysics, 2025)

Characteristics of Compound Heatwave and Heavy Precipitation Events in the Huai River Eco‐economic Corridor - Daoying Zhong; Yuqing Zhang; Bin Guo; Xinxin Li; Taizheng Liu (International Journal of Climatology, 2025)
Climate warming has increased the frequency of compound weather events, with alternating heatwaves and heavy precipitation often causing impacts greater than individual extremes. However, studies on compound events involving their sequential occurrence, such as compound heatwaves followed by heavy precipitation (CHWHP) and heavy precipitation followed by heatwaves (CHPHW) within short intervals (≤ 7 days), remain limited. This study investigated spatiotemporal patterns of CHWHP and CHPHW events in the Huai River Eco‐economic Corridor (HREC) during 1981–2020. Results showed CHWHP events increased by 0.046 events/decade within a 5‐day interval, with frequency and magnitude hotspots in the southwestern and eastern HREC. Although CHWHP and CHPHW events were infrequent in the northwest, their occurrence increased by 300%–400% during 2001–2020 compared to 1981–2000. CHWHP events are notably more intense and frequent than heatwaves not followed by heavy precipitation. The 2018 case study revealed that mid‐tropospheric anomalies, notably 500 hPa geopotential height and cloud cover, influenced CHWHP and CHPHW events. Heatwaves featured high pressure and less cloud cover, boosting solar radiation and atmospheric stability, whereas heavy precipitation involved moisture convergence and diminished radiation from increased clouds. These findings highlight the influence of circulation, radiation and moisture transport on compound heatwave‐precipitation events.

Latest Pleistocene to mid-Holocene vegetation changes revealed by multi-proxy analyses at Lop Nur in the eastern Central Asia - Yi-Feng Yao; Kai-Qing Lu; Feng Qin; Guo-An Wang; Qin-Min Yang; Xin-Ying Zhou; David K. Ferguson; Gan Xie; Jin-Feng Li; Bin Sun; Stephen Blackmore; Yu-Fei Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Preparation of pinolenic acid-embedded Lactiplantibacillus plantarum H6 Pickering emulsions stabilized with different concentrations of sodium alginate - Shengdong Bao; Lidan Guo; Jingjing Xuan; Liu Yang; Yue Li; Bin Jiang; Dayong Ren (Food Bioscience, 2025)

Mechanisms of high yield formation and carbon budget surplus in ratoon rice and its rhizosphere microecological responses - Jinying Li; Hailong Xu; Bin Qin; Bianhong Zhang; Mengying Chen; Peiying Weng; Chunlin Guo; Chaojie Lan; Jingnan Zou; Zhimin Lin; Wenfang Lin; Wenfei Wang; et al. (Field Crops Research, 2025)

Propranolol-loaded multifunctional hydrogel enhances the repair of infected bone defects via sympathetic microenvironment remodelling - Wenzhe Sun; Lian Zeng; Pengqing Zhang; Hongwei Lu; Bing Ye; Yizhou Wan; Yi Xu; Jialin Yu; Tingfang Sun; Yanzhen Qu; Bin Wu; Xiaohan Li; et al. (Chemical Engineering Journal, 2025)

Plasma engineering defect for constructing high-density Ru single atoms and RuCo alloy nanoparticles synergistic catalytic system to achieve efficient hydrogen evolution - Haolin Zeng; Yingchun Guo; Tongtong Li; Guangliang Chen; Jinfeng Qiu; Bin He; Peisong Tang (Chemical Engineering Journal, 2025)

Engineered aggregation-induced emission luminogens-based framework with CO-releasing property for accelerating diabetic wound healing - Minghai Zhao; Jialin Huang; Hao Yang; Ronghua Yang; Shuang Guo; Zeyu Liu; Qiulin Xie; Minying Li; Zhijin Fan; Peihong Xiao; Zhijun Zhang; Xu Chen; et al. (Chemical Engineering Journal, 2025)

Metabolic pathways and engineering prospects of eco-friendly immobilized sulfur-ferrous sulfide filler in sustainable nitrate removal - Yongguang Li; Zheng Guo; Linjie Gao; Zhi-Bin Wang; Shou-Qing Ni (Chemical Engineering Journal, 2025)

Internally coupled concave nanobox@quantum dots nanoassemblies for SERS/fluorescence/colorimetric trimodal detection of prognostic biomarker in acute ischemic stroke - Wei-Bin Wang; Jian-Jun Li; Lin-Lin Fan; Jing-Yuan Wang; Guo-Jun Weng; Jian Zhu; Jun-Wu Zhao (Chemical Engineering Journal, 2025)

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

A double seed-taking cotton precision dibbler for resource-saving agriculture: A further research - Zibin Mao; Bin Hu; Luochuan Xu; Mengyu Guo; Junwei Li; Xin Luo (Computers and Electronics in Agriculture, 2025)

Distribution, partitioning behaviors, and source identification of legacy and emerging per- and polyfluorinated alkyl substances in the Pearl River Estuary, South China - Bin Tang; Can Peng; Dong-Jing Zhou; Kai-Yi Wu; Fei Tian; Hai-Gang Chen; Shi-Yi Zhang; Bo-Wen Li; Guo-Cheng Hu; Ming-Zhong Ren; Jing Zheng (Water Research, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Long-chain fatty acid esters produced by Sporidiobolus pararoseus or Rhodotorula mucilaginosa enhance the fat flavor of soy sauce fermented by defatted soybeans - Shuoshuo Zhao; Xiaochao Xu; Zehui Li; Qifeng Wang; Ting Guo; Bin Dong; Yunping Yao; Guozhong Zhao (Food Chemistry, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Adaption strategies of extremophiles and the construction of wastewater treatment systems driven by extremophiles - Zheng Guo; Yong-Guang Li; Zhi-Bin Wang; Xin Zhou; Shou-Qing Ni (Environmental Research, 2025)

MOF-derived TiO2 nanosheets loaded with Nb2O5 for enhanced catalytic hydrogenation of MgH2 - Zhicheng Yang; Weiqi Sun; Yiting Bu; Ruoyang Zhang; Zexuan Yang; Bin Li; Lixian Sun; Fen Xu; Ting Yu; Wenwei Guo; Yi Liu; Zhengyi Liang (Chemical Engineering Journal, 2025)

Synergistically improving open-circuit voltage and fill factor via utilizing a natural pigment as efficient interconnect layer for high-performance perovskite-organic tandem solar cells - Bin Zhang; Yunqiang Du; Xinling Li; Aiqin Li; Menglan Lv; Weile Guo; Fei Guo; Ergang Wang (Chemical Engineering Journal, 2025)

Enhancement of the fluid diffusion-dominated mineralization storage in the wet supercritical CO2 system - Aoxing Qu; Meixue Liu; Yingqi Huang; Xianwei Guo; Qingping Li; Xin Lv; Bin Wang; Jiafei Zhao; Lei Yang; Yongchen Song (Chemical Engineering Journal, 2025)

Divergent drivers of litter decomposition in karst and non-karst tropical rainforests: a comparison - Qi Liu; Xinli Chen; Fuzhao Huang; Jianxing Li; Ting Chen; Fang Lu; Xiankun Li; Dongxing Li; Wusheng Xiang; Bin Wang; Hongming Zhao; Ruixia Ma; et al. (CATENA, 2025)

Influx of Metabolites into Cerebrospinal Fluid in Intracerebral Hemorrhage is Associated with Increased Central Inflammation: a Retrospective Observational Study - Huaying Zhang; Yuxia Zhong; Jinlian Shao; Kaijian Sun; Lingling Zhang; Yulong Zhang; Yu Xiao; Xiangyu Zuo; Zhixin Li; Tianhui Zeng; Zizheng Gao; Chun Yang; et al. (Translational Stroke Research, 2025)

Identification of novel small molecules as potential SGLT2 inhibitors through combined virtual screening and experimental validation - Fei Qin; Huicong Zeng; Li Zhou; Zhenhua Zhou; Yongxin Mao; Youyan Zeng; Rongxiang Guo; Kaixian Chen; Dongyu Zhao; Weiwei Yao; Bin Zhang; Qian Zhou; et al. (Molecular Diversity, 2025)

Evidence for cognitive compensation mechanism in the postoperative delirium: a prospective multi-modal neuroimaging cohort study - Guo-Bin Zhang; Hao-Yi Li; Jia-Mei Lv; Xiao-Kang Zhang; Yong-Gang Wang; Yun-Yun Duan; Hong-Yan Chen; Zhi-Zheng Zhuo; Ya-Ou Liu; Hua-Wei Huang (Brain Imaging and Behavior, 2025)

Quantifying the underestimated plant potential for phosphorus removal in constructed wetlands: Revealing the mediating mechanism of radial oxygen loss - Dun Guo; Jingying Zhang; Wei Bian; Yanbin Chi; Bin Li; Qinting Ren; Lei Yang; Jun Lan; Yongxiang Ren (Water Research, 2025)

Antiviral activity of Stephania japonica extract against porcine epidemic diarrhea virus infection - Yong Zhao; Baochao Fan; Yi Wang; Min Sun; Rongli Guo; Tao Tang; Mi Hu; Bin Li (Veterinary Microbiology, 2025)

A trivalent enteric coronaviruses inactivated vaccine provides effective protection against PEDV, TGEV, and PDCoV - Liyuan Fan; Xin Yi; Chunyan Zhong; Chuangye Yang; Ziyi Niu; Xiaofeng Xue; Wei Wang; Rongli Guo; Jiale Ma; Yinhe Zha; Jianhong Shu; Jizong Li; et al. (Veterinary Microbiology, 2025)

CiOs1, CiOs4 and CiOs5 modulate temperature-dependent growth and fludioxonil resistance in Calonectria ilicicola, causing soybean red crown rot - Xiujuan Li; Shuzhou Liu; Shuai Xie; Hao Hu; Guo Li; Bin Chen; Jiawei Li; Lingling Wei; Wenchan Chen; Xiushi Song; Wenyong Shao; Changjun Chen (Pesticide Biochemistry and Physiology, 2025)

Multi-objective optimal Bi-level scheduling of hybrid mobile-stationary energy storage systems for flexible distribution network - Bo Yang; Guo Zhou; Shuai Zhou; Yuanweiji Hu; Bin He; Zhengxun Guo; Zhibiao Luo; Hongbiao Li; Dengke Gao; Jingbo Wang; Lin Jiang (Journal of Cleaner Production, 2025)

Synergistic catalysis of CoN sites and Co nanoparticles for efficient CO -free hydrogen production from ammonia decomposition - Bin Kang; Zhilong Chang; Runduo Zhang; Zhigang Shen; Kun Wang; Xiaonan Guo; Haotian Wu; Daiqiang Li; Dexin Liu; Ying Wei; Jingbo Jia; Zhou-jun Wang (Fuel, 2025)

Formation and photoluminescence mechanism of fluorescent brightener-derived full-color emissive bioactive carbon dots for targeted microbial theranostics - Zhao Gao; Meng Li; Haolin Chen; Yuxiao Xiong; Yong Shao; Jieyi Chen; Bin Wu; Biwen Yang; Binggang Ye; Zhouyi Guo; Bo Xu; Shaoxin Li; et al. (Chemical Engineering Journal, 2025)

Potential role of the counter-current mainstream aerated biofilter in the competitive enrichment of copiotrophic ammonia-oxidizing archaea at low air-water ratios - Kehuan Guo; Dong Li; Bin Ji; Zhao Zhang; Luyao Teng; Shuai Li; Huiping Zeng; Jie Zhang (Chemical Engineering Journal, 2025)

Long-term green manuring increases phosphorus availability in soil by modifying microbial functional genes and enzyme activities - Xiaodong Chen; Yuan Wang; Bin Guo; Junli Liu; Gaoyang Qiu; Kuzyakov Yakov; Hua Li (Applied Soil Ecology, 2025)

Evaluating the sustainability potential of perennial rice in southeastern China by comparing yield, environmental impacts and economic benefits - Hailong Xu; Bianhong Zhang; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Chunlin Guo; Zhimin Lin; Qiaohong Fan; Changxun Fang; Zhixing Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Mechanical Characterization and Dual-Layer Discrete Element Modeling of Mactra veneriformis - Bin Xu; Yazhou Yang; Hangqi Li; Guangcong Chen; Yizhi Chang; Feihong Guo; Hao Wu; Jixuan Zhao; Zijing Liu; Guochen Zhang; Xiuchen Li; Hanbing Zhang; et al. (Fishes, 2025)
The discrete element model of Mactra veneriformis currently employs an oversimplified multi-sphere approach using EDEM’s Hertz–Mindlin model, assuming uniform shell–flesh mechanical properties. This study developed an advanced dual-layer flexible bonding model through comprehensive biomechanical testing. Mechanical properties and shell morphology were experimentally characterized to inform model development. Parameter optimization combined free-fall experiments with Plackett–Burman screening, steepest ascent method, and Box–Behnken RSM, yielding optimal contact parameters: flesh–flesh stiffness (X1) = 3.64 × 1011 N/m3, shell–flesh interface (X3) = 1.48×1013 N/m3, shell–shell tangential stiffness (X6) = 3.23 × 1012 N/m3, and normal strength (X7) = 8.35 × 106 Pa. Validation showed only 4.89% deviation between simulated and actual drop tests, with hydraulic impact tests confirming excellent model accuracy. The developed model accurately predicts mechanical behavior and shell fracture patterns during harvesting operations. This research provides a validated numerical tool for optimizing clam cultivation and harvesting equipment design, offering significant potential to reduce shell damage while improving harvesting efficiency in bivalve aquaculture systems.

Corrigendum to “Environmental DNA exploring the distribution of Indo-Pacific humpback dolphins and fish diversity from the Pearl River Estuary, China” [Mar. Pollut. Bull. 216 (2025) 118026] - Bin Sun; Dingyu Luo; Nuoyan Huang; Lang Guo; Xikai Tang; Zhicheng Li; Zhenhui Xie; Fei Liu; Xiyang Zhang; Yuping Wu (Marine Pollution Bulletin, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

(±)-Laevigiol A, a pair of new enantiomeric phenylpropanoids from the leaves and twigs of Croton laevigatus Vahl. and their anti-Alzheimer’s disease activities - Yu-Bin Lu; Mi-Na Yang; Hui-Jie Li; Li-Jia Ye; Le-Le Guo; Miao Zhang; Chun-Min Liu; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Phytochemistry Letters, 2025)

Rainfall-mediated CO2 flux dynamics in the Three Gorges Reservoir: Dominance of enzyme activity over carbon degradation and algal dynamics under dissolved organic carbon inputs - Kaikai Deng; Yixuan Li; Peng Yan; Bin Chen; Guijiao Lin; Qiang He; Jinsong Guo (Journal of Environmental Chemical Engineering, 2025)

Bisulfite-free whole-genome mapping of 5-methylcytosine at single-base resolution by NTD-seq - Min Wang; Neng-Bin Xie; Fang-Yin Gang; Shan Zhang; Li Zeng; Tong-Tong Ji; Jun Xiong; Xia Guo; Ying Hao; Yu Liu; Bi-Feng Yuan (Science China Life Sciences, 2025)

Numerical Simulation of the Rock-breaking Mechanism for Heterogeneous Rock with High-voltage Electrical Pulse - Xinhui Guo; Yuwei Li; Yishan Pan; Aiwen Wang; Bin Huang (Rock Mechanics and Rock Engineering, 2025)

Synergistic Detrital Zircon U-Pb and REE Analysis for Provenance Discrimination of the Beach-Bar System in the Oligocene Dongying Formation, HHK Depression, Bohai Bay Basin, China - Jing Wang; Youbin He; Hua Li; Tao Guo; Dayong Guan; Xiaobo Huang; Bin Feng; Zhongxiang Zhao; Qinghua Chen (Journal of Marine Science and Engineering, 2025)
The Oligocene Dongying Formation beach-bar system, widely distributed in the HHK Depression of the Bohai Bay Basin, constitutes a key target for mid-deep hydrocarbon exploration, though its provenance remains controversial due to complex peripheral source terrains. To address this, we developed an integrated methodology combining LA-ICP-MS zircon U-Pb dating with whole-rock rare earth element (REE) analysis, facilitating provenance studies in areas with limited drilling and heavy mineral data. Analysis of 849 high-concordance zircons (concordance >90%) from 12 samples across 5 wells revealed that Geochemical homogeneity is evidenced by strongly consistent moving-average trendlines of detrital zircon U-Pb ages among the southern/northern provenances and the central uplift zone, complemented by uniform REE patterns characterized by HREE (Gd-Lu) enrichment and LREE depletion; geochemical disparities manifest as dual dominant age peaks (500–1000 Ma and 1800–3100 Ma) in the southern provenance and central uplift samples, contrasting with three distinct peaks (65–135 Ma, 500–1000 Ma, and 1800–3100 Ma) in the northern provenance; spatial quantification via multidimensional scaling (MDS) demonstrates closer affinity between the southern provenance and central uplift (dij = 4.472) than to the northern provenance (dij = 6.708). Collectively, these results confirm a dual (north–south) provenance system for the central uplift beach-bar deposits, with the southern provenance dominant and the northern acting as a subsidiary source. This work establishes a dual-provenance beach-bar model, providing a universal theoretical and technical framework for provenance analysis in hydrocarbon exploration within analogous settings.

Environmental DNA exploring the distribution of Indo-Pacific humpback dolphins and fish diversity from the Pearl River Estuary, China - Bin Sun; Dingyu Luo; Nuoyan Huang; Lang Guo; Xikai Tang; Zhicheng Li; Zhenhui Xie; Fei Liu; Xiyang Zhang; Yuping Wu (Marine Pollution Bulletin, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Dual stable isotope tracing the source and composition of biogenic substance in microalgae-bacteria symbiosis: What do the bacteria contribute to the microalgae bloom? - Bin Chen; Wenjuan Ouyang; Jixiang Yang; Youpeng Chen; Peng Yan; Fang Fang; Zhe Li; Jinsong Guo (Science of The Total Environment, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Development of dynamic topology optimization method for offshore jacket platforms - Yu-Tao Guo; Kang Ge; Chen Wang; Xiao-Long Zhao; Bin-Bin Li (Ocean Engineering, 2025)

Companion animals as sources of hazardous critically important antimicrobial-resistant Escherichia coli: Genomic surveillance in Shanghai - Yiwen Chen; Min Li; Bingqing Sun; Luming Xia; Yifei Zhang; Jun Feng; Min Chen; Zile Cheng; Chao Lv; Weiye Chen; Jiewen Huang; Qingtian Li; et al. (Journal of Hazardous Materials, 2025)

SCAGAT: A scene-aware ensemble graph attention network for global PM2.5 pollution mapping via land–atmosphere interactions - Kaixu Bai; Ke Li; Songyun Qiu; Zhe Zheng; Penglong Jiao; Yibing Sun; Liuqing Shao; Chaoshun Liu; Xinran Li; Zhengqiang Li; Jianping Guo; Ni-Bin Chang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Characterization and metabolism pathway of volatile compounds in blueberries of different varieties and origins analyzed via HS-GC-IMS and HS-SPME-GC–MS - Xu Xie; Yuehua Wang; Bosu Wen; Jinlong Tian; Zhen Cheng; Siyi Tang; Yujie Nie; Xilin Wu; Xin Guo; Bin Li (Food Chemistry, 2025)

Comprehensive insights into the mechanism of flavor formation in mandarin fish (Siniperca chuatsi) with inoculated fermentation - Ke-Xun Guo; Bin Hu; Yi Jiang; Zeng-Yong Li; Jun Qi; Man-Man Yu (Food Chemistry, 2025)

Enrichment of Nitrosocosmicus-AOA in situ and their vertical distribution characteristics in aerated biofilters - Kehuan Guo; Dong Li; Luyao Teng; Bin Ji; Shuai Li; Huiping Zeng; Jie Zhang (Environmental Research, 2025)

Effects of mineral admixtures on time-dependent behavior of high-strength self-compacting concrete-filled steel tubes - Huan-Chi Ma; Yue Geng; Ren-Le Bin; Guo-Dong Li; Yu-Yin Wang (Engineering Structures, 2025)

Bacterial-targeting liposomes for synergistic nitric oxide/methicillin therapy in MRSA-infected osteomyelitis - Kai Lv; Zhen Wang; Wenjun He; Zijing Feng; Hui Xing; Yuanfang Jiang; Yingtong Lu; Jingjie Shang; Bin Guo; Hao Xu; Guowei Li; Bo Ning; et al. (Chemical Engineering Journal, 2025)

Identifying the effect of architecture morphology on wind fields and PM2.5 dispersion at the urban block scale via a combined scheme - Bin Guo; Lu Li; Xiaowei Zhu; Zheng Wang; Miaoyi Chen; Lin Pei; Tengyue Guo (Urban Climate, 2025)

Comparative analysis of thermal and visual comfort perceptions of outdoor military training of University students - Bin Yang; Luting Bai; Zhe Li; Miao Guo; Bo Hong (Urban Climate, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Performance of ethanol transformable microemulsions and remediation of salinized oil – contaminated soils - Xiaoning Feng; Nan Shi; Shuhai Guo; Bo Wu; Gang Li; Bin Lou; Xiujie Yang; Yifan Wang; Ping Xiang; Xiahong He; Dong Liu (Journal of Hazardous Materials, 2025)

Regional transport characteristics of PM2.5 pollution events in Beijing during 2018–2021 - Dejia Yin; Qian Song; Yuanxi Guo; Yueqi Jiang; Zhaoxin Dong; Bin Zhao; Shuxiao Wang; Da Gao; Xing Chang; Haotian Zheng; Shengyue Li; Yunting Li; et al. (Journal of Environmental Sciences, 2025)

Elucidating the influence of alumina mineral on sodium storage performance of biomass-derived hard carbon anode - Hang Guo; Jia-He Lv; Run-Dong He; Bin He; Xiao-Ling Dong; Wen-Cui Li (Fuel, 2025)

DSSAT modeling of oilseed flax (Linum usitatissimum L.): Sensitivity analysis of yield to weather variability and nitrogen application - Zechen Lin; Yue Li; Gerrit Hoogenboom; Yuhong Gao; Bing Wu; Ling Wu; Lili Wu; Hui Zhou; Bin Yan; Peina Lu; Jie Tang; Shunchang Su; et al. (Field Crops Research, 2025)

Nitrogen reduction and split application increased grain yield and agronomic nitrogen use efficiency of oilseed flax (Linum usitatissimum. L) by increasing nitrogen status - Ming Wen; Yuhong Gao; Lizhuo Guo; Bin Yan; Peina Lu; Bin Wu; Yifan Wang; Yue Li; Zhengjun Cui; Peng Xu; Haidi Wang; Yuanyuan Cui; et al. (Field Crops Research, 2025)

Effects of nitrogen fertilization on antibiotic resistance gene spread from soil to floodwater in paddy fields - Yuan Wang; Xiaodong Chen; Junwei Jin; Bin Guo; Gaoyang Qiu; Xin Wang; Hanghai Zhou; Hua Li (Environmental Research, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Improving short-term forecasting of surface dust concentration in Northern China: Integrating machine learning with multi-numerical models - Ziwei Yi; Zhaoliang Zeng; Yaqiang Wang; Weijie Li; Bihui Zhang; Hailin Gui; Bin Guo; Wencong Chen; Huizheng Che; Xiaoye Zhang (Atmospheric Pollution Research, 2025)

Inferring causal associations in hydrological systems: a comparison of methods - Hanxu Liang; Wensheng Wang; Dedi Liu; Bin Chen; Li Guo; Hu Liu; Siyi Yu; Dan Zhang (Stochastic Environmental Research and Risk Assessment, 2025)

Long non-coding RNA HOXA11-AS inhibits apoptosis, induces proliferation, and promotes autophagy via the miR-214-3p/ATG12 axis in acute T lymphoblastic leukemia - Rui Zhang; YuanYuan Zhang; XiaoFei Li; ShaoHua Wang; Jiao Li; ShuoChun Shao; Bin Liu; WeiWei Guo; Min Shi (Journal of Molecular Histology, 2025)

Heterosis in Growth and Survival of Intraspecific Crosses Between Two Geographically Different Wild Populations of Manila Clam (Ruditapes philippinarum) - Hongda Li; Shikang Li; Hong Guo; Shuhang Lv; Bin Wang; Jinhong Bi; Hongtao Nie (Journal of Ocean University of China, 2025)

Mapping carbon emissions and exploring its spatiotemporal dynamic based on local climate zones and landscape ecology theory across Beijing-Tianjin-Hebei - Tingting Xie; Bin Guo; Dingming Zhang; Peiqing Jing; Haojie Wu; Shixin Zhang; Jun Li; Chengye Zhang (Sustainable Cities and Society, 2025)

Unveiling the mechanism of Gelatin's influence on starch digestibility: A focus on amylopectin chain distribution - Yifan Chen; Yue Cheng; Wei Gao; Xuemin Kang; Bin Yu; Li Guo; Meng Zhao; Chao Yuan; Bo Cui (Food Hydrocolloids, 2025)

Prediction of the exposure profile of bisphenol A in Chinese population by physiologically-based pharmacokinetics modeling - Jun He; Li Zhang; Hong Jin; Daoyuan Yang; Li Jia; Bin Han; Haixia Sui; Jiabin Guo (Environmental Pollution, 2025)

Control of molecular stacking and film morphology of phosphomolybdic acid hole transporting layer via processing solvent for high-efficiency organic solar cells - Peng Li; Yaozhao Li; Shaobo Ding; Bin Wei; Xuyong Yang; Daobin Yang; Guo Chen (Chemical Engineering Journal, 2025)

Innovative electrooxidation-adsorption technology for efficient iodine recovery from ultrahigh Cl/I ratio underground brine - Bin Yu; Leijin Wang; Zheng Li; Haixia Liang; Kaiyu Zhao; Yafei Guo; Tianlong Deng (Chemical Engineering Journal, 2025)

Pollen-inspired novel silver/silica composite microsphere capable of synergistic bacteria-killing for bacteria-infected wound treatment - Hong Zhang; Guanyu Wang; Kang Qin; Ruipeng Chen; Wei Pang; Xuekun Bai; Ziming Li; Wengeng Guo; Bin Zheng; Huanying Zhou; Zhixian Gao (Chemical Engineering Journal, 2025)

High content of single-atomic sulfur in nano carbon spheres boosting potassium storage performance - Bin Cao; Zirong Guo; Huan Liu; Yu Ma; Wei Zhao; Yiheng Yang; Ang Li; Huaihe Song; Yaxiong Yang; Zhenglong Li; Wubin Du (Chemical Engineering Journal, 2025)

High spatiotemporal resolution vegetation index time series can facilitate enhanced remote sensing monitoring of soil salinization - Haohao Liu; Bin Guo; Xingchao Yang; Jinxia Zhao; Mengjian Li; Yujie Huo; Jianlin Wang (Plant and Soil, 2025)

Constructions and immunogenicity evaluations of two porcine epdemic diarrhea virus-like particle vaccines - Hong Xu; Mengdi Yang; Shiyu Liu; Fangyuan Zheng; YuPeng Li; Yunchuan Li; Chuanhong Wang; Jiali Qian; Yongxiang Zhao; Shanshan Yang; Min Sun; Xu Song; et al. (Veterinary Microbiology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Two new compounds from Pentadesma butyracea and their biological activities - Yue Yang; Li Hua Gong; Fu Hua Peng; Tao Jiang; Jian Guo Hu; Hong Dong Liu; Bin Li; Yin Xia Yang; Jing Ying Peng; Xue Mei Gao (Phytochemistry Letters, 2025)

Experimental and computational study on xylan pyrolysis: The effect of branch structures - Bin Hu; Wen-ming Zhang; Xue-Wen Guo; Ji-hong Li; Xiao Yang; Zhi-mo Fang; Ji Liu; Qiang Lu (Fuel, 2025)

A novel approach to bulk-phase hydrogenation using an extremely high-loading sulfide NiMoW/SiO2 catalyst - Fengyu Tian; Guangzheng Sun; Xianfu Zeng; Shuwen Xie; Yidi Wang; Zifan Wu; Bin Liu; Yuan Pan; Bin Dong; Yichuan Li; Yanpeng Li; Hailing Guo; et al. (Fuel, 2025)

Identification of key taste and nutrient components in 12 blueberry varieties using widely targeted metabolomics - Xu Xie; Yuehua Wang; Bosu Wen; Xin Guo; Zhen Cheng; Xu Si; Zhiying Li; Yujie Nie; Jiaqi Yang; Bin Li (Food Bioscience, 2025)

The modifying role of residential greenness on the association between heat waves and adverse birth outcomes: Results from the ELEFANT project - Yuxuan Ma; Yuanyuan Yu; Lei Zhao; Qisijing Liu; Jiayan Ni; Zi Lin; Bin Chen; Weixia Li; Huishu Lin; Yuhong He; Shuhao Shi; Jianqiong Zheng; et al. (Environmental Research, 2025)

Kinetic mechanism study of mixed ion exchange resins gasification in supercritical water - Le Wang; Linqing Mao; Ao Li; Zhiyong Peng; Lei Yi; Bin Chen; Hui Jin; Yunan Chen; Liejin Guo (Biomass and Bioenergy, 2025)

BTK and YKL-40 Levels and Their Association with Acute AQP4-IgG-Positive Neuromyelitis Optica Spectrum Disorder - Jing Liu; Gaoning Wang; Mengya Shi; Ruo-Yi Guo; Congcong Yuan; Yulin Wang; Arshad Mehmood; Lu Zhang; Bin Li (Molecular Neurobiology, 2025)

STC2 regulates the proliferation, migration and glycolysis of glioma cells through modulating ITGB2 - Zefeng Wei; Dengfeng Ge; Jie Bu; Xuenan Wang; Tao Zhong; Xiaoxiao Gongye; Bin Zhang; Feng Yan; Chunyan He; Runhan Guo; Jiayi Li; Zhenzhen Jin (Metabolic Brain Disease, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Exploring the effect of the architecture morphology on urban ventilation at block scale using CFD-GIS and random forest combined method - Bin Guo; Miaoyi Chen; Xiaowei Zhu; Zheng Wang; Lu Li; Lin Pei; Hailong Chen; Puhao Chen; Tengyue Guo (Sustainable Cities and Society, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Recent advances on Bi12O17Cl2-based photocatalysts for energy and environmental application - Xiao-Ju Wen; Xiao-Hang Qiao; Yu-Xin Li; Hai Guo; Hao-Zhe Li; Xian-Kun Wu; Bin-Bin Qian; Qi-Hui Xu; Zong-Tang Liu; Zheng-Hao Fei (Journal of Cleaner Production, 2025)

Microbial characteristics and CO2 diffuse emission in the Mt. Changbai volcanic field, northeast China - Yutao Sun; Xingxing Li; Zhengfu Guo; Wenbin Zhao; Yue Zhang; Peizhan Li; Xiaoyong Zhao; Yaru Li; Bin Hong (Journal of Asian Earth Sciences, 2025)

LC-MS profiling reveals metabolic dynamics in Apis mellifera worker bee larvae–pupae transition - Zhen Li; Shiqing Zhong; Bin Liu; Lizhi Li; Haibo Zhang; Weikun Guan; Dongsheng Guo (Journal of Asia-Pacific Entomology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Sn doping in In2O3-x nanoparticle achieving its synergy with oxygen vacancy towards high-efficiency electrocatalytic CO2 reduction and upcycling of spent liquid crystal display panels - Zhiyuan Ren; Bin Li; Yufeng Wu; Hui Liu; Feng Guo; Shaonan Tian; Jun Yang (Chemical Engineering Journal, 2025)

Self-healing physiological monitoring epidermal sensors of dual conductivity pathway with self-adaptive transformation - Liao Ziming; Zhu Ximing; Zhang Shuquan; Liu Tingting; Song Jiamei; Wang Yuhong; Guo Yanping; Li Xiaohong; Ji Xiaoyuan; Yao Bin (Chemical Engineering Journal, 2025)

Experimental study on supercritical water gasification of grease trap sludge in a continuous reactor - Le Wang; Ao Li; Linqing Mao; Zhiyong Peng; Lei Yi; Bin Chen; Yunan Chen; Liejin Guo (Biomass and Bioenergy, 2025)

Impact of meteorological uncertainties on PM2.5 forecast: An ensemble air quality forecast study during 2022 Beijing Winter Olympics - Wei Wen; Liyao Shen; Li Sheng; Xin Ma; Jikang Wang; Chenggong Guan; Guo Deng; Hongqi Li; Bin Zhou (Atmospheric Environment, 2025)

Establishing age-group specific reference intervals of human salivary proteome and its preliminary application for epilepsy diagnosis - Nianci Xue; Xia Xia; Yini Wang; Xianju Li; Nairen Zheng; Yi Wang; Baoying Gong; Bin Zhang; Yanjia Chen; Yue Chen; Yanjuan Li; Hong Cao; et al. (Science China Life Sciences, 2025)

Deploying an Integrated Fiber Optic Sensing System for Seismo-Acoustic Monitoring: A Two-Year Continuous Field Trial in Xinfengjiang - Siyuan Cang; Min Xu; Jiantong Chen; Chao Li; Kan Gao; Xingda Jiang; Zhaoyong Wang; Bin Luo; Zhuo Xiao; Zhen Guo; Ying Chen; Qing Ye; et al. (Journal of Marine Science and Engineering, 2025)
Distributed Acoustic Sensing (DAS) offers numerous advantages, including resistance to electromagnetic interference, long-range dynamic monitoring, dense spatial sensing, and low deployment costs. We initially deployed a water–land DAS system at the Xinfengjiang (XFJ) Reservoir in Guangdong Province, China, to monitor earthquake events. Environmental noise analysis identified three distinct noise zones based on deployment conditions: periodic 18 Hz signals near surface-laid segments, attenuated low-frequency signals (

Integrated analysis of the microbiome, culturable strains, and substrate microenvironment reveals significant shifts in bacterial community of Angelica sinensis from fresh roots to medicinal slices - Xiaopeng Guo; Xuee Li; Rong Guo; Shengli Zhang; Ying Sun; Bin Ji; Yinan Peng; Hushan Shang; Yue Wu (Biologia, 2025)

Long-term exposure to ambient air pollution and the incidence of systemic lupus erythematosus - Lihong Ye; Ding Ye; Yu Qian; Jiayu Li; Bin Liu; Jiacheng Ying; Manli Wang; Hao Lin; Jing Guo; Xiaohui Sun; Zhixing He; Chengping Wen; et al. (Chemosphere, 2025)

Potentially harmful effects of micro-/nanoplastics on humans as well as protective actions of dietary natural products - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Dan-Dan Zhou; Si-Yu Huang; Si-Xia Wu; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan (Trends in Food Science & Technology, 2025)

Toxicity assessment of wastewater using a battery of bioassays in two textile wastewater treatment plants from a large industrial park in Guangxi, Southwest China - Feng-Jiao Peng; Sen Li; Wen-Dan You; Xin-Yu Wang; Xing-Jun Feng; Bin Yang; Guang-Guo Ying (Science of The Total Environment, 2025)

Facile access to spirobifluorene-fused chiral multi-resonance materials with ultra-narrowband blue emission - Hu Cheng; Chen-Hao Guo; Meng Li; Yusong Guo; Zhangyi Fu; Junjie Liu; Yudong Yang; Jingbo Lan; Zhengyang Bin (Science Bulletin, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

Efficient removal of cationic malachite green using co-pyrolyzed corn straw biochar-montmorillonite composites - Xiaodong Yang; Zhiyong Hou; Xuefei Yang; Minghui Li; Yuanxia Guo; Kai Wang; Shuaiqi Luo; Jin Zhao; Pengkai Sun; Qiang Yang; Rui Chen; Yan Yan; et al. (Journal of Environmental Management, 2025)

Ni/ZSM-5@Ni/ZnO catalysts for fluid catalytic cracking gasoline desulfurization-aromatization tandem reactions - Zekun Guan; Guangxun Sun; Chao Feng; Junxi Li; Minmin Wang; Mengdi Guo; Bin Liu; Yuan Pan; Chenguang Liu; Yongming Chai; Yunqi Liu (Fuel, 2025)

Feasibility and comprehensive evaluation of the application of different low-carbon technologies in the iron and steel industry - Qiang Li; Jing song Wang; Xue feng She; Qing guo Xue; Guang Wang; Hai bin Zuo (Fuel, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Airflow and temperature characteristics of diffuse ceiling ventilation with ceiling fan under heating mode: An experimental study - Bin Yang; He Li; Bin Zhou; Zhe Li; Ruiqi Guo; Faming Wang (Energy and Buildings, 2025)

Investigation on the detailed mechanisms of cationic ion exchange resin gasification in supercritical water by ReaxFF reactive molecular dynamics simulation - Le Wang; Ao Li; Zhiyong Peng; Lei Yi; Bin Chen; Hui Jin; Yunan Chen; Liejin Guo (Biomass and Bioenergy, 2025)

Low-temperature oxidative pyrolysis characteristics of tobacco components - Zhongya Guo; Ke Zhang; Huanwei Li; Lili Fu; Qi Zhang; Ze Liu; Le Wang; Xueyi Qiao; Heng Guo; Ran Chen; Bing Wang; Bin Li (Biomass and Bioenergy, 2025)

pH-dependent cadmium binding to hemoglobin: Implications for human excretion - Min Yuan; Qiying Nong; Hua Guo; Yu Li; Haozhong Tian; Jiaao Zhang; Lihong Liu; Bin He; Ligang Hu; Guibin Jiang (Science of The Total Environment, 2025)

Unveiling Sustainable Mineral Resources Extraction, foreign direct Investment, Technology Advancement nexus: Evidence from BRICS countries - Ghulam Muhammad Qamri; Sheng Bin; Li Sanchuan; Guo Hui (Resources Policy, 2025)

Preparation of a Bi12TiO20/U6M1/PES composite membrane for rhodamine B degradation under visible-light irradiation - Jinyang Liu; Qiqi Liao; Chengcai Li; Xueliang Jiang; Jiuming Li; Wangyong Jin; Guojin Liu; Yuhai Guo; Bin Yu; Hailin Zhu (Process Safety and Environmental Protection, 2025)

Investigation of limonene leaching effects on methane adsorption–desorption behaviors in various rank coals: Insights from surface chemical composition and chemical structure analyses - Xiaomin Liang; Tianhe Kang; Jianting Kang; Xiaoyu Zhang; Liankun Zhang; Haoyang Li; Wenqing Zhu; Junqing Guo; Bin Zhang (Fuel, 2025)

Probiotic bacteria as a green solution for mitigating zearalenone toxicity and pollution - Bilal Murtaza; Ren Hongyang; Guo Ling-ling; Lili Wang; Xiaoyu Li; Bowen Jin; Ji-bin Li; Yongping Xu (Food Bioscience, 2025)

Anthocyanin-loaded polylactic acid/quaternized chitosan electrospun nanofiber as an intelligent and active packaging film in blueberry preservation - Mengyang Xu; Donglu Fang; Chong Shi; Shuqiong Xia; Junying Wang; Bin Deng; Benard Muinde Kimatu; Yalong Guo; Lianfei Lyu; Yaqiong Wu; Fuliang Cao; Weilin Li (Food Hydrocolloids, 2025)

Achieving 19.3%-efficiency binary organic solar cells via synergistically dual-phases morphology control - Yushou Zhao; Wenming Li; Xiaofeng Qin; Aiqin Li; Weile Guo; Menglan Lv; Zhicai He; Yong Hua; Dianyong Tang; Bin Zhang (Chemical Engineering Journal, 2025)

Effects of defect concentration on ferromagnetism in Xe-irradiated GaN films - Sen Chen; Qian Li; Yuan Qi; Peiye Yan; Chungang Guo; Wei Cheng; Bin Liao; Xiao Ouyang; Nianhua Peng; Gillian Gehring; Mei Zhou; Minju Ying (Chemical Engineering Journal, 2025)

Editing of the soluble starch synthase gene MeSSIII-1 enhanced the amylose and resistant starch contents in cassava - Xiaohua Lu; Yajie Wang; Xinghou Zhen; Yannian Che; Hui Yu; Yujian Ge; Xiangwen Wang; Ruimei Li; Mengting Geng; Bin Zhou; Jiao Liu; Jianchun Guo; et al. (Carbohydrate Polymers, 2025)

Rice rhizosphere microbiome is more diverse but less variable along environmental gradients compared to bulk soil - Yaping Guo; Yakov Kuzyakov; Na Li; Bin Song; Zihao Liu; Jonathan M. Adams; Lin Yang (Plant and Soil, 2025)

Navβ2 Intracellular Fragments Contribute to Aβ1-42-Induced Cognitive Impairment and Synaptic Deficit Through Transcriptional Suppression of BDNF - Min-Nan Lu; Dan Wang; Chen-Jun Ye; Guo-Ji Yan; Jing-Feng Song; Xin-Ying Shi; Shan-Shan Li; Li-Na Liu; Hui-Xiang Zhang; Xiao-Han Dong; Tao Hu; Xu-Yang Wang; et al. (Molecular Neurobiology, 2025)

Protective effect of SERCA2a-SUMOylation by SUMO-1 on diabetes-induced atherosclerosis and aortic vascular injury - Jinlin Liu; Shifang Xu; Bin Gao; Meng Yuan; Li Zhong; Rui Guo (Molecular and Cellular Biochemistry, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Evaluating the importance of vertical environmental variables for albacore fishing grounds in tropical Atlantic Ocean using machine learning and Shapley additive explanations (SHAP) approach - Tianjiao Zhang; Hu Guo; Liming Song; Hongchun Yuan; Hengshou Sui; Bin Li (Fisheries Oceanography, 2025)
This study aims to find reliable vertical environmental variables for modeling the fishing grounds of albacore ( Thunnus alalunga ) in the tropical waters of the Atlantic Ocean. Logbook data of 13 Chinese longliners operating in the high seas of the Atlantic Ocean from 2016 to 2019 were collected and matched with vertical environmental variables including dissolved oxygen, temperature, and salinity from 0 to 500 m at 50‐m depth intervals. Then four machine learning (ML) models: decision tree (DT), random forest (RF), light gradient boosting (LGB) and categorical boosting (CGB) were constructed and compared with generalized additive models (GAMs) within spatial resolutions of .5° × .5°, 1° × 1°, and 2° × 2° grids to find the significant features. The importance of each variable was ranked and compared based on Shapley additive explanations (SHAP) approach across five ML models at three resolutions. Results showed that (1) the vertical environmental variables—temperature at the depth of 100 m and dissolved oxygen concentration at the depth of 100 and 150 m—were the significant features that contributed most to all the ML models at three spatial resolutions; (2) the models with a spatial resolution of 2° × 2° grid exhibited higher accuracy compared to the models with .5° × .5° and 1° × 1° grids; (3) the RF model had the best prediction performance among all the models tested. Our results suggested that significant vertical environmental variables showed similar importance across different ML models at different resolutions, and these specific variables can be relied upon for accurately predicting the fishing grounds of albacore in the tropical waters of the Atlantic Ocean.

A new S1 subunit truncation vaccine induces effective protection against porcine deltacoronavirus in suckling piglets - Zhuoqi Chen; Li Xiao; Jinzhu Zhou; Wei Wang; Rongli Guo; Jizong Li; Bin Li (Veterinary Microbiology, 2024)

Efficient removal of aqueous ciprofloxacin antibiotic by ZnO/CuO-bentonite composites synthesized via carbon-bed pyrolysis of bentonite and metal co-precipitation - Xiaodong Yang; Xuefei Yang; Zhiyong Hou; Minghui Li; Shuaiqi Luo; Jin Zhao; Kai Wang; Yuanxia Guo; Pengkai Sun; Fang Tan; Yan Yan; Lulu Liu; et al. (Science of The Total Environment, 2024)

Identification and characterization of ATP-binding cassette transporters involved in chlorantraniliprole tolerance of model insect Drosophila melanogaster and agricultural pest Spodoptera frugiperda - Lixiang Wang; Bin Wen; Shaoyi Guo; Yujie Han; Zhongyuan Deng; Qian Ding; Xianchun Li (Pesticide Biochemistry and Physiology, 2024)

Substantial increase in future land exposure to compound droughts and heatwaves in China dominated by climate change - Taizheng Liu; Yuqing Zhang; Bin Guo; Shuming Zhang; Xin Li (Journal of Hydrology, 2024)

Biodegradable and conventional mulches inhibit nitrogen fixation by peanut root nodules – potentially related to microplastics in the soil - Wei Guo; Jizhi Li; Zhengfeng Wu; Guangyu Chi; Caiyan Lu; Jian Ma; Yanyu Hu; Bin Zhu; Miaoyin Yang; Xin Chen; Huiying Liu (Journal of Hazardous Materials, 2024)

Corrigendum to “Innovative approach for assessing nitrogen loss risk to surface waters from crop production in a watershed scale through nitrogen surplus index method” [J. Clean. Product. 475 (2024) 143725] - Ziwei Yang; Cong Zhu; Haixuan Zhao; Gaofei Yin; Yueying Wei; Wenqi Ma; Huiqing Jiao; Jiafa Luo; Bin Xi; Hongda Wen; Shufang Guo; Wenchao Li; et al. (Journal of Cleaner Production, 2024)

Electrostatic self-assembly of hydrotalcite-based g-C3N4 composites for adsorption and photocatalytic degradation of aqueous norfloxacin - Xiaodong Yang; Minghui Li; Zhiyong Hou; Xuefei Yang; Yuanxia Guo; Shuaiqi Luo; Jin Zhao; Kai Wang; Pengkai Sun; Qiang Yang; Rui Chen; Shuo Yang; et al. (Journal of Environmental Chemical Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Dietary oxygenated water mitigates type 2 diabetes mellitus by modulating gut microbiota and enhancing glucose metabolism in skeletal muscle - Yue Xiao; Dongmei Yang; Xiaoqing Chen; Li Xiong; Huan Guo; Sheng Ma; Bin Li; Hong Gao; Yina Huang (Food Bioscience, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Constructing bone organoids based on endochondral ossification model via endogenous enzyme-induced mineralization - Li Dong; Weiguo Chen; Xi Luo; Chengyuan Liu; Jingxi Xu; Dachuan Liu; Zhao Liu; Huan Wang; Jiaxu Shi; Weicheng Chen; Moyan Li; Jiaojiao Yang; et al. (Chemical Engineering Journal, 2024)

Polyvinyl alcohol/sodium alginate-based conductive hydrogels with in situ formed bimetallic zeolitic imidazolate frameworks towards soft electronics - Jiongru Li; Huige Wei; Shuaichuan Cui; Hua Hou; Yifan Zhang; Yingying Zhang; Ben Bin Xu; Liqiang Chu; Zeinhom M. El-Bahy; Saad Melhi; Rahma Sellami; Zhanhu Guo (Carbohydrate Polymers, 2024)

Two new furanone derivatives from the endophytic fungus Byssochlamys sp. and their cytotoxic activities - Jie Wang; Wen-Bin Gao; Fan-Wei Liu; Qi Liu; Bo Song; Jin Ye; Ying Chen; Cai-Lin Zhao; Wei Dong; Li-Na Guo; Bo Song (Natural Product Research, 2024)

Disintegration of Cav-1/β-catenin complex attenuates neuronal death after ischemia–reperfusion injury by promoting β-catenin nuclear translocation - Peng Guo; Wan Wang; Zhiyan Liang; Yihang Li; Xiangling Ou; Ming Li; Bin Wang; Xuewen Wei; Linyan Huang; Suhua Qi (Molecular Biology Reports, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Biochemical and transcriptomic analyses reveal the toxicological response and potential mechanism of butyl benzyl phthalate in zebrafish gills - Qian Wang; Bin Guo; Huiyan Yang; Wensa Zhou; Huijuan Lv; Xiangfeng Yao; Xianxu Li; Zhuran Hu; Jun Wang (Science of The Total Environment, 2024)

Shallow groundwater table fluctuations weaken nitrogen accumulation in the thin layer vadose zone of cropland around plateau lakes, Southwest China - Qingfei Chen; Anqiang Chen; Jinheng Min; Lin Li; Wanli Hu; Chi Wang; Bin Fu; Shufang Guo; Dan Zhang (Science of The Total Environment, 2024)

Long-term agricultural cultivation decreases microbial nutrient limitation in coastal saline soils - Guanjun Li; Zhi Ma; Liang Wei; Cuiyan Wu; Hao Chen; Bin Guo; Tida Ge; Jianming Wang; Jingwen Li (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Different preferences for inorganic carbon influence CO2 flux under Cyanobacteria or Chlorophyta dominance days - Kai-Kai Deng; Yi-Xuan Li; Peng Yan; Yuan-Chen Huo; Hao Yang; Bin Chen; Qiang He; Gui-Jiao Lin; Jin-Song Guo (Journal of Environmental Management, 2024)

Designing persimmon-liked FeOOH-(CrCo)Ox on the plasma-treated cobalt foam for a highly efficient oxygen evolution in an alkaline-seawater electrolyte - Ruixian Liu; Guangliang Chen; Yingchun Guo; Tongtong Li; Jinfeng Qiu; Bin He; Peisong Tang (Chemical Engineering Journal, 2024)

In situ regulating the interfacial work function of Ag doped Ni(OH)2 via trace of Fe2+ for efficient water splitting - Min Li; Runlin Huang; Chao Feng; Longfei Sun; Yanan Zhou; Haijun Liu; Chi Jiang; Yingli Wang; Jie Dou; Qiyao Guo; Yuanyuan Zhao; Jialong Duan; et al. (Chemical Engineering Journal, 2024)

PbHfO3-based antiferroelectric materials: Fundamentals, properties, and advanced applications - Dong-Liang Li; Xin-Gui Tang; Shui-Feng Li; Xiao-Bin Guo; Dan Zhang; Qi-Jun Sun; Wen-Hua Li; Zhen-Hua Tang; Yan-Ping Jiang; Qiu-Xiang Liu (Chemical Engineering Journal, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

Anti-tumor and anti-metastasis of water-soluble sulfated β-glucan derivatives from Saccharomyces cerevisiae - Jia Li; Mengmeng Zheng; Zhe Wang; Yang Liu; Qingfeng Niu; Han Zhou; Depeng Wang; Jike Song; Hongsheng Bi; Bin Guo; Guangli Yu; Chao Cai (Carbohydrate Polymers, 2024)

Hydrodeoxygenation of guaiacol over modified coconut carbon supported Ni nanoparticles catalysts under alkaline condition - Yacong Deng; Yanlin Xu; Zhuoyi Liu; Wenhong Wang; Bin Liu; Hailing Guo; Yanpeng Li; Bin Dong; Yichuan Li; Yuan Pan; Yongming Chai; Chenguang Liu (Biomass and Bioenergy, 2024)

ACE2 Rescues Sepsis-Associated Encephalopathy by Reducing Inflammation, Oxidative Stress, and Neuronal Apoptosis via the Nrf2/Sestrin2 Signaling Pathway - Ya Li; Tian-Tian Wan; Jia-Xin Li; Xue Xiao; Lei Liu; Hui-Hua Li; Shu-Bin Guo (Molecular Neurobiology, 2024)

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Nocturnal peak methane flux diel patterns in rice paddy fields - Hong Li; Changhui Peng; Manuel Helbig; Min Zhao; Haiqiang Guo; Bin Zhao (Agricultural and Forest Meteorology, 2024)

Comparative transcriptome reveals EphA2 and c-Fos as key factors driving enhanced replication in high-passage porcine deltacoronavirus strain - Shiyu Liu; Qi Peng; Baochao Fan; Gege Zhang; Wenlong He; Chuanhong Wang; Jingyuan Xie; Xu Song; Boshui Yuan; Rongli Guo; Jizong Li; Bin Li (Veterinary Microbiology, 2024)

A thorough investigation into the adsorption behavior of sophorolipid-modified fly ash towards compound pollution of lead and tetracycline - Pengyu Ren; Lu Wang; Tianhai Ma; Yimo Zhao; Bin Guo; Chi Luo; Shaohua Li; Puhui Ji (Science of The Total Environment, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Retraction notice to “N-rich and O-poor doped carbon prepared via facile ammonium nitrate assisted hydrothermal carbonization for robust supercapacitors” [J Clean. Prod. (2022) 133903] - Xue-Qin Ma; Bo Zhang; Zhi-Xiang Xu; Yi Tan; Bin Li; Yong-Cai Zhang; Guo-Song Ni; Wei-You Zhou; Rafael Luque; Hui-Yan Zhang (Journal of Cleaner Production, 2024)

Innovative approach for assessing nitrogen loss risk to surface waters from crop production in a watershed scale through nitrogen surplus index method - Ziwei Yang; Cong Zhu; Haixuan Zhao; Gaofei Yin; Yueying Wei; Wenqi Ma; Huiqing Jiao; Jia Luo; Bin Xi; Hongda Wen; Shufang Guo; Wenchao Li; et al. (Journal of Cleaner Production, 2024)

Riboflavin-induced microbial succession for enhanced tellurite reduction in wastewater treatment - Jiawei Jing; Bin Yu; Tingting Wang; Xinyu Guo; Pengfei Huang; Jiayue Che; Chuan Li; Yuanyuan Qu (Journal of Environmental Chemical Engineering, 2024)

Novel two-dimensional Ti3C2Tx MXene-supported Ni-M (M = Pd, Pt, Ru): A remarkable catalyst for efficient HDO of guaiacol under hydrothermal conditions: Performance, mechanism and kinetic studies - Junqian Wang; Yi Wang; Yuqi Wang; Xinyi Li; Caichao Wu; Tianyu Zhang; Bin Tian; Lili Qian; Yang Guo; Le Wu; Lan Zheng; Yanan Li; et al. (Fuel, 2024)

Introducing the sulfone group as a cellulose-binding site to improve the hydrolysis performance of the solid acid - Bin Wu; Shuguang Shen; Xingting Guo; Ruxue Sun; Yongmei Liu; Jing Li; Jiemin Guo; Shuai Wang; Xiaoting Hu; Yutong Guo (Fuel, 2024)

Lightweight CNN combined with knowledge distillation for the accurate determination of black tea fermentation degree - Zezhong Ding; Chongshan Yang; Bin Hu; Mengqi Guo; Jinggang Li; Mengjie Wang; Zhengrui Tian; Zhiwei Chen; Chunwang Dong (Food Research International, 2024)

Regulating fat globule structure of infant formula based on MFGM to promote lipid uptake by improving lipolysis - Yue Sun; Bin Zhu; Pingyao Cong; Xiaodong Li; Lu Liu; Chanchan Guo; Kuangyu Zhao; Jiaxin Qiu; Haowen Ji; Xiaojun Zhu; Kouadio Jean Eric-Parfait Kouame (Food Hydrocolloids, 2024)

Construction of an ideotype root system architecture of subsurface flow constructed wetland macrophytes by vertical spatial stress: strengthening of rhizosphere effects and determination of appropriate substrate depth - Jiewen Zheng; Dun Guo; Jingying Zhang; Tongyao Zhang; Lei Yang; Bin Li; Jun Lan; Yongxiang Ren (Environmental Research, 2024)

Topography-based and vectorized algorithm for extracting physical quantities in 3D-SPH form and its application in debris-flow entrainment modeling - Bin Su; Yange Li; Zheng Han; Yangfan Ma; Weidong Wang; Bo Ruan; Wei Guo; Wendu Xie; Shaofeng Tan (Engineering Geology, 2024)

Development of a novel Co-doped carbon fiber from textile waste as catalyst for the highly efficient degradation of organic pollutants: The key role of C–O–Co bond - Bin Fang; Linyu Li; Junmei Guo; Yuhong Qin; Yuexing Wei; Jiansheng Zhang; Chong He; Yichao Chen (Chemical Engineering Journal, 2024)

Unraveling the delithiation mechanism of air-stabilized fluorinated lithium iron oxide pre-lithiation material - Naifeng Wen; Jie Li; Bin Zhu; Juanlang Guo; Zhian Zhang (Chemical Engineering Journal, 2024)

Interferon Regulatory Factor 5 Gene Polymorphisms and mRNA Expression Levels Are Associated with Neuromyelitis Optica Spectrum Disorder - Gaoning Wang; Liu Jing; Ying Wang; Arshad Mehmood; Huining Zhang; Ruoyi Guo; Lu Zhang; Bin Li (Molecular Neurobiology, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Effects of parental nutritional programming on the hatching parameters, metabolome, glucose metabolism-related gene expressions, and global DNA methylation in larvae of yellow catfish Tachysurus fulvidraco - Wen-Bin Xu; Li-Guo Yang; Qing-Ji Zhang; Yu-Shi Chen (Aquaculture International, 2024)

Chemical constituents from the roots of Dolomiaea souliei - Zhe Wang; Li-Dan Zhang; Gang-Gang Zhou; Qi-Zheng Zhong; Yun-Bin Jiang; Guo-Wei Wang; Zhi-Hua Liao; Fan-Cheng Meng; Min Chen (Natural Product Research, 2024)

High temporal and spatial estimation of grass yield by applying an improved Carnegie-Ames-Stanford approach (CASA)-NPP transformation method: A case study of Zhenglan Banner, Inner Mongolia, China - Bin Sun; Pengyao Qin; Wei Yue; Ye Guo; Zhihai Gao; Yan Wang; Yifu Li; Ziyu Yan (Computers and Electronics in Agriculture, 2024)

Synergistic photocatalysis of oxygen-enriched vacancy BiOBr based on rice husk biochar: Efficient seawater purification achieved by carrier directional migration - Qi Tang; Jinyuan Liu; Huimin Han; Shihao Jia; Yiru Guo; Gaopeng Liu; Bin Wang; Huaming Li; Chongtai Wang; Hui Xu; Yingjie Hua (Process Safety and Environmental Protection, 2024)

Genome-wide analysis of TOPLESS/TOPLESS-RELATED co-repressors and functional characterization of BnaA9.TPL regulating the embryogenesis and leaf morphology in rapeseed - Xiaolong Zhang; Yingying Chen; Hongyu Chen; Chaocheng Guo; Xue Su; Tingting Mu; Bin Feng; Yu Wang; Zhixin Liu; Biaoming Zhang; Yan Li; Haitao Zhang; et al. (Plant Science, 2024)

RNA interference-mediated silencing of ctl13 inhibits innate immunity and development in stored pest Tribolium castaneum - Mingxiao Ning; Qing Li; Lixia Fan; Changying Guo; Bingchun Zhang; Jia Li; Xianfeng Ren; Bin Li; Jingxuan Zhu (Pesticide Biochemistry and Physiology, 2024)

Recent advances of structure-performance relationship and improvement methods of catalysts for photochemical and electrochemical reduction of nitrogen to green ammonia - Junyan Chen; Bin Guan; Zhongqi Zhuang; Chunzheng Zheng; Jiefei Zhou; Tianxu Su; Yujun Chen; Chenyu Zhu; Xuehan Hu; Sikai Zhao; Jiangfeng Guo; Hongtao Dang; et al. (Fuel, 2024)

Natural pyrethrins induce cytotoxicity in SH-SY5Y cells and neurotoxicity in zebrafish embryos (Danio rerio) - Wei-Guo Wang; Shou-Lin Li; Bin Liu; Ning Tang; Cheng Zhang; Xu-Feng Jiang; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Environmental Research, 2024)

Efficient electrocatalytic OOH production on P–N–CuO for selective cleavage of lignin C–C bonds in the photoelectric collaborative system - Linglong Shi; Huifang Ma; Bin Shan; Da Li; Shuangzhen Guo; Yu Liu; Jianjie Wang; Weifang Dong; Mengqi Li; Shuting Gu; Weiyu Xia (Chemical Engineering Journal, 2024)

Inspection for the desorption effect and mechanism of petroleum from contaminated soil in surfactant solution - Meixia Gu; Xiaoshuang Yin; Xiaoning Feng; Nan Shi; Wei Zhu; Shuhai Guo; Min Li; Bo Wu; Gang Li; Xingshun Cong; Bin Lou; Fushan Wen; et al. (Journal of Soils and Sediments, 2024)

Effect of using reclaimed water via furrow and subsurface drip systems under alternate partial root-zone irrigation mechanism on crops growth and soil properties - Mahmoud S. Hashem; Wei Guo; Xue-Bin Qi; Ping Li; Ying-jun She; Jiaxin Cui; Tong Li (Irrigation Science, 2024)
The growing population in the face of water scarcity inevitably necessitates the quest for alternative sources of irrigation water, which integrates them with irrigation strategies for improved agricultural productivity to meet the Sustainable Development Goals. A three-year field experiment was conducted in 2017, 2018, and 2019 to investigate the effect of water quality (reclaimed water (RW) and clean water (CW)), irrigation techniques (subsurface drip irrigation (SDI) and furrow irrigation (FUI)), irrigation methods (full irrigation (FI) and alternate partial root-zone irrigation (APRI) (70% ETc)), and their interactions on the fresh fruit yield (FY), irrigation water use efficiency (IWUE), and nitrogen use efficiency (NUE) of tomatoes. Further, electrical conductivity (EC), pH, and organic matter (OM) of soil were evaluated. The experiments were undertaken over three growing spring seasons in a greenhouse at the Chinese Academy of Agricultural Sciences in Henan Province, China. Throughout the three years of this study, the yield, the IWUE, and the NUE values of all treatments under RW were higher than those corresponding values under CW. The trend was the same under SDI as it was under FUI. Statistical analyses revealed that there was no significant effect ( P > 0.05) of water quality, irrigation technique, and irrigation methods on the soil EC, pH, and OM over the three years. In addition, the interaction between the different experimental factors over the three years of the study was not significant. In conclusion, the application of RW under SDI can result in saving CW and increasing productivity without any negative effect on the investigated soil properties. Furthermore, when RW-SDI is used in conjunction with APRI, it can result in increasing IWUE.

Genetic characterization and phylogenetic analysis of the S genes of porcine epidemic diarrhea virus isolates from China from 2020 to 2023 - Yi Wang; Jiali Qian; Yupeng Li; Dandan Wang; Xu Song; Shuo Tian; Jinzhu Zhou; Wei Wang; Rongli Guo; Jizong Li; Xuehan Zhang; Xianwei Wang; et al. (Archives of Virology, 2024)

A new method for predicting precipitation δ 18 O distribution based on deep learning and spatio-temporal clustering - Yang Li; Siyuan Huo; Bin Ma; Bingbing Pei; Qiankun Tan; Qing Guo; Deng Wang; Longbiao Yu (Hydrological Sciences Journal, 2024)

Nonstructural protein 14 of PDCoV promotes complement C3 expression via the activation of p38-MAPK-C/EBP pathway - Zhuoqi Chen; Chunyan Zhong; Liyuan Fan; Hongqi Shang; Li Xiao; Wei Wang; Rongli Guo; Baochao Fan; Jizong Li; Bin Li (Veterinary Microbiology, 2024)

Removing ammonia from exhaust gas through selective catalytic oxidation reaction: Research status and future perspectives - Sikai Zhao; Bin Guan; Zhongqi Zhuang; Junyan Chen; Chenyu Zhu; Xuehan Hu; Zeren Ma; Jiangfeng Guo; Hongtao Dang; Kaiyou Shu; Yuheng Yuan; Kuangyi Shi; et al. (Journal of Cleaner Production, 2024)

Bipolar membrane electrodialysis integrated with in-situ CO2 absorption for simulated seawater concentrate utilization, carbon storage and production of sodium carbonate - Jingtao Bi; Tianyi Chen; Yue Xie; Ruochen Shen; Bin Li; Mengmeng Sun; Xiaofu Guo; Yingying Zhao (Journal of Environmental Sciences, 2024)

CCL2 Potentiates Inflammation Pain and Related Anxiety-Like Behavior Through NMDA Signaling in Anterior Cingulate Cortex - Huan Guo; Wen-chao Hu; Hang Xian; Yun-xin Shi; Yuan-ying Liu; Sui-bin Ma; Kun-qing Pan; Sheng-xi Wu; Li-yan Xu; Ceng Luo; Rou-gang Xie (Molecular Neurobiology, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

Laccaria guizhouensis sp. nov. (Agaricales, Basidiomycota) from Southwest China - San-Fang Zhang; Yang Gui; Guo-Sheng Zhu; Nian-Jie Shang; Biao Li; Tong-Jing Yang; Guang-Lu Gong; Wan-Bin Huang; Zhan-Bo Liu (New Zealand Journal of Botany, 2024)

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Zinc-associated phospholipid metabolic alterations and their impacts on ALT levels in workers - Yuanyuan Wang; Yiling Li; Qiying Nong; Guohuan Zhang; Nian Liu; Hua Guo; Qinghao He; Lihong Liu; Guangbo Qu; Bin He; Ligang Hu; Guibin Jiang (Science of The Total Environment, 2024)

Modulation of rhizosphere microbial community and metabolites by bio-functionalized nanoscale silicon oxide alleviates cadmium-induced phytotoxicity in bayberry plants - Temoor Ahmed; Linfei Shou; Junning Guo; Muhammad Noman; Yetong Qi; Yanlai Yao; Hafiza Ayesha Masood; Muhammad Rizwan; Md. Arshad Ali; Hayssam M. Ali; Bin Li; Xingjiang Qi (Science of The Total Environment, 2024)

Toxic mechanisms of the antiviral drug arbidol on microalgae in algal bloom water at transcriptomic level - Ziwei Guo; Huan He; Kunqian Liu; Zihui Li; Yanting Xi; Zhicheng Liao; Guohua Dao; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2024)

Material flow analysis of heavy metals in large-scale cattle farms and ecological risk assessment of cattle manure application to fields - Bin Guo; Pengyu Ren; Lu Wang; Shaohua Li; Chi Luo; Yimo Zhao; Hanghang Zhao; Jian Sun; Puhui Ji (Journal of Environmental Management, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Effective immobilization and biosafety assessment of antimony in soil with zeolite-supported nanoscale zero-valent iron - Ying Zhao; Xinyi Zhang; Haotian Xue; Bin Gong; Qingxu Li; Wenshan Guo; Xiaoguang Meng (Environmental Pollution, 2024)

Combining CENTURY model and vulnerability assessment index to estimate aboveground biomass and ecological vulnerability of grassland: An analysis in Northwest Sichuan Plateau - Huayun He; Chao Chen; Qiuyue Li; Bin Guo; Qi Hu; Lina Zhang; Yanmei Pang (Ecological Modelling, 2024)

Light grazing reduces the abundance of carbon cycling functional genes by decreasing oligotrophs microbes in desert steppe - Tianqi Zhao; Jianying Guo; Rongzhen Suo; Yuxi Jin; JujieYang; Shaoyu Li; Jiahua Zheng; Naijing Lu; Guodong Han; Mengli Zhao; Bin Zhang (Applied Soil Ecology, 2024)

Phosphorylation of G3BP1 is involved in the regulation of PDCoV-induced inflammatory response - Baotai Zhang; Siyuan Li; Zhuoqi Chen; Liyuan Fan; Wei Wang; Rongli Guo; Baochao Fan; Jizong Li; Bin Li (Veterinary Microbiology, 2024)

Non-target and target screening and risk assessment of per- and polyfluoroalkyl substances in textile wastewater and receiving river - Sheng Xiao; Ting Liu; Li-Xin Hu; Bin Yang; Guang-Guo Ying (Science of The Total Environment, 2024)

Effects of different precipitation on the runoff-lake library carbon cycle process in the Three Gorges reservoir - Yixuan Li; Kaikai Deng; Zhe Li; Guijiao Lin; Bin Chen; Fang Fang; Jinsong Guo (Journal of Cleaner Production, 2024)

Soot particles formed by n-heptane and n-heptane/oxymethylene ether-3 in an inverse diffusion flame: A comparative analysis of chemical features - Ye Liu; Ran Zhang; Jun Wang; Yajun Wang; Gang Lv; He Yang; Haibo Chen; Tiezhu Li; Bin Hao; Junhua Guo (Fuel, 2024)

Encapsulation of apigenin into β-cyclodextrin metal-organic frameworks with high embedment efficiency and stability - Yaqi Liu; Chao Yuan; Bo Cui; Meng Zhao; Bin Yu; Li Guo; Pengfei Liu; Yishan Fang (Food Chemistry, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

Hydrophobic sisal cellulose paper-based TENG for collecting rain energy and raindrop-based sensor - Yating Pan; Ming Li; Yuxiang Lu; Manli Lu; Bin Guo; Xianming Liu; Kaiyou Zhang; Yu Wang; Liang Feng; Aimiao Qin (Chemical Engineering Journal, 2024)

Bio-formulated chitosan nanoparticles enhance disease resistance against rice blast by physiomorphic, transcriptional, and microbiome modulation of rice (Oryza sativa L.) - Rahila Hafeez; Junning Guo; Temoor Ahmed; Hubiao Jiang; Mubashar Raza; Muhammad Shahid; Ezzeldin Ibrahim; Yanli Wang; Jiaoyu Wang; Chengqi Yan; Qianli An; Jason C. White; et al. (Carbohydrate Polymers, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

Spatio-temporal evolution and topographic gradient effect of land use and ecosystem service value in the Lhasa River Basin - Jianwei Zhou; Bin Feng; Hua Wu; Tong Xu; Linna Chen; Xinyong Zhao; Qiyun Guo; Jiatong Li; Chenguang Zhang; Kangcheng Zhu; Yuzhong Kong (Journal of Mountain Science, 2024)

Preparation of modified halloysite nanotubes@Ag3PO4/polyacrylonitrile electrospinning membranes for highly efficient air filtration and disinfection - Jiayu Ma; Xu Jin; Yeyue Lu; Mengjuan Yang; Ximeng Zhao; Mengting Guo; Huijie Zhang; Xiuyan Li; Bin Wang (Applied Clay Science, 2024)

Integrative transcriptomic and metabolomic analyses reveals the toxicity and mechanistic insights of bioformulated chitosan nanoparticles against Magnaporthe oryzae - Rahila Hafeez; Junning Guo; Temoor Ahmed; Ezzeldin Ibrahim; Md. Arshad Ali; Muhammad Rizwan; Munazza Ijaz; Qianli An; Yanli Wang; Jiaoyu Wang; Bin Li (Chemosphere, 2024)

Research on seedling sowing method based on high voltage electrostatic characteristics - Sheng Sun; Bin Hu; Jinhu Ma; Xin Luo; Mengyu Guo; Junwei Li; Luochuan Xu; Xiaoyun Xu (Computers and Electronics in Agriculture, 2024)

Triaxial mechanical behaviours and life cycle assessment of sustainable multi-recycled aggregate concrete - Bin Lei; Linjie Yu; Yipu Guo; Hongjie Xue; Xiaonan Wang; Yan Zhang; Wenkui Dong; Frank Dehn; Wengui Li (Science of The Total Environment, 2024)

Cell-excreted proteins mediate the interactions of differently sized silica nanoparticles during cellular uptake - Bin Huang; Jia-Ming Li; Xiao-Mei Zang; Mei Wang; Wei Pan; Ke-Da Zhang; Huan He; Qiao-Guo Tan; Ai-Jun Miao (Journal of Hazardous Materials, 2024)

Recombinant microgels utilized to formulate green Pickering emulsions - Han Liu; Li Guo; Fuying Wang; Hongxun Tao; Bin Yu; Haibo Zhao; Jianpeng Li; Minwei Xu; Haiteng Tao; Bo Cui; Yuxiao Wang (Food Hydrocolloids, 2024)

Regulation of photoassimilate transportation and nitrogen uptake to decrease greenhouse gas emissions in ratooning rice with higher economic return by optimized nitrogen supplies - Jingnan Zou; Hailong Xu; Chaojie Lan; Bin Qin; Jinying Li; Witness Joseph Nyimbo; Hongmei Lin; Ziqin Pang; Nyumah Fallah; Chunlin Guo; Changxun Fang; Zhixing Zhang; et al. (Field Crops Research, 2024)

Enhancing the carbon content of coal gangue for composting through sludge amendment: A feasibility study - Chi Luo; Shaohua Li; Pengyu Ren; Fan Yan; Lu Wang; Bin Guo; Yimo Zhao; Yue Yang; Jian Sun; Pengcheng Gao; Puhui Ji (Environmental Pollution, 2024)

Experimental and numerical investigation on energy-saving performance of radiative cooling coating for metal container office - Qingdong Xuan; Jiancong Lao; Bin Zhao; Guiqiang Li; Gang Pei; Jianlei Niu; Jian-Guo Dai (Energy and Buildings, 2024)

Aerobic granulation in a continuous-flow simultaneous nitrification, endogenous denitrification, and phosphorus removal system fed with low-strength wastewater: Granulation mechanism and microbial succession - Rongfan Chen; Wenbin Guo; Lu Li; Hongyu Wang; Bin Wang; Xiaoling Hu; Bin Ji; Dao Zhou; Wanlin Lyu (Chemical Engineering Journal, 2024)

Regulation of CuFeZn catalysts by K3PO4 and its effect on CO2 hydrogenation to C2+ alcohols - Sensen Zhou; Yueli Wen; Bin Wang; Maohong Fan; Lu Ren; Zheng Cui; Wei Huang; Jing Li; Jianping Guo (Chemical Engineering Journal, 2024)

Strong Lewis acid-induced self-healing of loose FeOOH for alkaline oxygen evolution - Ning Yu; Jing Yi Lv; Zi-Chuan Guo; Xin-Jie Tian; Yu-Sheng Zhang; Wen-Jing Li; Yu-Lu Zhou; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Energy-efficient operation of portable air cleaners based on real-time prediction of non-uniform concentrations of indoor air pollutants in open offices - Difei Chen; Mingqi Liu; Weichen Guo; Yiqun Li; Bin Xu; Wei Ye (Building and Environment, 2024)

In vitro suppression of porcine epidemic diarrhea virus by Panax notoginseng saponins: assessing antiviral potential - Yiyi Hu; Yunchuan Li; Haodan Zhu; Dandan Wang; Junming Zhou; Yanxiu Ni; Rongli Guo; Baochao Fan; Bin Li (Archives of Virology, 2024)

Relationships between high-concentration toxic metals in sediment and evolution of microbial community structure and carbon–nitrogen metabolism functions under long-term stress perspective - Tao Song; Weiguo Tu; Shu Chen; Min Fan; Liang Jia; Bin Wang; Yuankun Yang; Sen Li; Xuemei Luo; Mingyue Su; Jingjing Guo (Environmental Science and Pollution Research, 2024)

Large-scale quantum emulating simulations of biomolecules: A pilot exploration of parallel quantum computing - Honghui Shang; Fei Wang; Yi Fan; Huan Ma; Qi Liu; Chu Guo; Pengyu Zhou; Qi Chen; Qian Xiao; Tianyu Zheng; Bin Li; Fen Zuo; et al. (Science Bulletin, 2024)

Gamma-ray irradiation as an effective method for mitigating antibiotic resistant bacteria and antibiotic resistance genes in aquatic environments - Ming-Qi Zhang; Xiao-Yong Zhang; Han-Chao Zhang; Hai-Bin Qiu; Zheng-Hao Li; Dong-Hua Xie; Li Yuan; Guo-Ping Sheng (Journal of Hazardous Materials, 2024)

Renewable synthetic fuels: Research progress and development trends - Yuan Li; Bin Guan; Jiangfeng Guo; Yujun Chen; Zeren Ma; Zhongqi Zhuang; Chenyu Zhu; Hongtao Dang; Lei Chen; Kaiyou Shu; Kuangyi Shi; Zelong Guo; et al. (Journal of Cleaner Production, 2024)

Impact of government subsidies and carbon inclusion mechanism on carbon emission reduction and consumption willingness in low-carbon supply chain - Fang Li; Yuhang Guo; Bin Liu (Journal of Cleaner Production, 2024)

High stocking rates effects in continuous season long grazing reduces the contribution of microbial necromass to soil organic carbon in a semi-arid grassland in Inner Mongolia - Tianqi Zhao; Rongzhen Suo; Aklilu W. Alemu; Shaoyu Li; Jiahua Zheng; Naijing Lu; Feng Zhang; Jirong Qiao; Jianying Guo; Alan D. Iwaasa; Guodong Han; Mengli Zhao; et al. (Journal of Environmental Management, 2024)

The effects of sowing date on maize: Phenology, morphology, and yield formation in a hot subtropical monsoon region - Zhong-Yang Cao; Zhi-Hui Chen; Bin Tang; Qiang Zeng; Huan-Le Guo; Wan-Hua Huang; Yu Luo; Si Shen; Shun-Li Zhou (Field Crops Research, 2024)

Review of nitrous oxide direct catalytic decomposition and selective catalytic reduction catalysts - Zhongqi Zhuang; Bin Guan; Junyan Chen; Chunzheng Zheng; Jiefei Zhou; Tianxu Su; Yujun Chen; Chenyu Zhu; Xuehan Hu; Sikai Zhao; Jiangfeng Guo; Hongtao Dang; et al. (Chemical Engineering Journal, 2024)

Effects of grass strips distribution on soil erosion and its optimal configuration on hillslopes - Xia Zhang; Peng Li; Zhan Bin Li; Guo Qiang Yu (CATENA, 2024)

Key function of Kouleothrix in stable formation of filamentous aerobic granular sludge at low superficial gas velocity with polymeric substrates - Xi Chen; Yanzhe Gong; Zhihua Li; Yingming Guo; Hongjiang Zhang; Bin Hu; Wenhao Yang; Yinhuan Cao; Ruihua Mu (Bioresource Technology, 2024)

Machine learning-based prediction of outdoor thermal comfort: Combining Bayesian optimization and the SHAP model - Ruiqi Guo; Bin Yang; Yuyao Guo; He Li; Zhe Li; Bin Zhou; Bo Hong; Faming Wang (Building and Environment, 2024)

Highly efficient copper ions removal by sodium alginate/sodium humate@Polyacrylamide: adsorption behavior and removal mechanism - Hongyu Wang; Mengyuan Huang; Lu Li; Bin Wang; Can Jiang; Xiaoling Hu; Yi Xie; Rongfan Chen; Wenbin Guo; Henglin Xiao; Mingfei Wang; Dao Zhou (Water, Air, & Soil Pollution, 2024)

The Chaperone Protein Cct5 is Essential for Hematopoietic Stem Cell Maintenance - Linxi Li; Jie Huang; Suping Zhang; Chunxu Yao; Yandan Chen; Haitao Wang; Bin Guo (Stem Cell Reviews and Reports, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Death-associated protein 3 in cell death and beyond - Ting Cao; Xuling Luo; Binjiao Zheng; Yao Deng; Yu Zhang; Yuyan Li; Wenwen Xi; Meng Guo; Xuefeng Yang; Zhiyue Li; Bin Lu (Genome Instability & Disease, 2024)

Sources of elevated organic acids in the mountainous background atmosphere of southern China - Yan Guo; Daocheng Gong; Hao Wang; Qinqin Li; Gengchen Wu; Yu Wang; Huang Cai; Bin Yuan; Boguang Wang; Shaw Chen Liu (Science of The Total Environment, 2024)

Widespread inversions shape the genetic and phenotypic diversity in rice - Wenchuang He; Huiying He; Qiaoling Yuan; Hai Zhang; Xiaoxia Li; Tianyi Wang; Yingxue Yang; Longbo Yang; Yuting Yang; Xiangpei Liu; Hua Wei; Hong Zhang; et al. (Science Bulletin, 2024)

The environmental risks of antiviral drug arbidol in eutrophic lake: Interactions with Microcystis aeruginosa - Ziwei Guo; Huan He; Gui Yang; Kunqian Liu; Yanting Xi; Zihui Li; Yu Luo; Zhicheng Liao; Guohua Dao; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2024)

Combating land degradation through human efforts: Ongoing challenges for sustainable development of global drylands - Ziyu Yan; Ye Guo; Bin Sun; Zhihai Gao; Pengyao Qin; Yifu Li; Wei Yue; Hanwen Cui (Journal of Environmental Management, 2024)

Effects of starch–fatty acid complexes with different fatty acid chain lengths and degrees of saturation on the rheological and 3D printing properties of corn starch - Yue Cheng; Wei Gao; Xuemin Kang; Jianfei Wang; Bin Yu; Li Guo; Meng Zhao; Chao Yuan; Bo Cui (Food Chemistry, 2024)

Highly-branched cyclic dextrin for improvement in mechanical properties and freeze-thaw stability of κ-carrageenan gels - Wentao Ma; Chao Yuan; Bo Cui; Tian Gao; Li Guo; Bin Yu; Meng Zhao; Feixue Zou (Food Hydrocolloids, 2024)

Catalytic degradation of antibiotic sludge to produce formic acid by acidified red mud - Ruihao Yang; Zixuan Wang; Junjiang Guo; Jiamin Qi; Shuai Liu; Hengxi Zhu; Bin Li; Zewei Liu (Environmental Research, 2024)

Metagenomic and biochemical analyses reveal the potential of silicon to alleviate arsenic toxicity in rice (Oryza sativa L.) - Temoor Ahmed; Junning Guo; Muhammad Noman; Luqiong Lv; Natasha Manzoor; Xingjiang Qi; Bin Li (Environmental Pollution, 2024)

Synergistic effect between CoSx and MoS2 at the micrometer scale: Considerable promotion of the hydrodesulfurization of DBT - Fengyu Tian; Wenhong Wang; Bin Liu; Yuan Pan; Bin Dong; Yichuan Li; Yanpeng Li; Hailing Guo; Yongming Chai; Chenguang Liu (Chemical Engineering Journal, 2024)

Engineering an injectable gellan gum-based hydrogel with osteogenesis and angiogenesis for bone regeneration - Hongbin Liu; Kaihu Li; Bin Guo; Yuhao Yuan; Zhe Ruan; Haitao Long; Jianxi Zhu; Yong Zhu; Can Chen (Tissue and Cell, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Novel modified semi-carbonized fiber prepared using discarded clothes for derisking Cu(II) and Pb(II) contaminated water - Hong-yan Deng; Yin-fei Wang; Meng-ting Guo; Wen-bin Li; Min Li; Chu-tong Yu (Journal of Environmental Management, 2024)

Simultaneous removal of Methylene blue and Cadmium from aqueous solution by a novel sulfonated material: Characterization, mechanism and application - Lu Wang; Hanghang Zhao; Shaohua Li; Bin Guo; Xunrong Huang; Pengcheng Gao; Shaoquan Xu; Puhui Ji (Journal of Environmental Chemical Engineering, 2024)

Recruitment dynamics in a tropical karst seasonal rain forest: Revealing complex processes from spatial patterns - Ruixia Ma; Jianxing Li; Yili Guo; Bin Wang; Wusheng Xiang; Dongxing Li; Fuzhao Huang; Fang Lu; Shujun Wen; Shuhua Lu; Xian-kun Li (Forest Ecology and Management, 2024)

The connection between the antibiotic resistome and nitrogen-cycling microorganisms in paddy soil is enhanced by application of chemical and plant-derived organic fertilizers - Yuan Wang; Jingjing Cai; Xiaodong Chen; Bin Guo; Junli Liu; Gaoyang Qiu; Hua Li (Environmental Research, 2024)

Evaluation of MERRA-2 and CAMS reanalysis for black carbon aerosol in China - Weijie Li; Yaqiang Wang; Ziwei Yi; Bin Guo; Wencong Chen; Huizheng Che; Xiaoye Zhang (Environmental Pollution, 2024)

Design of porous ZrO2 with well-tuned band structures and strong visible-light harvesting via Zn doping for enhanced visible-light photocatalysis - Bin Wang; Yifan Guo; Qian Li; Changhui Xin; Yajie Tian; Weiping Zhang; Xin Yu (Chemical Engineering Journal, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Soil carbon turnover and balance in the priming effects of basalt, montmorillonite, and kaolinite in a Luvisol soil - Junyan Xu; Junli Liu; Qinglin Fu; Ming Zhang; Bin Guo; Hua Li; Xiaodong Chen; Gaoyang Qiu (Journal of Soils and Sediments, 2024)

Icariin ameliorates the cuprizone-induced demyelination associated with antioxidation and anti-inflammation - Li-Juan Song; Qing-Xian Han; Zhi-Bin Ding; Kexin Liu; Xiao-Xu Zhang; Min-Fang Guo; Dong Ma; Qing Wang; Bao-Guo Xiao; Cun-Gen Ma (Inflammopharmacology, 2024)

Interactive effects of dietary leucine and isoleucine affect amino acid profile and metabolism through AKT/TOR signaling pathways in blunt snout bream (Megalobrama amblycephala) - Mang-mang Wang; Yang-yang Huang; Wen-bin Liu; Kang Xiao; Xi Wang; Hui-xing Guo; Yi-lin Zhang; Jing-Wei Fan; Xiang-fei Li; Guang-zhen Jiang (Fish Physiology and Biochemistry, 2024)

Effect of exposures to multiple metals on blood pressure and hypertension in the elderly: a community-based study - Wen-lei Hu; Wei Xiao; Wen-bin Shen; Yue-yang Wu; Xue Li; Qi Zhong; Guo-ao Li; Huan-huan Lu; Jian-jun Liu; Zhi-hua Zhang; Fen Huang (BioMetals, 2024)

Overview on Mangrove Forest Disaster Prevention and Mitigation Functions - Xinping Chen; Ziqi Yin; Zibin Li; Bin Wang; Aifeng Tao; Zhixing Guo; Fei Wang; Yanhong An; Kieran O’Driscoll (Journal of Ocean University of China, 2024)

Global burden study of lower respiratory infections linked to low temperatures: an analysis from 1990 to 2019 - Yunhui Yu; Ce Liu; Ji Zhou; Ling Zheng; Xiaobing Shan; Li He; Ling Zhang; Jingzhe Guo; Bin Luo (Environmental Science and Pollution Research, 2024)

A new C 19 -diterpenoid alkaloid in Aconitum georgei Comber - Lin-Lin Yao; Sheng-Qi Zhang; Ce Guo; Bin-Xian Li; Hua-Juan Yang; Tian-Peng Yin; Le Cai (Natural Product Research, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Responses of lettuce (Lactuca sativa L.) growth and soil properties to conventional non-biodegradable and new biodegradable microplastics - Weixuan Wang; Yingmei Xie; Han Li; Hongmin Dong; Bin Li; Yunjie Guo; Yutong Wang; Xinrui Guo; Tao Yin; Xiaowei Liu; Weiwei Zhou (Environmental Pollution, 2024)

Visible-light-driven CO2 reduction to CO boosted by hydrogenated sphalerite-type CoO atomic layers with exposed polar {1 1 1} surfaces and the photocatalytic mechanism - Junyi Guo; Zehao Sun; Qi Luo; Xiaohua Meng; Xinyi Fan; Yali Zhou; Nana Fan; Yexuan He; Xiaobo Li; Bin Liu; Heqing Yang (Chemical Engineering Journal, 2024)

Retraction Note to: Mesothelial cells differentiate into fibroblast-like cells under the scirrhous gastric cancer microenvironment and promote peritoneal carcinomatosis in vitro and in vivo - Zhi-Dong Lv; Hai-Bo Wang; Qian Dong; Bin Kong; Jian-guo Li; Zhao-Chuan Yang; Hui-Li Qu; Wei-Hong Cao; Hui-Mian Xu (Molecular and Cellular Biochemistry, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Establishment and characterization of a patient-derived solitary fibrous tumor/hemangiopericytoma cell line model - Jing Yi Lee; Peiyong Guan; Abner Herbert Lim; Zexi Guo; Zhimei Li; Jessica Sook Ting Kok; Elizabeth Chun Yong Lee; Boon Yee Lim; Bavani Kannan; Jui Wan Loh; Cedric Chuan-Young Ng; Kah Suan Lim; et al. (Human Cell, 2023)

Lighting Up Fluorescence: Precise Recognition of Halogenated Solvents Through Effective Fluorescence Detection Using Chalcone Derivatives as a D-A-D-A-type Fluorescent Chemosensor - Guo Yang; Yuanwei Li; Bin Wang; Ying Zhang (Journal of Fluorescence, 2023)

Toxicological evaluation of TBBPA by common carp (Cyprinus carpio) about the in vivo/vitro disturbance of the AHR pathway - Renjun Wang; Chen Zhang; Xingyang Li; Weilai Sha; Zhenhong Xue; Zhiguang Zhou; Yongchao Ma; Shuyun Zhu; Zitong Guo; Bin Zhao; Wanglong Zhang (Science of The Total Environment, 2023)

Vertical distribution and characteristics of soil microplastics under different land use patterns: A case study of Shouguang City, China - Jizhi Li; Bin Zhu; Bin Huang; Jian Ma; Caiyan Lu; Guangyu Chi; Wei Guo; Xin Chen (Science of The Total Environment, 2023)

Cephalopod-inspired polymer composites with mechanically tunable infrared properties - Bin Yao; Xinwei Xu; Zhubing Han; Wenhan Xu; Guang Yang; Jing Guo; Guixin Li; Qing Wang; Hong Wang (Science Bulletin, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Red mud-based heterogeneous catalyst for hydrothermal resource-based degradation of norfloxacin in pharmaceutical wastewater by hydrogen peroxide - Yuwei Zhang; Junjiang Guo; Bin Li; Zhiwei Wang; Zunzhu Xu (Journal of Water Process Engineering, 2023)

Sunlight-induced degradation of COVID-19 antivirals arbidol in natural aquatic environments: Mechanisms, pathways and toxicity - Ziwei Guo; Huan He; Kunqian Liu; Shicheng Yang; Zihui Li; Chaochao Lai; Zhicheng Liao; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Environmental Management, 2023)

Photocatalytic degradation of tetrabromobisphenol A by Z-scheme WO3/ZnIn2S4 heterojunction: Efficiency, mechanism and toxicity evaluation - Bin Xu; Zhiquan An; Minjie Li; Bihong Zhang; Liang-Hong Guo (Journal of Environmental Chemical Engineering, 2023)

The repair mechanism of sublethal Salmonella by intense pulsed light treatment - Qing Chen; Lijun Ding; Yawen Duan; Chunlei Shi; ke Li; Chunfeng Guo; Zhenpeng Gao; Bin Liu (Food Bioscience, 2023)

Fabrication and characterization of Plumula nelumbinis extract loaded gelatin/zein films (PNE@GZF) to prolong strawberries shelf-life - Yuan Li; Liang Guo; Xiaohan Yi; Qixuan Xu; Qiao Zhang; Yanxin Zhou; Xiaoyan Li; Bin Chen; Ningwei Zhao; Wei Pan; Yibo He; Peng Cao; et al. (Food Control, 2023)

Inducing root redundant development to release oxygen: An efficient natural oxygenation approach for subsurface flow constructed wetland - Jingying Zhang; Qiuhui Yan; Ge Bai; Dun Guo; Yanbin Chi; Bin Li; Lei Yang; Yongxiang Ren (Environmental Research, 2023)

Remediation of Pb(II) and Cd(II) in polluted waters with calcium thioglycolate–modified straw biochar - Shaohua Li; Chi Luo; Fan Yan; Yue Yang; Bin Guo; Lu Wang; Shaoquan Xu; Feng Wu; Puhui Ji (Environmental Pollution, 2023)

Hydrodeoxygenation of guaiacol to bio-hydrocarbons in alkaline condition on the Ni/AC catalyst with an “acid-switch” - Yanlin Xu; Yacong Deng; Bin Liu; Zhuoyi Liu; Wenhong Wang; Yuan Pan; Bin Dong; Yichuan Li; Changlong Yin; Hailing Guo; Yongming Chai; Chenguang Liu (Chemical Engineering Journal, 2023)

Mixing intensification and kinetics of 2,4-difluoronitrobenzene homogeneous nitration reaction in a heart-shaped continuous-flow microreactor - Shuai Guo; Le-wu Zhan; Bin-dong Li (Chemical Engineering Journal, 2023)

High-fat diet alters intestinal microbiota and induces endoplasmic reticulum stress via the activation of apoptosis and inflammation in blunt snout bream - Kenneth Prudence Abasubong; Guang-Zhen Jiang; Hui-xing Guo; Xi Wang; Xiang-Fei Li; Dong Yan-zou; Wen-bin Liu; Hesham Eed. Desouky (Fish Physiology and Biochemistry, 2023)

Microalgae from the Three Gorges Reservoir for Carbon Dioxide Fixation and Biodiesel Production - Ping Yang; Bin Chen; Kaikai Deng; Lei Liao; Yixuan Li; Guijiao Lin; Jinsong Guo (BioEnergy Research, 2023)

Study on seismic petrophysics and dispersion characteristics of carbonate rocks with deep ultra-deep complex pore structure in Tarim Basin - Chuang Li; Jian-guo Pan; Hong-bin Wang; Hui-zhen Li; Chao Feng; Jun-feng Zhou (Applied Geophysics, 2023)

Decreased SIRT1 mRNA expression in peripheral blood mononuclear cells from patients with neuromyelitis optica spectrum disorders - Lu Zhang; Yumei Xue; Congcong Yuan; Xiaochen Du; Xuan Wang; Li Guo; Bin Li (Acta Neurologica Belgica, 2023)

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

Catalytic activity-modulated etching of plasmonic gold nanorods enabled ultra-sensitive colorimetric strategy for Early-Stage cancer diagnosis - Caiping Ding; Ming Li; Weiwei Chen; Zikang Chen; Zhanhu Guo; Ben Bin Xu; Xuehua Zhang; Zhiyong Guo; Youju Huang (Chemical Engineering Journal, 2023)

Starch/polyvinyl alcohol with ionic liquid/graphene oxide enabled highly tough, conductive and freezing-resistance hydrogels for multimodal wearable sensors - Xueting Li; Shiqing Zhang; Xiaonan Li; Lu Lu; Bo Cui; Chao Yuan; Li Guo; Bin Yu; Qingqing Chai (Carbohydrate Polymers, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

Generation estimation and metals recycling potentials evaluation of retired mobile phones in Korea - Ang Li; Bo Li; Huibin Wang; Xia Liu; Yanan Guo; Bin Lu (Environmental Science and Pollution Research, 2023)

Impact of ryegrass cover crop inclusion on soil phosphorus and pqqC- and phoD-harboring bacterial communities - Xiaodong Chen; Yuan Wang; Jianhong Wang; Leo M. Condron; Bin Guo; Junli Liu; Gaoyang Qiu; Hua Li (Soil and Tillage Research, 2023)

Exploring HONO formation and its role in driving secondary pollutants formation during winter in the North China Plain - Shaobin Zhang; Guo Li; Nan Ma; Yao He; Shaowen Zhu; Xihao Pan; Wenlin Dong; Yanyan Zhang; Qingwei Luo; Jeannine Ditas; Uwe Kuhn; Yuxuan Zhang; et al. (Journal of Environmental Sciences, 2023)

Kinetics study on the catalytic recombination of non-premixed hydrogen–oxygen system: Effects of initial temperature, oxygen flow rate, and hydrogen diffusion time - Xuan Li; Si-Yuan Zhou; Jing Zhang; Zhuo-Wei Guo; Man-Qi Guan; Bin Li; Dan Zhang; Yong-Xu Wang; Li-Feng Xie (Fuel, 2023)

Oral bovine serum albumin administration alleviates inflammatory signals and improves antioxidant capacity and immune response under thioacetamide stress in blunt snout bream fed a high-calorie diet - Kenneth Prudence Abasubong; Guang-Zhen Jiang; Hui-xing Guo; Xi Wang; Yang-yang Huang; Yong-Jun Dai; Xiang-Fei Li; Yan-zou Dong; Ndakalimwe Naftal Gabriel; Wen-bin Liu (Fish & Shellfish Immunology, 2023)

Long-term effects on liver metabolism induced by ceftriaxone sodium pretreatment - Chengze Lai; Linkang Chen; Xiaoting Zhong; Zeli Tang; Bin Zhang; Yu Luo; Chengji Li; Mengcheng Jin; Xu Chen; Jinglin Li; Yinying Shi; Yanqin Sun; et al. (Environmental Pollution, 2023)

Temperature-adaptive porous polymer radiative cooling coatings for all-season thermal management and annual energy-saving - YingJie Wu; Bin Liu; RenYan Zhang; Tao Yu; MingBo Pu; Xiong Li; XiaoLiang Ma; YongCai Guo; XianGang Luo (Energy and Buildings, 2023)

The anion conductivity of acid-doped polybenzimidazole membrane and utilization in mitigating the capacity decay of vanadium redox flow battery stacks - Zhenyu Wang; Jiayou Ren; Jing Sun; Yiju Li; Zixiao Guo; Bin Liu; Xinzhuang Fan; Tianshou Zhao (Chemical Engineering Journal, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Confinement strategy to boost the compatibility of hybrid microbial-inorganic catalysis for highly efficient CO2 reduction - Siyuan Xiu; Jianguo Lu; Yichuan Guo; Youzhi Li; Folin Liu; Jiani Yao; Haoliang Wu; Bin Yang; Yang Hou; Lecheng Lei; Zhongjian Li (Chemical Engineering Journal, 2023)

AIEgen-based nanotherapeutic strategy for enhanced FLASH irradiation to prevent tumour recurrence and avoid severe side effects - Meng Lyu; Tianfu Zhang; Yang Li; Jingfeng Xiang; Daoming Zhu; Ligang Xia; Bin Guo; Youhua Xu; Haijun Yu; Benzhong Tang (Chemical Engineering Journal, 2023)

Effects of magnetic field direction on O + vertical transport in the Martian ionosphere - Shi-bang Li; Hao-yu Lu; Jin-bin Cao; Jun Cui; Yun Li; Guo-kan Li; Ni-han Chen; Jian-xuan Wang (Advances in Space Research, 2023)

Course-, dose-, and stage-dependent toxic effects of prenatal acetaminophen exposure on fetal long bone development - Chi Ma; Xufeng Li; Hao Xiao; Bin Li; Hanwen Gu; Yu Guo; Hui Wang; Yinxian Wen; Liaobin Chen (Toxicology Letters, 2023)

Frequent heatwaves limit the indirect growth effect of urban vegetation in China - Shengjun Gao; Yunhao Chen; Kangning Li; Bin He; Peng Hou; Zheng Guo (Sustainable Cities and Society, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

Expanding Azania at the heart of Gondwana: Terrane correlation from Southern India to Sri Lanka - Lei Zhao; Prasanna Lakshitha Dharmapriya; Yan-Bin Zhang; Ming-Guo Zhai; Jing-Hui Guo; Amarasooriya Pitawala; Xian-Hua Li (Precambrian Research, 2023)

Early Paleozoic subduction imprints of the Proto-Tethys Ocean: Evidence from the Appinite–Diorite–Granodiorite complex in East Kunlun, Northern Tibet - Yang-Ming Hu; Xiao-Wei Li; Xuan-Xue Mo; Lin Li; Kai Wang; Bing-Zhang Wang; Xiao-Ping Gong; Guo-Chen Dong; Yan-Bin Liu (Lithos, 2023)

Water-in-oil oleogel with biphasic stabilization for fabrication of low-fat salad dressing - Fuying Wang; Li Guo; Han Liu; Hongxun Tao; Bin Yu; Haibo Zhao; Jianpeng Li; Haiteng Tao; Bo Cui; Yuxiao Wang (Food Hydrocolloids, 2023)

Whey protein isolate nanofibrils as emulsifying agent to improve printability of Cheddar cheese for 3D printing - Dongxu Wang; Jiaxuan Guo; Yexuan Wang; Yue Yang; Bin Jiang; Dongmei Li; Zhibiao Feng; Chunhong Liu (Food Hydrocolloids, 2023)

Screening and prioritization of organic chemicals in a large river basin by suspect and non-target analysis - Jia-Hui Zhao; Li-Xin Hu; Sheng Xiao; Jian-Liang Zhao; You-Sheng Liu; Bin Yang; Qian-Qian Zhang; Guang-Guo Ying (Environmental Pollution, 2023)

Enhanced phosphate removal by filler encapsulation and surface engineering using SA/PVA matrix: Fabrication optimization, adsorption behaviors and inner removal mechanism - Bin Wang; Xiaoling Hu; Lu Li; Yi Xie; Rongfan Chen; Wenbin Guo; Hongyu Wang; Mingfei Wang; Jian Shi; Ling Chen; Dao Zhou (Chemical Engineering Journal, 2023)

Overlithiation lithium-rich Mn-based oxide as cathode pre-lithiation agent towards high-energy-density batteries - Juanlang Guo; Shihao Li; Bin Zhu; Haiyan Zhang; Xianggang Gao; Yulun Wu; Shuai Zhang; Naifeng Wen; Xu Wang; Yanqing Lai; Zhian Zhang (Chemical Engineering Journal, 2023)

Neural-network-assisted optimization of a close-range multi-spacecraft rendezvous mission based on a multi-impulse maneuvering strategy - Huida Yan; Yanning Guo; Chuanjiang Li; Bin Song (Advances in Space Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

New insights into the protection of dietary components on anxiety, depression, and other mental disorders caused by contaminants and food additives - Ruo-Gu Xiong; Jiahui Li; Jin Cheng; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan; Yibin Feng (Trends in Food Science & Technology, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Reproductive and developmental toxicity assessments of LPM3480392, a novel mu opioid receptor biased agonist in rats - Bin Liu; Hongyu Chen; Chunmei Li; Yana Guan; Wanglin Jiang; Hanrong Wang; Wei Guo; Wen Wen; Xiaobo Cen; Hongbo Wang; Jingwei Tian (Reproductive Toxicology, 2023)

Anion exchange resin/quartz sand bi-layer composite dynamic membranes in ultrafiltration for algae-laden water treatment - Cong Ma; Xinbin Guo; Tong Li; Xi Jiang; Liang Wang; Bin Zhao; Zhaohui Zhang (Process Safety and Environmental Protection, 2023)

New α-pyrone and unsaturated ketone analogues from the endophytic fungus Lasiodiplodia sp. and their cytotoxic effects - Wei Dong; Wen-Bin Gao; Fan-Wei Liu; Jin-Ye; Ying Chen; Hong-Lian Zhang; Zhen Lv; Li-Na Guo; Bo Song (Phytochemistry Letters, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Determining the degradation mechanism and application potential of benzopyrene-degrading bacterium Acinetobacter XS-4 by screening - Xiaoshuang Zou; Qi Su; Qianwen Yi; Ling Guo; Diyong Chen; Bin Wang; Yancheng Li; Jiang Li (Journal of Hazardous Materials, 2023)

A relatively warm and humid Oligocene climate in the northeastern Tibetan Plateau based on a high-resolution clay mineralogical and geochemical record - Chunxia Zhang; Ran Zhang; Bin Hu; Xiaoyan Zhang; Pei Li; Ning Tan; Yunxia Jia; Zhilin He; Haibin Wu; Zhengtang Guo (Global and Planetary Change, 2023)

pH-Regulated lignin as a green catalyst for Highly-Efficient CO2 cycloaddition - Yidan Ouyang; Bin Lei; Zhouqing Tan; Fen Hu; Zhao Wu; Jiaxue Wang; Yixuan Ma; Ran Zhang; Li Guo; Feifei Chen (Fuel, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

The use of the general thermal sensation discriminant model based on CNN for room temperature regulation by online brain-computer interface - Yangyi Guo; Xiaohe He; Hailong Li; Bin Liu; Shengchun Liu; Hongzhi Qi (Building and Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Current extraction, purification, and identification techniques of tea polyphenols: An updated review - Hang Li; Huan Guo; Qiong Luo; Ding-Tao Wu; Liang Zou; Yi Liu; Hua-Bin Li; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2023)

Effects and mechanisms of tea on obesity - Xiao-Yu Xu; Cai-Ning Zhao; Bang-Yan Li; Guo-Yi Tang; Ao Shang; Ren-You Gan; Yi-Bin Feng; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2023)

High adsorption performance for trace lead (II) cation from sewage by Fe/Cu metal organic nanosheets modified with terephthalic acid - Xiaofeng Shi; Lingshu Gao; Eman Alzahrani; Junmao Hong; Abdullah K. Alanazi; Hala M. Abo-Dief; Junhua Li; Ben Bin Xu; Hassan Algadi; Zeinhom M. El-Bahy; Zhanhu Guo (Chemosphere, 2023)

A global lithospheric magnetic field model between ± 65° latitude derived from CSES satellite scalar data - Jie Wang; Xuhui Shen; Yanyan Yang; Zhima Zeren; Bin Zhou; Magnes Werner; Angelo De Santis; Jianping Huang; Changli Yao; Zelin Li; Yuanman Zheng; Shufan Zhao; et al. (Physics of the Earth and Planetary Interiors, 2023)

Nitration of o-xylene in the microreactor: Reaction kinetics and process intensification - Shuai Guo; Le-wu Zhan; Bin-dong Li (Chemical Engineering Journal, 2023)

An efficient seeding state monitoring system of a pneumatic dibbler based on an interdigital capacitive sensor - Luochuan Xu; Bin Hu; Junwei Li; Ling Ren; Mengyu Guo; Zibin Mao; Yiquan Cai; Sheng Sun (Computers and Electronics in Agriculture, 2023)

Identifying plant disease and severity from leaves: A deep multitask learning framework using triple-branch Swin Transformer and deep supervision - Bin Yang; Zhulian Wang; Jinyuan Guo; Lili Guo; Qiaokang Liang; Qiu Zeng; Ruiyuan Zhao; Jianwu Wang; Caihong Li (Computers and Electronics in Agriculture, 2023)

Microalgae-based constructed wetland system enhances nitrogen removal and reduce carbon emissions: Performance and mechanisms - Xinyue Zhao; Tuoshi Zhang; Bin Dang; Mengran Guo; Ming Jin; Chunyan Li; Ning Hou; Shunwen Bai (Science of The Total Environment, 2023)

The photolytic behavior of COVID-19 antivirals ribavirin in natural waters and the increased environmental risk - Ziwei Guo; Huan He; Kunqian Liu; Zihui Li; Shicheng Yang; Zhicheng Liao; Chaochao Lai; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2023)

New insight into desorption behavior and mechanism of oil from aged oil-contaminated soil in microemulsion - Xiaoning Feng; Shuhai Guo; Fushan Wen; Wei Zhu; Xiujie Yang; Meixia Gu; Nan Shi; Zhiheng Li; Bin Lou; Dong Liu (Journal of Hazardous Materials, 2023)

A clean two-stage Bayer process for achieving near-zero waste discharge from high-iron gibbsitic bauxite - Guo-tao Zhou; Yi-lin Wang; Yu-guan Zhang; Tian-gui Qi; Qiu-sheng Zhou; Gui-hua Liu; Zhi-hong Peng; Xiao-bin Li (Journal of Cleaner Production, 2023)

The roles of red mud as desulfurization and denitrification in flue gas: A review - Shuai Liu; Zewei Liu; Hengxi Zhu; Zixuan Wang; Junjiang Guo; Xiaoyue Zhang; Hongxin Yu; Xiangdong Yue; Ping Ning; Bin Li (Journal of Environmental Chemical Engineering, 2023)

Structural annotation, semi-quantification and toxicity prediction of pyrrolizidine alkaloids from functional food: In silico and molecular networking strategy - Yaping Xu; Jie Li; Huajian Mao; Wei You; Jia Chen; Hua Xu; Jianfeng Wu; Ying Gong; Lei Guo; Tao Liu; Wuju Li; Bin Xu; et al. (Food and Chemical Toxicology, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Taxonomic study of species of tribe Aphonoidini Gorochov, 2008 (Orthoptera: Oecanthidae) based on ovipositor morphology in China - Qian Wu; Rong-Hua Guo; Li-Bin Ma (Zoologischer Anzeiger, 2023)

Transcriptomic and antiviral analyses of PoIFN-Delta5 against porcine enteric viruses in porcine intestinal epithelial cells - Xuejiao Zhu; Baochao Fan; Shiying Song; Jie Gao; Jinzhu Zhou; Yongxiang Zhao; Weilu Guo; Xue Zhang; Jiali Qian; Mingjun Zhu; Jizong Li; Yunchuan Li; et al. (Veterinary Microbiology, 2023)

Failure experiment on CFRP-strengthened prestressed concrete cylinder pipe with broken wires - Kejie Zhai; Hongyuan Fang; Bin Li; Chengchao Guo; Kangjian Yang; Xueming Du; Mingrui Du; Niannian Wang (Tunnelling and Underground Space Technology, 2023)

Elevated CO2 and temperature increase arbuscular mycorrhizal fungal diversity, but decrease root colonization, in maize and wheat - Zihao Liu; Zhenhua Yu; Bin Song; Yansheng Li; Jie Fang; Yaping Guo; Jian Jin; Jonathan M. Adams (Science of The Total Environment, 2023)

Effects of transglutaminase and glucose oxidase on the properties of frozen dough: Water distribution, rheological properties, and microstructure - Wen-Tao Guo; Xue-Fei Yang; Yi-Shun Ji; Bin Hu; Wan-Guang Li; Xi-Yang Zhong; Shao-Tong Jiang; Zhi Zheng (Journal of Cereal Science, 2023)

Impact of heat on all-cause and cause-specific mortality: A multi-city study in Texas - Chunyu Guo; Kevin Lanza; Dongying Li; Yuyu Zhou; Kristin Aunan; Becky P.Y. Loo; Jason Kai Wei Lee; Bin Luo; Xiaoli Duan; Wangjian Zhang; Zhengjun Zhang; Shao Lin; et al. (Environmental Research, 2023)

Evaluating the performance of a novel ventilated embankment structure in warm permafrost regions by numerical simulation - Zhanyuan Zhu; Zonghang He; Fei Luo; Bin Luo; Chenxuan Tang; Zuyin Zou; Zihong Guo; Weimin Xiao; Xiangang Jiang; Lin Li (Cold Regions Science and Technology, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Description and evaluation of a newly developed emission inventory processing system (EMIPS) - Wencong Chen; Yaqiang Wang; Jiawei Li; Ziwei Yi; Zhenchi Zhao; Bin Guo; Huizheng Che; Xiaoye Zhang (Science of The Total Environment, 2023)

Molecular tracers, mass spectral tracers and oxidation of organic aerosols emitted from cooking and fossil fuel burning sources - Chengrui Liang; Shuxiao Wang; Ruolan Hu; Guanghan Huang; Jinzi Xie; Bin Zhao; Yuyang Li; Wenfei Zhu; Song Guo; Jingkun Jiang; Jiming Hao (Science of The Total Environment, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity - Yu-Fei Xi; Ming Bai; Xin Zhang; Zi-Lin Hou; Bin Lin; Guo-Dong Yao; Li-Li Lou; Xiao-Bo Wang; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Environmental profiling microalgae-based eicosapentaenoic acid production along the technical advancement via life cycle assessment - Zi-Hao Qin; Xiaomeng Hu; Jin-Hua Mou; Guo-Hui He; Guang-Bin Ye; Hong-Ye Li; Shauhrat Singh Chopra; Liang Dong; Carol Sze Ki Lin; Xiang Wang (Journal of Cleaner Production, 2023)

Insight into the desorption behavior of oily soil with different particle sizes based on accumulation effect and binding interaction - Xiaoning Feng; Zhiheng Li; Xiujie Yang; Bin Lou; Fushan Wen; Nan Shi; Wei Zhu; Shuhai Guo; Meixia Gu; Dong Liu (Journal of Environmental Chemical Engineering, 2023)

Toward sustainable green alumina production: A critical review on process discharge reduction from gibbsitic bauxite and large-scale applications of red mud - Guo-tao Zhou; Yi-lin Wang; Tian-gui Qi; Qiu-sheng Zhou; Gui-hua Liu; Zhi-hong Peng; Xiao-bin Li (Journal of Environmental Chemical Engineering, 2023)

Effect of nitrite on hydrolysis-acidification, biogas production and microbial community in semi-continuous two-phase anaerobic digestion of sewage sludge - Qian Sheng; Yiqing Lu; Shijie Yuan; Xiaowei Li; Xiaohu Dai; Yali Guo; Bin Dong (Journal of Environmental Sciences, 2023)

Utilization of KOH-modified fly ash for elimination from aqueous solutions of potentially toxic metal ions - Yue Yang; Lu Wang; Hanghang Zhao; Fan Yan; Shaohua Li; Bin Guo; Chi Luo; Xunrong Huang; Puhui Ji (Environmental Research, 2023)

Association between thermal comfort and cortisol depends on the air temperature and exposure time - Xiaoxia Zhang; Songtao Hu; Chengji Guo; Rujin Liu; Li Tong; Baoshan Shi; Bin Li (Building and Environment, 2023)

Atomic coordination structural dynamic evolution of single-atom Mo catalyst for promoting H2 activation in slurry phase hydrocracking - Guangxun Sun; Dongyuan Liu; Min Li; Shu Tao; Zekun Guan; Yanfei Chen; Shihuan Liu; Qingzhou Du; Han Guo; Xinyue Yuan; Xinying Zhang; Houyu Zhu; et al. (Science Bulletin, 2023)

Carbon dots as light-responsive oxidase-like nanozyme for colorimetric detection of total antioxidant capacity in fruits - Jinquan Li; Yun Zhou; Yue Xiao; Shuo Cai; Changsheng Huang; Shuo Guo; Yuanqiang Sun; Rong-Bin Song; Zhaohui Li (Food Chemistry, 2023)

Simultaneous defect passivation and energy level modulation by multifunctional phthalocyanine for efficient and stable perovskite solar cells - Jiawei Zhang; Tie Liu; Zhiqiang Bao; He Liu; Ying Lv; Xiaoyang Guo; Xingyuan Liu; Yulei Chang; Bin Li (Chemical Engineering Journal, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Water quality criteria derivation and tiered ecological risk evaluation of antifouling biocides in marine environment - Hai-Wei Luo; Min Lin; Xin-Xin Bai; Bin Xu; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Photoaging mechanisms of microplastics mediated by dissolved organic matter in an iron-rich aquatic environment - Huan He; Kunqian Liu; Ziwei Guo; Fan Li; Zhicheng Liao; Xiaoxia Yang; Xiaomin Ren; Huang Huang; Bin Huang; Xuejun Pan (Science of The Total Environment, 2023)

Effect of grazing exclusion on emission of greenhouse gases and soil organic carbon turnover in alpine shrub meadow - Zhiqiang Dang; Na Guo; Shanshan Li; A. Allan Degen; Jingjuan Cao; Bin Deng; Aidong Wang; Zhen Peng; Luming Ding; Ruijun Long; Zhanhuan Shang (Science of The Total Environment, 2023)

HSQC-based small molecule accurate recognition technology discovery of diverse cytotoxic sesquiterpenoids from Elephantopus tomentosus L. and structural revision of molephantins A and B - Ming Bai; Wei Xu; Xin Zhang; Qian Li; Ning-Ning Du; De-Feng Liu; Guo-Dong Yao; Bin Lin; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Porous phosphomolybdate-based poly(ionic liquid) hybrids with reversible water absorption for enhancement of oxidative desulfurization - Shao-Xu Mao; Qi-Hang Zhou; Hui-Li Guo; Ming Du; Wen-Shuai Zhu; Hua-Ming Li; Jing-Yu Pang; Dong-Bin Dang; Yan Bai (Fuel, 2023)

Water-borne, durable and multicolor silicon nanoparticles/sodium alginate inks for anticounterfeiting applications - Jing Xie; Xuening Sun; Xin Guo; Xiang Feng; Kailong Chen; Xin Shu; Chenhao Wang; Wei Sun; Yang Liu; Bin Shang; Xin Liu; Dongzhi Chen; et al. (Carbohydrate Polymers, 2023)

Smog chamber study of secondary organic aerosol formation from gas- and particle-phase naphthalene ozonolysis - Jixing Liu; Shuping Zhu; Teng Guo; Bin Jia; Li Xu; Jun Chen; Ping Cheng (Atmospheric Environment, 2023)

Highly Engrafting Cord Blood Hematopoietic Stem Cells are Enriched in CD34+ Cell Population with High Autophagy Activity - Qingwei Ding; Jingchao Zhou; Yu Li; Qin Wang; Chunxu Yao; Rongzhen Jiang; Qingyou Meng; Haitao Wang; Yandan Chen; Bin Guo (Stem Cell Reviews and Reports, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Grass cover increases soil microbial abundance and diversity and extracellular enzyme activities in orchards: A synthesis across China - Yangzhou Xiang; Scott X. Chang; Yuying Shen; Guo Chen; Ying Liu; Bin Yao; Jianming Xue; Yuan Li (Applied Soil Ecology, 2023)

Dietary interventions for better management of osteoporosis: An overview - Danjun Guo; Mengge Zhao; Wei Xu; Hui He; Bin Li; Tao Hou (Critical Reviews in Food Science and Nutrition, 2023)

Enhanced water permeance and EDCs rejection using a UiO-66-NH2-predeposited polyamide membrane - Bin Zhao; Min Sun; Zhiqiang Guo; Liang Wang; Yiran Qian; Xiaojia He; Jixiang Li (Chemosphere, 2023)

Alleviation of aqueous nitrogen loss from paddy fields by growth and decomposition of duckweed (Lemna minor L.) after fertilization - Yuan Wang; Xiaodong Chen; Bin Guo; Chen Liu; Junli Liu; Gaoyang Qiu; Qinglin Fu; Hua Li (Chemosphere, 2023)

Hypoxia mediates Hif-1α to affect myofiber development and Vc regulates the influence by activating Shh-Gli pathway in channel catfish (Ictalurus punctatus) - Kang Xiao; Xi Wang; Yong-jun Dai; Yang-yang Huang; Mang-mang Wang; Hui-Xing Guo; Wen-Bin Liu; Xiang-fei Li; Kenneth Prudence Abasubong; Guang-Zhen Jiang (Aquaculture, 2023)

The fecal arsenic excretion, tissue arsenic accumulation, and metabolomics analysis in sub-chronic arsenic-exposed mice after in situ arsenic-induced fecal microbiota transplantation - Yu Luo; Jiating Wang; Chenfei Wang; Dongbin Wang; Chengji Li; Bin Zhang; Xiaoting Zhong; Linkang Chen; Hao Li; Hongtian Su; Qiuyi Zheng; Dajian Zhu; et al. (Science of The Total Environment, 2023)

The optimum cooking time: A possible key index for predicting the deterioration of fresh white-salted noodle - Qin Guo; Yun-ting Li; Jia-hui Cai; Cheng-wan Ren; Muhammad Adil Farooq; Bin Xu (Journal of Cereal Science, 2023)

Physicochemical characteristics and biological activities of soluble dietary fibers isolated from the leaves of different quinoa cultivars - Yi-Chen Hu; Ju-Li Hu; Jie Li; Jin Wang; Xian-Yue Zhang; Xiao-Yong Wu; Xiang Li; Zhan-Bin Guo; Liang Zou; Ding-Tao Wu (Food Research International, 2023)

Effects of physiologic activities of plankton on CO2 flux in the Three Gorges Reservoir after rainfall during algal blooms - Yi-Xuan Li; Kai-Kai Deng; Gui-Jiao Lin; Bin Chen; Fang Fang; Jin-Song Guo (Environmental Research, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Impact of the COVID-19 on electricity consumption of open university campus buildings – The case of Twente University in the Netherlands - Sheng Xu; Bin Cheng; Zefeng Huang; Tao Liu; Yuan Li; Lin Jiang; Wei Guo; Jie Xiong (Energy and Buildings, 2023)

Inoculation with Arbuscular Mycorrhizal Fungi Reinforces Tea Plant’s Tolerance to Salinity - Shasha Guo; Qi Wang; Lei Tang; Tianxin Zhang; Jiayang Li; Yao Xiao; Yuefang Gao; Juan Bai; Bin Xiao; Chunmei Gong (Journal of Plant Growth Regulation, 2022)

Genome-Wide Identification Reveals the Potential Functions of the bZIP Gene Family in Common Bean (Phaseolus vulgaris) in Response to Salt Stress During the Sprouting Stage - Qi Zhang; Wen-jing Zhang; Zhen-gong Yin; Wei-jia Li; Chun-Yang Xia; Hao-Yue Sun; Yi-Ming Yang; Hong-Bin Wu; Shuo Zhang; Hao-hao Zhao; Wen-Hui Zhang; Yong-xia Guo; et al. (Journal of Plant Growth Regulation, 2022)

Effects of nitrogen addition on the soil detachment in the typical grasslands of the Loess Plateau - Pan-pan Li; Bing Wang; Yan-fen Yang; Guo-bin Liu (Journal of Mountain Science, 2022)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

Regional green total factor performance analysis of China’s construction industry based on a unified framework combining static and dynamic indexes - Yan Li; Jiangfeng Wang; Bin Liu; Hongyan Li; Yumin Guo; Xinru Guo (Environmental Science and Pollution Research, 2022)

Recent development in zebrafish model for bioactivity and safety evaluation of natural products - Fang-Jun Lin; Hang Li; Ding-Tao Wu; Qi-Guo Zhuang; Hua-Bin Li; Fang Geng; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2022)

Antigenic epitope screening and functional modification of mannose enhance the efficacy of largemouth bass virus subunit vaccines - Yi‐Jun Jia; Jun‐Yao Xia; Fu‐Yi Jiang; Yang Li; Guo Chen; Bin Zhu (Journal of Fish Diseases, 2022)
Major capsid protein (MCP) can be used as a subunit vaccine against largemouth bass virus (LMBV). However, subunit vaccines usually have low immunogenicity. Here, to identify the major immunogenicity determinant region of the MCP gene, we truncated the MCP of the LMBV gene into four parts ( MCP ‐ 1, MCP ‐ 2, MCP ‐ 3 and MCP ‐ 4 ). Enzyme‐linked immunosorbent assay (ELISA) was used to identify the antigenicity of these four truncated MCP proteins. Then, the highly antigenic truncated protein was modified with mannose and connected with functionalized single‐walled carbon nanotubes (SWCNTs) as carriers. Largemouth basses were immunized by bath immersion, challenged with LMBV on the 28th day after immunization and evaluated for related immune indicators. The results indicated that the MCP‐2 protein could induce a higher antibody titre than the other truncated MCP proteins. We found that the levels of immune‐related genes ( TNF‐α, CD40 , IgM , IFNγ and IL‐10 ) in the spleen and kidney were significantly increased in the MCP‐2 and MCP‐2‐Man groups. ELISA results showed that the antibody content in the serum increased significantly in the MCP‐2 group 7 days post‐vaccination and increased with days in all the vaccinated groups, with the highest observed on the 21st day. Notably, the MCP‐2‐Man vaccine (10 mg L −1 ) showed durability of immunoprotection efficacy that could protect largemouth basses from LMBV challenge, and the immune protection rate reached 78.94%. These results suggest that MCP‐2 might be the major immunogenicity determinant region of LMBV and that the mannose‐modified MCP‐2 vaccine can induce stronger adaptive immune responses.

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Transdermal Delivery of Metformin Utilizing Ionic Liquid Technology: Insight Into the Relationship Between Counterion Structures and Properties - Minghuang Hong; Qinglin Wang; Kai Wang; Jinghui Li; Ming-Hui Qi; Guo-Bin Ren (Pharmaceutical Research, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Transcriptome Analysis of Greenfin Horse-Faced Filefish (Thamnaconus septentrionalis) Gills in Response to Amyloodinium ocellatum (AO) Infection - Li-Guo Yang; Yue Wang; Wen-Bin Xu; Bo Qin; Na Ying; Xue-Feng Song; Yan-Feng Yue; Xiao-Shan Wang; Bian-Bian Zhang; Yan-Qing Wu (Fishes, 2022)
The greenfin horse-faced filefish (Thamnaconus septentrionalis) is susceptible to recurrent Amyloodinium ocellatum (AO) infestation over the grow-out production cycle. This parasite breeds mainly on the gills, causing hypoxia in the fish body, and leading to many deaths. The host-parasite response drives a complex immune reaction, which is poorly understood. To generate a model for host-parasite interaction and the pathogenesis of AO in greenfin horse-faced filefish, an RNA-seq approach, differential gene expression, GO, and KEGG analyses were employed. Overall, 624 new genes and 2076 differentially expressed genes (DEGs) were detected, including 942 upregulated and 1134 downregulated genes in the gills. Compared with the control group, the expression of leptin a, GTPase IMAP family member 4, and NLR family CARD domain-containing protein 3 was significantly higher in the AO-infected group. Conversely, cell wall integrity and stress response component 1-like, and hepcidin-like were significantly downregulated in the gills of AO-infected fish. GO and KEGG enrichment analysis indicated that DEGs were significantly enriched in signaling pathways associated with viral protein interaction with cytokine and cytokine receptor and cytokine–cytokine receptor interaction. Collectively, this transcriptomic study provides novel molecular insights into the pathology caused by AO infestation and alternative theories for future research implementing strategies to control and manage AO.

Genome-wide association study reveals a NAC transcription factor TaNAC074 linked to pre-harvest sprouting tolerance in wheat - Hao Jiang; Yu Fang; Dong Yan; Si-tong Liu; Jun Wei; Fei-long Guo; Xing-ting Wu; Hong Cao; Chang-bin Yin; Fei Lu; Li-feng Gao; Yong-xiu Liu (Theoretical and Applied Genetics, 2022)

Review of landslide susceptibility assessment based on knowledge mapping - Chen Yong; Dong Jinlong; Guo Fei; Tong Bin; Zhou Tao; Fang Hao; Wang Li; Zhan Qinghua (Stochastic Environmental Research and Risk Assessment, 2022)

Identification and molecular mapping of YrBm for adult plan resistance to stripe rust in Chinese wheat landrace Baimangmai - Chaoyue Hu; Fengtao Wang; Jing Feng; Cai Sun; Jiyuan Guo; Xiaowei Lang; Jinghuang Hu; Bin Bai; Wentao Zhang; Hongjie Li; Ruiming Lin; Shichang Xu (Theoretical and Applied Genetics, 2022)

CREB1 contributes colorectal cancer cell plasticity by regulating lncRNA CCAT1 and NF-κB pathways - Bin Li; Lisi Zheng; Jiayi Ye; Chenmin Zhang; Jie Zhou; Qiaojuan Huang; Yanhua Guo; Luqin Wang; Peng Yu; Shurong Liu; Qiao Lin; Yuxia Luo; et al. (Science China Life Sciences, 2022)

Calenduloside E alleviates cerebral ischemia/reperfusion injury by preserving mitochondrial function - Jianxiong Li; Yujie Bu; Bin Li; Hailin Zhang; Jia Guo; Jianping Hu; Yanfang Zhang (Journal of Molecular Histology, 2022)
Calenduloside E (CE) isolated from Aralia elata (Miq.) Seem. is a natural triterpenoid saponin that can reportedly ameliorate myocardial ischemia/reperfusion injury. However, its potential roles and mechanism in cerebral ischemia/reperfusion injury are barely understood. In this study, we established an oxygen-glucose deprivation/reoxygenation (OGD/R) model in HT22 cells. We found that CE significantly attenuated the OGD/R-induced inhibition of cell viability and apoptotic cell death in HT22 cells. Moreover, CE treatment significantly ameliorated OGD/R-induced mitochondrial fission by inhibiting mitochondrial dynamin-related protein 1 (Drp1) recruitment and increasing Drp1 phosphorylation at Ser637. CE treatment significantly ameliorated OGD/R-induced mitochondrial dysfunction by increasing the mitochondrial membrane potential and reducing the mitochondrial ROS and cellular calcium accumulation. Moreover, CE treatment significantly inhibited the OGD/R-induced release of mitochondrial Cytochrome C and increase in Bax, Cleaved-caspase3 and Cleaved-caspase9 protein levels, whereas CE treatment significantly reversed the OGD/R-induced decrease in Bcl-2 and full length of caspase3 and caspase9 protein levels. In vivo, we found that CE treatment significantly ameliorated ischemic/hypoxic-induced brain infarct volume, neurological deficits, and neuronal apoptosis in mice after middle cerebral artery occlusion and reperfusion. CE treatment also significantly ameliorated the mitochondrial transmembrane potential, decreased Cytochrome C release, and reversed the increase in Bax, Cleaved-caspase3 and Cleaved-caspase9 protein levels and the decrease in Bcl-2 and full length of caspase3 and caspase9 protein levels induced by cerebral ischemia/reperfusion (I/R). All these results indicated that CE treatment exerted a neuroprotective effect by ameliorating mitochondrial dysfunction during cerebral I/R injury.

Deepened snow loosens temporal coupling between plant and microbial N utilization and induces ecosystem N losses - Zhou Jia; Ping Li; Yuntao Wu; Pengfei Chang; Meifeng Deng; Luyin Liang; Sen Yang; Chengzhang Wang; Bin Wang; Lu Yang; Xin Wang; Zhenhua Wang; et al. (Global Change Biology, 2022)
Seasonal differences in plant and microbial nitrogen (N) acquisition are believed to be a major mechanism that maximizes ecosystem N retention. There is also a concern that climate change may interrupt the delicate balance in N allocation between plants and microbes. Yet, convincing experimental evidence is still lacking. Using a 15 N tracer, we assessed how deepened snow affects the temporal coupling between plant and microbial N utilization in a temperate Mongolian grassland. We found that microbial 15 N recovery peaked in winter, accounting for 22% of the total ecosystem 15 N recovery, and then rapidly declined during the spring thaw. By stimulating N loss via N 2 O emission and leaching, deepened snow reduced the total ecosystem 15 N recovery by 42% during the spring thaw. As the growing season progresses, the 15 N released from microbial biomass was taken up by plants, and the competitive advantage for N shifted from microbes to plants. Plant 15 N recovery reached its peak in August, accounting for 17% of the total ecosystem 15 N recovery. The Granger causality test showed that the temporal dynamics of plant 15 N recovery can be predicted by microbial 15 N recovery under ambient snow but not under deepened snow. In addition, plant 15 N recovery in August was positively correlated with and best explained by microbial 15 N recovery in March. The lower microbial 15 N recovery under deepened snow in March reduced plant 15 N recovery by 73% in August. Together, our results provide direct evidence of seasonal differences in plant and microbial N utilization that are conducive to ecosystem N retention; however, deepened snow disrupted the temporal coupling between plant–microbial N use and turnover. These findings suggest that changes in snowfall patterns may significantly alter ecosystem N cycling and N‐based greenhouse gas emissions under future climate change. We highlight the importance of better representing winter processes and their response to winter climate change in biogeochemical models when assessing N cycling under global change.

Natural variation MeMYB108 associated with tolerance to stress-induced leaf abscission linked to enhanced protection against reactive oxygen species in cassava - Bin Wang; Shuxia Li; Liangping Zou; Xin Guo; Jiaxin Liang; Wenbin Liao; Ming Peng (Plant Cell Reports, 2022)
Key Message Natural variation of the MeMYB108 exon was associated with reactive oxygen scavengers led to alleviate leaf abscission under drought in cassava. Abstract The reactive oxygen scavengers play important roles in regulating the cassava ( Manihot esculenta Crantz) leaf abscission induced by stresses. To date, the relationship between natural variations of MYB genes and reactive oxygen scavengers under drought in cassava genotypes remains unclear. Here, we reported the transcription factor MeMYB108 played an important role in regulating leaf abscission exposed to drought in cassava. The expression levels of MeMYB108 in abscission zones of cassava leaf pulvinus were higher in cassava genotype SC124, which were less easy to shed leaves under stress than cassava genotype SC8 when the leaf abscission induced by the same drought condition. Compared with wild type and interference expression plants, overexpression of MeMYB108 significantly reduced the drought-induced leaf abscission rate under drought. The consecutively 2-year analysis of reactive oxygen scavengers showed significant differences among different cassava genotypes under drought-induced leaf abscission, indicating the relevance between reactive oxygen scavengers and leaf abscission. Correlation analysis revealed the natural variation of the MeMYB108 exon was associated with reactive oxygen scavengers during drought-induced leaf abscission. Association analysis between pairwise LD of DNA polymorphism indicated the MeMYB108 allele enhanced the tolerance of cassava to drought-induced leaf abscission. Complementation transgenic lines containing the elite allele of MeMYB108 SC124 decreased the leaf abscission rate induced by drought conditions, demonstrating natural variation in MeMYB108 contributed to leaf abscission tolerance induced by drought in cassava. Further studies showed MeMYB108 played an active role in the tolerance of cassava to drought-induced leaf abscission by inducing scavenging of reactive oxygen species.

The effect of meteorological drought on vegetation cover in the Yellow River basin, China - Lu Jia; Kun‐xia Yu; Zhan‐bin Li; Peng Li; Guo‐ce Xu; Yu‐ting Cheng; Xiang Zhang; Zhi Yang (International Journal of Climatology, 2022)
As a widespread natural disaster, drought has a significant impact on changes in regional vegetation cover. Based on 1‐month standardized precipitation index (SPI1), this study took the Yellow River basin (YRB) with frequent droughts as the research object, using NDVI data from 1999 to 2018, Mann–Kendall trend test, and correlation test to study the temporal and spatial characteristics of meteorological drought, explored the response of vegetation cover to meteorological drought, and further discussed the possible factors affecting meteorological drought. The results of the study showed that from 1999 to 2018, the SPI1 in the YRB had not increased significantly in a large area in different months ( p > .05). On the monthly time scale, the NDVI of the YRB gradually increased from north to south, showing a significant increasing trend the central area ( p p p

A stable block adjustment method without ground control points using bound constrained optimization - Yonghua Jiang; Zhen Li; Meilin Tan; Shaodong Wei; Guo Zhang; Zhichao Guan; Bin Han (International Journal of Remote Sensing, 2022)

Integrated metabolism and epigenetic modifications in the macrophages of mice in responses to cold stress - Jingjing Lu; Shoupeng Fu; Jie Dai; Jianwen Hu; Shize Li; Hong Ji; Zhiquan Wang; Jiahong Yu; Jiming Bao; Bin Xu; Jingru Guo; Huanmin Yang (Journal of Zhejiang University-SCIENCE B, 2022)

Impact of selenium on rhizosphere microbiome of a hyperaccumulation plant Cardamine violifolia - Zisheng Guo; Bin Zhu; Jia Guo; Gongting Wang; Meng Li; Qiaoli Yang; Liping Wang; Yue Fei; Shiwei Wang; Tian Yu; Yanmei Sun (Environmental Science and Pollution Research, 2022)

Potential Application of Biosurfactant-Producing Bacteria for Bioremediation of Oil Polluted Marine Intertidal Sediments - Ping Guo; Wei-Wei Xu; Dan-Na Wei; Man-Xia Zhang; Jin Zhang; Shi Tang; Bin-Xia Cao; Jian-Guo Lin; Wei Li (Journal of Marine Science and Engineering, 2022)
The removal of oil contaminants in marine intertidal sediments under cold climate is an urgent issue. Although the bioavailability of petroleum hydrocarbons decreases at low temperatures, biosurfactants can promote oil biodegradation. In this study, characteristics of biosurfactants produced by cold-adapted oil-degrading bacteria Planococcus sp. XW-1 were studied. Adding the XW-1 biosurfactant could effectively facilitate the solubility of phenanthrene, pyrene, diesel oil, and crude oil. The solubilization was limited by the number of rings and the molecular weight (WSRphenanthrene = 0.0234; WSRpyrene = 0.0165; WSRdiesel oil = 0.0027; WSRcrude oil = 0.0015). Additional biosurfactants significantly washed out crude oil adsorbed to the sand (reduction from 17.1%, 22.7% to 87.9% and 94.28% in 24 h). With the increase in particle size, the removal efficiency increased from 87.9% to 94.28%. After the addition of biosurfactant, the effect of degradation increased by 20% in 20 days. The results suggest that the biosurfactant-producing bacteria Planococcus sp. XW-1 is a promising candidate used in the in situ bioremediation of petroleum-contaminated intertidal sediment.

PdeHCA2 affects biomass in Populus by regulating plant architecture, the transition from primary to secondary growth, and photosynthesis - Biligen-Gaowa Zhao; Guo Li; Yue-Feng Wang; Zhen Yan; Feng-Qin Dong; Ying-Chang Mei; Wei Zeng; Meng-Zhu Lu; Hong-Bin Li; Qing Chao; Bai-Chen Wang (Planta, 2022)

A scientometric analysis of agricultural pollution by using bibliometric software VoSViewer and Histcite™ - Bin Li; Kai Hu; Vladimir Lysenko; Kiran Yasmin Khan; Yingkuan Wang; Yongnian Jiang; Ya Guo (Environmental Science and Pollution Research, 2022)

Isolation and characterization of 112 SNP markers in Yellowfin seabream (Acanthopagrus latus) using RAD sequencing - Ke-Cheng Zhu; Ya-Ling Li; Wei-Bin Wu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Liang Guo; Dian-Chang Zhang (Conservation Genetics Resources, 2022)

An overview on plasticized biodegradable corn starch-based films: the physicochemical properties and gelatinization process - Bin Wang; Bin Yu; Chao Yuan; Li Guo; Pengfei Liu; Wei Gao; Dapeng Li; Bo Cui; A. M. Abd El-Aty (Critical Reviews in Food Science and Nutrition, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Dihydroartemisinin ameliorates chronic nonbacterial prostatitis and epithelial cellular inflammation by blocking the E2F7/HIF1α pathway - Yan Zhou; Jun-hao Wang; Jian-peng Han; Jian-yong Feng; Kuo Guo; Fei Du; Wen-bin Chen; Yong-zhang Li (Inflammation Research, 2022)

Carbon consumption and regeneration of oxygen-containing functional groups on activated carbon for flue gas purification - Yuran Li; Yuting Lin; Junxiang Guo; Zhicheng Xu; Bin Wang; Tingyu Zhu (Environmental Science and Pollution Research, 2022)

Modular-level alterations of single-subject gray matter networks in schizophrenia - Yuxiang Guo; Yunxiao Ma; GongShu Wang; Ting Li; Tong Wang; Dandan Li; Jie Xiang; Tianyi Yan; Bin Wang; Miaomiao Liu (Brain Imaging and Behavior, 2022)

Load transfer laws of tensile anchors in rock masses with weak interlayers based on a shear-slipping updating model - Yan Wang; Xin Xiang; Chang-dong Li; Guo-qiang Zhu; Cheng-bin Song; Jin-ye Xian; Jia-jun Zhang (Journal of Mountain Science, 2022)

Characterization of Grinding-Induced Subvisible Particles and Free Radicals in a Freeze-Dried Monoclonal Antibody Formulation - Zhen-Yi Jing; Guo-Li Huo; Min-Fei Sun; Bin-Bin Shen; Wei-Jie Fang (Pharmaceutical Research, 2022)

Selenium Deficiency Causes Inflammatory Injury in the Bursa of Fabricius of Broiler Chickens by Activating the Toll-like Receptor Signaling Pathway - Yu Bai; Ruili Zhang; Qing Liu; Rong Guo; Guangxing Li; Bin Sun; Di Zhang; Yang Chen; Xiaodan Huang (Biological Trace Element Research, 2022)

Mesenchymal-to-epithelial transition of osteoblasts induced by Fam20c knockout - Ya-Wei Geng; Zhen Zhang; Han Jin; Jun-Long Da; Kai Zhang; Jian-Qun Wang; Yu-Yao Guo; Bin Zhang; Ying Li (Genes & Genomics, 2022)

Fabrication of Stable Apigenin Nanosuspension with PEG 400 as Antisolvent for Enhancing the Solubility and Bioavailability - Renjie Xu; Cuiping Jiang; Lijing Zhou; Bin Li; Yi Hu; Yujie Guo; Xuecheng Xiao; Shan Lu (AAPS PharmSciTech, 2022)

Genetic dissection of QTLs linked with seedling, yield and fiber quality traits of upland cotton under salt stress field conditions - Ying Su; Shiwei Geng; Anhui Guo; Babar Ijaz; Bin Li; Qin Chen; Kai Zheng; Quanjia Chen; Jinping Hua (Euphytica, 2021)

Immersion immunization of common carp with bacterial ghost‐based DNA vaccine inducing prophylactic protective immunity against spring viraemia of carp virus - Yu‐Ying Zheng; Chen Zhang; Yang Li; Peng‐Qi Zhang; Guo Chen; Gao‐Xue Wang; Bin Zhu (Journal of Fish Diseases, 2021)
The interactive applications of immunization route, vaccine type and delivery vectors are emerging as a key area of research within the field of mass immunization in fishery production. In an effort to improve DNA vaccine's immune efficiency in large‐scale immunization, a promising bacterial ghost‐loaded DNA vaccine was constructed based on Escherichia coli DH5α. In common carp was investigated the immune response to immersion immunization via related indicator analysis, and the challenge test of spring viraemia of carp virus (SVCV) was carried out. The result indicated that BG‐loaded DNA vaccine induced higher serum antibody level than naked pEG‐G. Simultaneously, the immunophysiological indicators and genes change at the more advanced levels in the BG/pEG‐G immune group. At the treatment concentration of 20 mg/L of the BG/pEG‐G group, IgM and IgZ expressions in vivo were markedly increased by 21.62 times and 6.91 times, respectively, and the relative percentage survival reached the peak of 59.57%. This study paves the way for future aquatic animal vaccine research, which aimed to develop the highly effective immersion vaccine system by delivery vectors, with the ultimate aim to prevent and restrict SVCV in actual production.

Optimization of immunization procedure for SWCNTs‐based subunit vaccine with mannose modification against spring viraemia of carp virus in common carp - Yu‐Ming Gong; Chen Zhang; Yang Li; Guo Chen; Gao‐Xue Wang; Bin Zhu (Journal of Fish Diseases, 2021)
Immersion vaccination of single‐walled carbon nanotubes loaded with mannose‐modified glycoprotein (SWCNTs‐MG) vaccine has been proved to be effective in preventing spring viraemia of carp virus (SVCV). Immunization procedure has immense consequence on the immune effect of the immersion vaccine. However, immunization procedure optimization for SWCNTs‐MG vaccine against SVCV has not been reported. In this study, accordingly, a full‐factor experiment was designed to optimize the immunization procedure of SWCNTs‐MG vaccine by three aspects of vaccine dose (30 mg/L, 40 mg/L and 50 mg/L), immunization density (8 fish L −1 , 24 fish L −1 and 48 fish L −1 ) and immunization time (6, 12 and 24 hr). Furthermore, we used the immunization group (A1B2C1, 30 mg/L, 24 fish L −1 and 6 hr) in the previous study as a positive control (PC) to evaluate the immunization effect optimized conditions from the expression of immune‐related genes and relative percentage survival (RPS). At 28 days post‐vaccination (DPV), common carps were intraperitoneal injected SVCV challenged test indicated that the A1B2C2 group (30 mg/L, 24 fish L −1 , 12 hr) displayed superiority of protective efficacy compare with other groups and the RPS with 77.9%, which was 15.6% higher than the PC group of RPS with 62.3%. Moreover, the expression of immune‐related genes such as IL‐10 , CD4 and MHC‐II was also significantly higher than PC group. The specific experimental flow chart is shown in Figure 1 . Conclusively, these results demonstrated that vaccine dose, immunization density and immunization time are 30 mg/L, 24 fish L −1 and 12 hr, which is the more appropriate immunization programme with juvenile carp for SWCNTs‐MG vaccine. This study provides a profitable reference for improving the immune efficiency of aquatic immersion vaccine. The experiment process and timeline chart of the present research image

Dynamically monitoring cellular γ-H2AX reveals the potential of carcinogenicity evaluation for genotoxic compounds - Minmin Qu; Hua Xu; Wuju Li; Jia Chen; Yajiao Zhang; Bin Xu; Zhi Li; Tao Liu; Lei Guo; Jianwei Xie (Archives of Toxicology, 2021)

Degradation of wetlands on the Qinghai-Tibetan Plateau causing a loss in soil organic carbon in 1966–2016 - Hailing Li; Tingting Li; Wenjuan Sun; Wen Zhang; Qing Zhang; Lijun Yu; Zhangcai Qin; Bin Guo; Jia Liu; Xingchu Zha (Plant and Soil, 2021)

Study on synthesis and anticancer activity of 17beta-estradiol-phenol/aniline nitrogen mustard derivatives - Yu-dong Yin; Jing-jing Liu; Wen-fei Liao; Xian-kun Guo; Li-shan Zhang; Wei-bin Mo; Ke-guang Cheng (Medicinal Chemistry Research, 2021)

Effects of α-linolenic acid intake on blood lipid profiles：a systematic review and meta-analysis of randomized controlled trials - Hao Yue; Bin Qiu; Min Jia; Wei Liu; Xiao-fei Guo; Na Li; Zhi-xiang Xu; Fang-ling Du; Tongcheng Xu; Duo Li (Critical Reviews in Food Science and Nutrition, 2021)

Sum of High-Risk Gene Mutation (SHGM): A Novel Attempt to Assist Differential Diagnosis for Adrenocortical Carcinoma with Benign Adenoma, Based on Detection of Mutations of Nine Target Genes - Guo-Yang Zheng; Xue-Bin Zhang; Han-Zhong Li; Yu-Shi Zhang; Jian-Hua Deng; Xing-Cheng Wu (Biochemical Genetics, 2021)
There has been no research on applying gene detection to differential diagnosis of adrenocortical carcinoma (ACC). We attempted to explore a novel auxiliary method for differential diagnosis between ACC with benign adrenocortical adenoma (ACA), based on mutations of target genes in tissues. Nine genes were chosen as target genes, including TP53, CTNNB1, ARMC5, PRKAR1A, ZNRF3, RB1, APC, MEN1, and RPL22 . Exons sequencing of target genes were performed in 98 cases of tissue samples by FastTarget technology, including 41 ACC tissues, 32 ACA tissues, and 25 normal adrenal gland tissues. Significant mutations were detected and identified, and the clinical information was collected, for further comparative analysis and application to assist differential diagnosis of ACC. We identified 132 significant gene mutations and 227 significant mutation sites in 37 ACC tissues, much more than ACA and normal adrenal gland tissues. Mutation rates of 6 genes in ACC tissues were obviously higher than ACA tissues, including ZNRF3, ARMC5, TP53, APC, RB1, and PRKAR1A , regarded as high-risk genes. The sum of mutated high-risk genes detected in each sample was denominated sum of high-risk gene mutation (SHGM), and the rates of SHGM > 0 and SHGM > 1 in ACC tissues were 73.0% and 62.2%, respectively, both obviously higher than those in ACA tissues, with significant statistic differences. Especially for 8 cases of ACC with diameter 0 and SHGM > 1 were found in 6 samples (75%) and 4 samples (50%), respectively. However, no relevance was found between SHGM and clinical characteristics of ACC. We identified 6 high-risk genes in ACC tissues, with significantly higher mutation rates than ACA or normal adrenal gland tissues. The sum of mutated high-risk genes detected in ACC tissues was denominated SHGM, which was potential to assist the differential diagnosis of ACC with ACA, especially for the small-size ACC.

Metagenomic insights into the metabolism and evolution of a new Thermoplasmata order ( Candidatus Gimiplasmatales) - Wenzhe Hu; Jie Pan; Bin Wang; Jun Guo; Meng Li; Meiying Xu (Environmental Microbiology, 2021)
Summary Thermoplasmata is a widely distributed and ecologically important archaeal class in the phylum Euryarchaeota. Because few cultures and genomes are available, uncharacterized Thermoplasmata metabolisms remain unexplored. In this study, we obtained four medium‐ to high‐quality archaeal metagenome‐assembled genomes (MAGs) from the filamentous fragments of black‐odorous aquatic sediments (Foshan, Guangdong, China). Based on their 16S rRNA gene and ribosomal protein phylogenies, the four MAGs belong to the previously unnamed Thermoplasmata UBA10834 clade. We propose that this clade (five reference genomes from the Genome Taxonomy Database (GTDB) and four MAGs from this study) be considered a new order, Candidatus Gimiplasmatales. Metabolic pathway reconstructions indicated that the Ca . Gimiplasmatales MAGs can biosynthesize isoprenoids and nucleotides de novo . Additionally, some taxa have genes for formaldehyde and acetate assimilation, and the Wood–Ljungdahl CO 2 ‐fixation pathway, indicating a mixotrophic lifestyle. Sulfur reduction, hydrogen metabolism, and arsenic detoxification pathways were predicted, indicating sulfur‐, hydrogen‐, and arsenic‐transformation potentials. Comparative genomics indicated that the H 4 F Wood–Ljungdahl pathway of both Ca . Gimiplasmatales and Methanomassiliicoccales was likely obtained by the interdomain lateral gene transfer from the Firmicutes. Collectively, this study elucidates the taxonomic and potential metabolic diversity of the new order Ca . Gimiplasmatales and the evolution of this subgroup and its sister lineage Methanomassiliicoccales.

Soil fertility, enzyme activity, and microbial community structure diversity among different soil textures under different land use types in coastal saline soil - Yun Zhu; Bin Guo; Chen Liu; Yicheng Lin; Qinglin Fu; Ningyu Li; Hua Li (Journal of Soils and Sediments, 2021)

Supercooling capacity and cold tolerance of the South American tomato pinworm, Tuta absoluta, a newly invaded pest in China - Xiao-wei Li; Dong Li; Zhi-jun Zhang; Jun Huang; Jin-ming Zhang; Muhammad Hafeez; Li-kun Wang; Wen-chao Guo; Yao-bin Lu (Journal of Pest Science, 2021)
Tuta absoluta is a devastating invasive pest worldwide, causing severe damage to the global tomato industry. It has been recorded recently in the northwestern border areas of China, posing a significant threat to tomato production. It was presumed that the region's winter-related low temperatures would avert the alien species from successfully overwintering. In this study, the supercooling capacity and low-temperature tolerance of this pest were examined under laboratory conditions and its overwintering potential in Xinjiang was estimated. The results showed that the lowest supercooling point was recorded in the adult stage (− 19.47 °C), while the highest (− 18.11 °C) was recorded in the pupal stage. The supercooling points of pupae and adults were not influenced by gender. The Ltemp 50 and Ltemp 90 of female and male adults were the lowest when exposed to cold for 2 h. However, when the duration of exposure extended from 4 to 10 h, the Ltemp 50 and Ltemp 90 of female and male pupae were the lowest. Comparison of the lowest Ltemp 50 and Ltemp 90 with temperatures in January indicated that T. absoluta might not be able to overwinter in most of the northern and central regions of Xinjiang. However, in the southern regions, the extremely low temperature was higher than the Ltemp 90 , suggesting that T. absoluta has a higher overwintering potential in these regions. These results form a basis for predicting the dispersal potential and possible geographic range of this pest in Xinjiang. In addition, our findings provide guidance for the control of this pest by reducing overwintering shelters.

Adaptive Evolution of Chalcone Isomerase Superfamily in Fagaceae - Li-Mei Lin; Hong-Yu Guo; Xin Song; Duo-Duo Zhang; Yue-Hong Long; Zhao-Bin Xing (Biochemical Genetics, 2021)

Initial ingestion of CMV-infected plants reduces subsequent aphid performance - Xiao-bin Shi; Jun Deng; Zhuo Zhang; Shuo Yan; Li-min Zheng; Shu-e Sun; Yang Gao; Xu-guo Zhou; De-yong Zhang; Yong Liu (Arthropod-Plant Interactions, 2021)

Moderate oxidative stress promotes epithelial–mesenchymal transition in the lens epithelial cells via the TGF-β/Smad and Wnt/β-catenin pathways - Xi Chen; Hong Yan; Ying Chen; Guo Li; Yue Bin; Xiyuan Zhou (Molecular and Cellular Biochemistry, 2021)

Dysfunction of chaperone-mediated autophagy in human diseases - Zhaozhong Liao; Bin Wang; Wenjing Liu; Qian Xu; Lin Hou; Jinlian Song; Qingming Guo; Ning Li (Molecular and Cellular Biochemistry, 2021)

Influence of the roots of mixed-planting species on the shear strength of saline loess soil - Ya-bin Liu; Xia-song Hu; Dong-mei Yu; Hai-li Zhu; Guo-rong Li (Journal of Mountain Science, 2021)

TMEM166 inhibits cell proliferation, migration and invasion in hepatocellular carcinoma via upregulating TP53 - Jiejie Yang; Bin Wang; Qian Xu; Yuling Yang; Lin Hou; Kan Yin; Qingming Guo; Yanan Hua; Li Zhang; Yixuan Li; Jinyu Zhang; Ning Li (Molecular and Cellular Biochemistry, 2021)

Selenium Deficiency via the TLR4/TRIF/NF-κB Signaling Pathway Leading to Inflammatory Injury in Chicken Spleen - Ruili Zhang; Rong Guo; Qing Liu; Guangxing Li; Bin Sun; Xiaodan Huang (Biological Trace Element Research, 2021)

Deepened snow cover alters biotic and abiotic controls on nitrogen loss during non-growing season in temperate grasslands - Zhou Jia; Ping Li; Yuntao Wu; Sen Yang; Chengzhang Wang; Bin Wang; Lu Yang; Xin Wang; Jing Li; Ziyang Peng; Lulu Guo; Weixing Liu; et al. (Biology and Fertility of Soils, 2021)

Overexpression of miR319 in petunia (Petunia × hybrida) promotes de novo shoot organogenesis from leaf explants - Yulong Guo; Xiaoting Qin; Bin Zhang; Xiaojing Xu; Zhineng Li; Mingyang Li (In Vitro Cellular & Developmental Biology - Plant, 2021)

Advances in intervention methods and brain protection mechanisms of in situ and remote ischemic postconditioning - Chun-Yan Li; Wei Ma; Kuang-Pin Liu; Jin-Wei Yang; Xian-Bin Wang; Zhen Wu; Tong Zhang; Jia-Wei Wang; Wei Liu; Jie Liu; Yu Liang; Xing-Kui Zhang; et al. (Metabolic Brain Disease, 2021)

A unique porin meditates iron‐selective transport through cyanobacterial outer membranes - Guo‐Wei Qiu; Hai‐Bo Jiang; Hagar Lis; Zheng‐Ke Li; Bin Deng; Jin‐Long Shang; Chuan‐Yu Sun; Nir Keren; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Cyanobacteria are globally important primary producers and nitrogen fixers with high iron demands. Low ambient dissolved iron concentrations in many aquatic environments mean that these organisms must maintain sufficient and selective transport of iron into the cell. However, the nature of iron transport pathways through the cyanobacterial outer membrane remains obscure. Here we present multiple lines of experimental evidence that collectively support the existence of a novel class of substrate‐selective iron porin, Slr1908, in the outer membrane of the cyanobacterium Synechocystis sp. PCC 6803. Elemental composition analysis and short‐term iron uptake assays with mutants in Slr1908 reveal that this protein is primarily involved in inorganic iron uptake and contributes less to the accumulation of other metals. Homologues of Slr1908 are widely distributed in both freshwater and marine cyanobacteria, most notably in unicellular marine diazotrophs. Complementary experiments with a homologue of Slr1908 in Synechococcus sp. PCC 7002 restored the phenotype of Synechocystis knockdown mutants, showing that this siderophore producing species also possesses a porin with a similar function in Fe transport. The involvement of a substrate‐selective porins in iron uptake may allow cyanobacteria to tightly control iron flux into the cell, particularly in environments where iron concentrations fluctuate.

Dermatologists may need to pay more attention to herpes zoster during the pandemic of COVID-19 - Bin Wang; Shujing Guo; Yue Yao; Yanjia Li; Guoqiang Zhang (Infectious Diseases, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Effect of various doses of 3,4-dimethylpyrazole phosphate on mineral nitrogen losses in two paddy soils - Hua Li; Xiaodong Chen; Chen Liu; Shaoxian Wang; Bin Guo; Ningyu Li; Yuequn Jin; Qinglin Fu; Xinqiang Liang (Journal of Soils and Sediments, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Voxel-based morphometry analysis and machine learning based classification in pediatric mesial temporal lobe epilepsy with hippocampal sclerosis - Shihui Chen; Jian Zhang; Xiaolei Ruan; Kan Deng; Jianing Zhang; Dongfang Zou; Xiaoming He; Feng Li; Guo Bin; Hongwu Zeng; Bingsheng Huang (Brain Imaging and Behavior, 2020)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Macrophage–NLRP3 Inflammasome Activation Exacerbates Cardiac Dysfunction after Ischemic Stroke in a Mouse Model of Diabetes - Hong-Bin Lin; Guan-Shan Wei; Feng-Xian Li; Wen-Jing Guo; Pu Hong; Ya-Qian Weng; Qian-Qian Zhang; Shi-Yuan Xu; Wen-Bin Liang; Zhi-Jian You; Hong-Fei Zhang (Neuroscience Bulletin, 2020)

Drug Elimination Alteration in Acute Lymphoblastic Leukemia Mediated by Renal Transporters and Glomerular Filtration - Yue Zhou; Bin Du; Min Kan; Shang Chen; Bo-Hao Tang; Ai-Qing Nie; Pan-Pan Ye; Hai-Yan Shi; Guo-Xiang Hao; Xiu-Li Guo; Qiu-Ju Han; Yi Zheng; et al. (Pharmaceutical Research, 2020)

Duration of SARS-CoV-2 viral shedding during COVID-19 infection - Guo-Qing Qian; Xue-Qin Chen; Ding-Feng Lv; Ada Hoi Yan Ma; Li-Ping Wang; Nai-Bin Yang; Xiao-Min Chen (Infectious Diseases, 2020)

Correction to: Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)

A flagellin-adjuvanted inactivated porcine epidemic diarrhea virus (PEDV) vaccine provides enhanced immune protection against PEDV challenge in piglets - Xiangwei Xu; Luping Du; Baochao Fan; Bing Sun; Jinzhu Zhou; Rongli Guo; Zhengyu Yu; Danyi Shi; Kongwang He; Bin Li (Archives of Virology, 2020)

Soluble receptor for advanced glycation end-products promotes angiogenesis through activation of STAT3 in myocardial ischemia/reperfusion injury - Xianxian Cao; Bin Li; Xuejie Han; Xiuling Zhang; Mengqiu Dang; Hongxia Wang; Fenghe Du; Xiangjun Zeng; Caixia Guo (Apoptosis, 2020)

Effects and mechanisms of tea for the prevention and management of cancers: An updated review - Xiao-Yu Xu; Cai-Ning Zhao; Shi-Yu Cao; Guo-Yi Tang; Ren-You Gan; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2020)

Phylogenetic patterns of shrub communities along the longitudinal and latitudinal gradients on the northeastern Qinghai–Tibetan Plateau - Yuan-ming Xiao; Lu-cun Yang; Xiu-qing Nie; Chang-bin Li; Feng Xiong; Guo-ying Zhou (Journal of Mountain Science, 2020)

Tenuazonic acid-induced change in volatile emission from rose plants and its chemometrical analysis - Fa-zhong Yang; Yun-xian Li; Min Tang; Guo-lei Zhu; Shi-ping Zhou; Bin Yang (Journal of Plant Diseases and Protection, 2020)

Dynamic change of vegetation and its response to climate and topographic factors in the Xijiang River basin, China - Lu Jia; Zhan-bin Li; Guo-ce Xu; Zong-ping Ren; Peng Li; Yu-ting Cheng; Yi-xin Zhang; Bin Wang; Jia-xin Zhang; Shu Yu (Environmental Science and Pollution Research, 2020)

Study on visual control system of acoustic in situ measurement technology for survey of seafloor sediment - Bin Lv; Guo-liang Qi; Guan-bao Li; Guang-ming Kan; Jing-qiang Wang; Jie Liu (Marine Georesources & Geotechnology, 2020)

Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)
Simulated microgravity can significantly affect various cell types and multiple systems of the human body, such as cardiovascular system, skeletal muscle system, and immune system, and is known to cause anemia and loss of electrolyte and fluids. Epidermal stem cells (EpSCs) were cultured in a rotary cell culture system (RCCS) bioreactor to simulate microgravity. The metabolites of EpSCs were identified by liquid chromatography-mass spectrometry (LC-MS). Compared with normal gravity (NG) group, a total of 57 different metabolites of EpSCs were identified ( P < 0.05, VIP > 1), including lipids and lipid-like molecules (51 molecules), amino acids (5 molecules), nucleosides, nucleotides, and analogues (1 molecule). According to the partial least squares discriminant analysis (PLS-DA) score plot, a VIP > 1 and P < 0.05 were obtained for the 57 different metabolites, of which 23 molecules were significantly downregulated and 34 were significantly upregulated in simulated microgravity (SMG) group. These results showed that SMG has a significant impact on different pathways, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that multiple pathways were involved, mainly the amino acid metabolism pathway, lipid metabolism pathway, membrane transport pathway, and cell growth and death pathways. Thus, the metabolic profile of EpSCs was changed under SMG. Exploring the metabolic profile of EpSCs would be helpful to further understand the growth characteristics of EpSCs under SMG, which will provide a new approach to explore the metabolomics mechanism of stress injury and repair trauma under SMG.

Review of Cystic Echinococcosis in Nigeria: A Story of Neglect - John Asekhaen Ohiolei; Hong-Bin Yan; Li Li; Guo-Qiang Zhu; Rosline James Muku; Yan-Tao Wu; Wan-Zhong Jia (Acta Parasitologica, 2020)

Carbon consumption mechanism of activated coke in the presence of water vapor - Junxiang Guo; Yuran Li; Bin Wang; Tingyu Zhu (Environmental Science and Pollution Research, 2020)

Classification of tight sandstone reservoirs based on NMR logging - Chang-Xi Li; Mi Liu; Bin-Cheng Guo (Applied Geophysics, 2019)

Effects of micrite microtextures on the elastic and petrophysical properties of carbonate reservoirs - Jian-Guo Pan; Ji-Xin Deng; Chuang Li; Hong-Bin Wang; Hu-Quan Zhang; Jian-Guo Zhao; Gen-Yang Tang (Applied Geophysics, 2019)

A Novel Event Detection Model for Water Distribution Systems Based on Data-Driven Estimation and Support Vector Machine Classification - Xiang-Yun Zou; Yi-Li Lin; Bin Xu; Zi-Bo Guo; Sheng-Ji Xia; Tian-Yang Zhang; An-Qi Wang; Nai-Yun Gao (Water Resources Management, 2019)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

Characterization of the complete chloroplast genome of Euryodendron excelsum (Pentaphylacaceae), a critically endangered species endemic to China - Xiang-gang Shi; Wei-xi Li; Fen Xing; Yu-bin Zhou; Wu-xia Guo; Ye-lin Huang (Conservation Genetics Resources, 2019)

Uncommon Peptide Bond Cleavage of Glucagon from a Specific Vendor under near Neutral to Basic Conditions - Hong-Jian Zheng; Bin-Bin Shen; Jing Wang; Haibin Wang; Guo-Li Huo; Li-Rui Huang; Jian-Qing Gao; Wei-Jie Fang (Pharmaceutical Research, 2019)

Development of grouting materials with application to the protection of the geological relics of the Weng’an Biota - Sheng Wang; Zhi-hong Shu; Kai-bin Guo; Li-ming Jian; Li-yi Chen (Journal of Mountain Science, 2019)

Effects of perinatal dioxin exposure on development of children: a 3-year follow-up study of China cohort - Zheng Wang; Jin Guo Hang; Hao Feng; Li Li Shi; Jing Jian Dong; Bin Shen; Ting Luo; Ren Mei Cai; Ling Jie Shen; Teruhiko Kido; Xian Liang Sun (Environmental Science and Pollution Research, 2019)

Comparative genomic and phylogenetic analyses of Populus section Leuce using complete chloroplast genome sequences - Kai Gao; Juan Li; Wasif Ullah Khan; Tianyun Zhao; Xiong Yang; Xiaoyu Yang; Bin Guo; Xinmin An (Tree Genetics & Genomes, 2019)

Cloning, Expression and Characterization of a Highly Active Alcohol Dehydrogenase for Production of Ethyl (S)-4-Chloro-3-Hydroxybutyrate - Yi-Hao Zhu; Cai-Yun Liu; Sha Cai; Li-Bin Guo; In-Won Kim; Vipin C. Kalia; Jung-Kul Lee; Ye-Wang Zhang (Indian Journal of Microbiology, 2019)

The sedimentary record of polycyclic aromatic hydrocarbons in Yamzho Yumco Lake: evolution of local sources and adsorption dynamic in the Tibetan Plateau - Qi Wang; Jun Li; Xu-Chuan Duan; Guo-Li Yuan; Bin Fang; An-Ting Wang (Environmental Science and Pollution Research, 2019)

Length-Weight Relationship and Population Dynamics of Bombay Duck (Harpadon nehereus) in the Min River Estuary, East China Sea - Xiongbo He; Jun Li; Chen Shen; Yan Shi; Chen Feng; Junhong Guo; Yunrong Yan; Bin Kang (Thalassas: An International Journal of Marine Sciences, 2019)

Mitochondrial superoxide anions induced by exogenous oxidative stress determine tumor cell fate: an individual cell-based study - Hui Pan; Bao-hui Wang; Zhou-bin Li; Xing-guo Gong; Yong Qin; Yan Jiang; Wei-li Han (Journal of Zhejiang University-SCIENCE B, 2019)

Modelling and analysis of net primary productivity and its response mechanism to climate factors in temperate grassland, northern China - Fen Zhao; Bin Xu; Xiuchun Yang; Lang Xia; Yunxiang Jin; Jinya Li; Wenbo Zhang; Jian Guo; Ge Shen (International Journal of Remote Sensing, 2019)

A new triterpene diglycoside from the roots of Bupleurum chinense DC. and its inhibitory effect on adipogensis in 3T3-L1 cells - Yujing Feng; Zhou-Wei Wu; Yanyan Luo; Liang Chen; Yufeng Cao; Lun Wang; Aftab Yaseen; Bin Chen; Ashfaq Ahmad Khan; Ming-Kui Wang; Guo-Lin Zhang; Xin-Feng Wang; et al. (Medicinal Chemistry Research, 2019)

Are glutamate transporters neuroprotective or neurodegenerative during cerebral ischemia? - Li-Nan Zhang; Liang Hao; Yu-Song Guo; Hai-Yan Wang; Lin-lin Li; Li-Zhe Liu; Wen-Bin Li (Journal of Molecular Medicine, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Antibacterial activity and mechanism of ThDP analogs against rice brown stripe pathogen Acidovorax avenae subsp. avenae RS-1 - Xiao Xuan Wang; Hang Ying Qi; Jie Chen; Ying Zi Yang; Wen Qiu; Wei Wang; Peng Zou; Bin Li; Yan Li Wang; Hong Wu He; Guo Chang Sun (Journal of Plant Pathology, 2019)

Producing more grain yield of rice with less ammonia volatilization and greenhouse gases emission using slow/controlled-release urea - Chen Guo; Tao Ren; Pengfei Li; Bin Wang; Jialong Zou; Saddam Hussain; Rihuan Cong; Lishu Wu; Jianwei Lu; Xiaokun Li (Environmental Science and Pollution Research, 2019)

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

Uneven winter snow influence on tree growth across temperate China - Xiuchen Wu; Xiaoyan Li; Hongyan Liu; Philippe Ciais; Yuanqiao Li; Chongyang Xu; Flurin Babst; Weichao Guo; Bingyan Hao; Pei Wang; Yongmei Huang; Shaomin Liu; et al. (Global Change Biology, 2019)
Winter snow is an important driver of tree growth in regions where growing‐season precipitation is limited. However, observational evidence of this influence at larger spatial scales and across diverse bioclimatic regions is lacking. Here, we investigated the interannual effects of winter (here defined as previous October to current February) snow depth on tree growth across temperate China over the period of 1961–2015, using a regional network of tree ring records, in situ daily snow depth observations, and gridded climate data. We report uneven effects of winter snow depth on subsequent growing‐season tree growth across temperate China. There shows little effect on tree growth in drier regions that we attribute mainly to limited snow accumulation during winter. By contrast, winter snow exerts important positive influence on tree growth in stands with high winter snow accumulation (e.g., in parts of cold arid regions). The magnitude of this effect depends on the proportion of winter snow to pre‐growing‐season (previous October to current April) precipitation. We further observed that tree growth in drier regions tends to be increasingly limited by warmer growing‐season temperature and early growing‐season water availability. No compensatory effect of winter snow on the intensifying drought limitation of tree growth was observed across temperate China. Our findings point toward an increase in drought vulnerability of temperate forests in a warming climate.

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

BMAL1 regulates balance of osteogenic–osteoclastic function of bone marrow mesenchymal stem cells in type 2 diabetes mellitus through the NF-κB pathway - Xiaoguang Li; Na Liu; Bin Gu; Wei Hu; Ying Li; Bin Guo; Dongsheng Zhang (Molecular Biology Reports, 2018)

Correlation of PICALM polymorphism rs3851179 with Alzheimer’s disease among Caucasian and Chinese populations: a meta-analysis and systematic review - Bin Zhu; Li-Xia Li; Lei Zhang; Shu Yang; Yue Tian; Shan-Shan Guo; Wei Zhang; Zhi-Gang Zhao (Metabolic Brain Disease, 2018)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Synthesis and Application of Water-Soluble Oxazine Dyes for Detection of PHAs-Producing Bacteria - Qing-Hao Liu; Jin-Chun Guo; Hong-Yu Lu; Yan-Nan Guo; Hai-Bin Wang; Zhi-Yong Hu; Hong-Yan Liu; Dong-Liang; Li-Gong Chen (Journal of Fluorescence, 2018)

Comparative genomics analysis reveals gene family expansion and changes of expression patterns associated with natural adaptations of flowering time and secondary metabolism in yellow Camellia - Xinlei Li; Zhengqi Fan; Haobo Guo; Ning Ye; Tao Lyu; Wen Yang; Jie Wang; Jia-Tong Wang; Bin Wu; Jiyuan Li; Hengfu Yin (Functional & Integrative Genomics, 2018)

A pair of enantiomeric 5-oxabicyclic[4.3.0]lactam derivatives and one new polyketide from the marine-derived fungus Penicillium griseofulvum - Jian-Kun Yang; Bin Zhang; Tong Gao; Meng-Yue Yang; Guo-Zheng Zhao; Hua-Jie Zhu; Li Liu; Fei Cao (Natural Product Research, 2018)

Methylation of Cdkn1c may be involved in the regulation of tooth development through cell cycle inhibition - Qiulan Li; Yue Guo; Mianfeng Yao; Jun Li; Yingyi Chen; Qiong Liu; Yun Chen; Yuanyuan Zeng; Bin Ji; Yunzhi Feng (Journal of Molecular Histology, 2018)

Development of the nano-composite cement: Application in regulating grouting in complex ground conditions - Sheng Wang; Jing-fei Wang; Chao-peng Yuan; Li-yi Chen; Shi-tong Xu; Kai-bin Guo (Journal of Mountain Science, 2018)

Aneuploidization under segmental allotetraploidy in rice and its phenotypic manifestation - Ying Wu; Yue Sun; Shuai Sun; Guo Li; Jie Wang; Bin Wang; Xiuyun Lin; Meng Huang; Zhiyun Gong; Karen A. Sanguinet; Zhiwu Zhang; Bao Liu (Theoretical and Applied Genetics, 2018)

On the initiation, movement and deposition of a large landslide in Maoxian County, China - Xiang-jun Pei; Bin Guo; Sheng-hua Cui; Dong-po Wang; Qiang Xu; Tian-tao Li (Journal of Mountain Science, 2018)

Postnatal Subacute Benzo(a)Pyrene Exposure Caused Neurobehavioral Impairment and Metabolomic Changes of Cerebellum in the Early Adulthood Period of Sprague-Dawley Rats - Chunlin Li; Jing Wang; Qiuping Su; Kai Yang; Chengzhi Chen; XueJun Jiang; Tingli Han; Shuqun Cheng; Tingting Mo; Ruiyuan Zhang; Bin Peng; Yuming Guo; et al. (Neurotoxicity Research, 2018)

Estimating aboveground biomass using Pléiades satellite image in a karst watershed of Guizhou Province, Southwestern China - Yin-ming Guo; Jian Ni; Li-bin Liu; Yang-yang Wu; Chun-zi Guo; Xin Xu; Qiao-lian Zhong (Journal of Mountain Science, 2018)

In Situ Observation of Hard Surrounding Rock Displacement at 2400-m-Deep Tunnels - Xia-Ting Feng; Zhi-Bin Yao; Shao-Jun Li; Shi-Yong Wu; Cheng-Xiang Yang; Hao-Sen Guo; Shan Zhong (Rock Mechanics and Rock Engineering, 2018)

Aboveground biomass of the alpine shrub ecosystems in Three-River Source Region of the Tibetan Plateau - Xiu-qing Nie; Lu-cun Yang; Feng Xiong; Chang-bin Li; Li Fan; Guo-ying Zhou (Journal of Mountain Science, 2018)

Midazolam prevents motor neuronal death from oxidative stress attack mediated by JNK-ERK pathway - Guo-zheng Li; Hong-Lei Tao; Cheng Zhou; Dong-dong Wang; Cong-bin Peng (Human Cell, 2018)

Genome sequencing and phylogenetic analysis of Banna virus (genus Seadornavirus, family Reoviridae) isolated from Culicoides - Song Song; Yuanyuan Li; Shihong Fu; Wenwen Lei; Xiaofang Guo; Yun Feng; Xiaoyan Gao; Xiaolong Li; Zhonghua Yang; Ziqian Xu; Ying He; Huanyu Wang; et al. (Science China Life Sciences, 2017)

Protective effect of proanthocyanidin on mice Sertoli cell apoptosis induced by zearalenone via the Nrf2/ARE signalling pathway - Miao Long; Shu-Hua Yang; Wei Shi; Peng Li; Yang Guo; Jiayi Guo; Jian-Bin He; Yi Zhang (Environmental Science and Pollution Research, 2017)

Temperature effects on the mechanical properties of slates in triaxial compression test - Lu-bo Meng; Tian-bin Li; Guo-jun Cai (Journal of Mountain Science, 2017)

Two new cadinane-type sesquiterpenes from cultures of the basidiomycete Trichaptum pargamenum - Bin Tang; Xi Du; Han-An Long; Jun Du; Jian-Min Guo; Xin Hu; Hua Tu; Li Yang; Hong-Jin Liu (Natural Product Research, 2017)

Inland Fisheries in China: Past, Present, and Future - Bin Kang; Xiaoxia Huang; Jun Li; Min Liu; Longgen Guo; Chiao-Chuan Han (Reviews in Fisheries Science & Aquaculture, 2017)

Hsa_circ_0045714 regulates chondrocyte proliferation, apoptosis and extracellular matrix synthesis by promoting the expression of miR-193b target gene IGF1R - Bao-feng Li; Ying Zhang; Jin Xiao; Fei Wang; Mei Li; Xiao-ze Guo; Hui-bin Xie; Hong Xia; Bei Chen (Human Cell, 2017)

Evaluation of the Integrity of Deep Rock Masses Using Results of Digital Borehole Televiewers - Hao-Sen Guo; Xia-Ting Feng; Shao-Jun Li; Cheng-Xiang Yang; Zhi-Bin Yao (Rock Mechanics and Rock Engineering, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Construction, Selection and Immunogenicity of Recombinant Fowlpox Candidate Vaccine Co-expressing HIV-1 gag and gp145 - Yilong Zhu; Yan Guo; Shouwen Du; Cunxia Liu; Maopeng Wang; Dayong Ren; Fei Zhao; Yanfang Zhang; Wenchao Sun; Yiquan Li; Tingting Cao; Yingyue Jiang; et al. (Indian Journal of Microbiology, 2017)

The improvement of M1 polarization in macrophages by glycopeptide derived from Ganoderma lucidum - Li-Xin Sun; Zhi-Bin Lin; Jie Lu; Wei-Dong Li; Yan-Dong Niu; Yu Sun; Chen-Yang Hu; Guo-Qiang Zhang; Xin-Suo Duan (Immunologic Research, 2017)

Phosphorus removal from aqueous solution in parent and aluminum-modified eggshells: thermodynamics and kinetics, adsorption mechanism, and diffusion process - Ziyan Guo; Jiuhai Li; Zhaobing Guo; Qingjun Guo; Bin Zhu (Environmental Science and Pollution Research, 2017)

Impacts of terrain attributes and human activities on soil texture class variations in hilly areas, south-west China - Ai-Di Li; Peng-Tao Guo; Wei Wu; Hong-Bin Liu (Environmental Monitoring and Assessment, 2017)

Developmental changes in digestive enzyme activity in American shad, Alosa sapidissima, during early ontogeny - Xiao-Qiang Gao; Zhi-Feng Liu; Chang-Tao Guan; Bin Huang; Ji-Lin Lei; Juan Li; Zheng-Long Guo; Yao-Hui Wang; Lei Hong (Fish Physiology and Biochemistry, 2017)

Identification of protein tyrosine phosphatase SHP-2 as a new target of perfluoroalkyl acids in HepG2 cells - Yu Yang; Qi-Yan Lv; Liang-Hong Guo; Bin Wan; Xiao-Min Ren; Ya-Li Shi; Ya-Qi Cai (Archives of Toxicology, 2017)

Calcaneal varus angle change in normal calcaneus: a three-dimensional finite element analysis - Xue-bin Zhang; Hao Wu; Li-guo Zhang; Ji-tang Zhao; Ying-ze Zhang (Medical & Biological Engineering & Computing, 2017)

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5 - Wei Ran Zhang; Hui Na Zhang; Yi Min Wang; Yang Dai; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Assessing the impact of climatic parameters and their inter-annual seasonal variability on fire activity using time series satellite products in South China (2001–2014) - Zeeshan Shirazi; Huadong Guo; Fang Chen; Bo Yu; Bin Li (Natural Hazards, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Phthalates in plastic bottled non-alcoholic beverages from China and estimated dietary exposure in adults - Ji-Feng Yang; Li-Ming Yang; Li-Ying Zheng; Guang-Guo Ying; Cheng-Bin Liu; Sheng-Lian Luo (Food Additives & Contaminants Part B-Surveillance, 2017)

A bifunctional type III polyketide synthase from raspberry (Rubus idaeus L.) with both chalcone synthase and benzalacetone synthase activity - Hui-Li Guo; Ya-Dong Yang; Ya-Di Ma; Wen-Bin Liu; Jing Feng; Zai-Qi Luo; He-Shu Lu; Chun-Mei Liu; Ming-Feng Yang; You-Nian Wang; Lan-Qing Ma (Journal of Plant Biochemistry and Biotechnology, 2017)

Deformation features and failure mechanism of steep rock slope under the mining activities and rainfall - Zhi-qiang Li; Yi-guo Xue; Shu-cai Li; Le-wen Zhang; Dan Wang; Bin Li; Wen Zhang; Kai Ning; Jian-ye Zhu (Journal of Mountain Science, 2017)

Synergistic and Superimposed Effect of Bone Marrow-Derived Mesenchymal Stem Cells Combined with Fasudil in Experimental Autoimmune Encephalomyelitis - Jing-Wen Yu; Yan-Hua Li; Guo-Bin Song; Jie-Zhong Yu; Chun-Yun Liu; Jian-Chun Liu; Hai-Fei Zhang; Wan-Fang Yang; Qing Wang; Ya-Ping Yan; Bao-Guo Xiao; Cun-Gen Ma (Journal of Molecular Neuroscience, 2016)

Different responses of soybean cyst nematode resistance between two RIL populations derived from Peking × 7605 under two ecological sites - YONGCHUN LI; NA GUO; JINMING ZHAO; BIN ZHOU; RAN XU; HUI DING; WEIGUO ZHAO; JUNYI GAI; HAN XING (Journal of Genetics, 2016)

Runx2 acts downstream of C/EBPβ to regulate the differentiation of uterine stromal cells in mice - Chuan-Hui Guo; Zhan-Peng Yue; Zhi-Kun Bai; Dang-Dang Li; Zhan-Qing Yang; Bin Guo (Cell and Tissue Research, 2016)

Optimization and Evaluation of Environmental Operations for Three Gorges Reservoir - Ming Hu; Guo H. Huang; Wei Sun; Xiaowen Ding; Yongping Li; Bin Fan (Water Resources Management, 2016)

Proteomic profile of Citrus grandis roots under long-term boron-deficiency revealed by iTRAQ - Lin-Tong Yang; Yi-Bin Lu; Yuan Zhang; Peng Guo; Li-Song Chen (Trees, 2016)

Brittle Rock Modeling Approach and its Validation Using Excavation-Induced Micro-Seismicity - Chun-Chi Ma; Tian-Bin Li; Hui-Lin Xing; Hang Zhang; Min-Jie Wang; Tian-Yi Liu; Guo-Qing Chen; Zi-Quan Chen (Rock Mechanics and Rock Engineering, 2016)

Comparative proteomic analysis reveals the positive effect of exogenous spermidine on photosynthesis and salinity tolerance in cucumber seedlings - Ting Sang; Xi Shan; Bin Li; Sheng Shu; Jin Sun; Shirong Guo (Plant Cell Reports, 2016)

Classifying four-category visual objects using multiple ERP components in single-trial ERP - Yu Qin; Yu Zhan; Changming Wang; Jiacai Zhang; Li Yao; Xiaojuan Guo; Xia Wu; Bin Hu (Cognitive Neurodynamics, 2016)

Research on the surface movement rules and prediction method of underground coal gasification - Huai-zhan Li; Guang-li Guo; Jian-feng Zha; Ya-fei Yuan; Bin-chen Zhao (Bulletin of Engineering Geology and the Environment, 2016)

Voriconazole combined with low-dose amphotericin B liposome for treatment of cryptococcal meningitis - Shan-Shan Li; Xin-Yue Tang; Sheng-Guo Zhang; Shun-Lan Ni; Nai-Bin Yang; Ming-Qin Lu (Infectious Diseases, 2016)

Silicon Alleviates Cadmium Toxicity in Two Cypress Varieties by Strengthening the Exodermis Tissues and Stimulating Phenolic Exudation of Roots - Bin Guo; Chen Liu; Nengfei Ding; Qinglin Fu; Yicheng Lin; Hua Li; Ningyu Li (Journal of Plant Growth Regulation, 2016)

Daytime birth and postbirth behavior of wild Rhinopithecus roxellana in the Qinling Mountains of China - Bin Yang; Peng Zhang; Kang Huang; Paul A. Garber; Bao-Guo Li (Primates, 2016)

microRNA-128 regulates the proliferation and differentiation of bovine skeletal muscle satellite cells by repressing Sp1 - Yang Dai; Wei Ran Zhang; Yi Min Wang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (Molecular and Cellular Biochemistry, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Clinicopathological and Prognostic Significance of CD133 in Glioma Patients: A Meta-Analysis - Mingzhi Han; Laixiu Guo; Ya Zhang; Bin Huang; Anjing Chen; Weiliang Chen; Xupeng Liu; Shicheng Sun; Kun Wang; Ao Liu; Xingang Li (Molecular Neurobiology, 2016)

The role of microRNA-1 and microRNA-206 in the proliferation and differentiation of bovine skeletal muscle satellite cells - Yang Dai; Yi Min Wang; Wei Ran Zhang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2016)

Silencing of dehydrin CaDHN1 diminishes tolerance to multiple abiotic stresses in Capsicum annuum L. - Ru-gang Chen; Hua Jing; Wei-li Guo; Shu-Bin Wang; Fang Ma; Bao-Gui Pan; Zhen-Hui Gong (Plant Cell Reports, 2015)

Gadd45b Mediates Axonal Plasticity and Subsequent Functional Recovery After Experimental Stroke in Rats - Bin Liu; Long-ling Li; Xiao-dan Tan; Yan-hong Zhang; Ying Jiang; Guo-qian He; Qian Chen; Chang-qing Li (Molecular Neurobiology, 2015)

Effect of vinegar residue compost amendments on cucumber growth and Fusarium wilt - Nanshan Du; Lu Shi; Lantian Du; Yinghui Yuan; Bin Li; Ting Sang; Jin Sun; Sheng Shu; Shirong Guo (Environmental Science and Pollution Research, 2015)

The Accordant Trend of Both Parameters (rgs Expression and cAMP Content) Follows the Pattern of Development of Fruiting Body in Volvariella volvacea - Yuanping Lu; Lingdan Lian; Lixian Guo; Bin Xie; Wei Wang; Bingzhi Chen; Arend Frans van Peer; Shaojie Li; Taju Wu; Baogui Xie (Current Microbiology, 2015)

A monitoring indicator system for remote sensing of grassland vegetation growth and suitability evaluation – a case study of the Xilingol Grassland in Inner Mongolia, China - Xiuchun Yang; Bin Xu; Xiaohua Zhu; Yunxiang Jin; Jinya Li; Fen Zhao; Shi Chen; Jian Guo; Hailong Ma; Haida Yu (International Journal of Remote Sensing, 2015)

Characterizing changes in grassland desertification based on Landsat images of the Ongniud and Naiman Banners, Inner Mongolia - Jinya Li; Bin Xu; Xiuchun Yang; Yunxiang Jin; Lina Zhao; Fen Zhao; Shi Chen; Jian Guo; Zhihao Qin; Hailong Ma (International Journal of Remote Sensing, 2015)

Adenovirus-mediated osteoprotegerin ameliorates cartilage destruction by inhibiting proteoglycan loss and chondrocyte apoptosis in rats with collagen-induced arthritis - Zhi-yun Feng; Zhen-nian He; Bin Zhang; Yi-qiao Li; Jian Guo; Yuan-lin Xu; Ming-yuan Han; Zhong Chen (Cell and Tissue Research, 2015)

Differential expression and regulation of Runx1 in mouse uterus during the peri-implantation period - Zhi-Kun Bai; Dang-Dang Li; Chuan-Hui Guo; Zhan-Qing Yang; Hang Cao; Bin Guo; Zhan-Peng Yue (Cell and Tissue Research, 2015)

Identification of Genes Involved in the Biosynthesis of Tripterygium wilfordii Hook.f. Secondary Metabolites by Suppression Subtractive Hybridization - Guo-peng Miao; Wei Li; Bin Zhang; Zhan-feng Zhang; Zhi-qing Ma; Jun-tao Feng; Xing Zhang; Chuan-shu Zhu (Plant Molecular Biology Reporter, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Thymosin alpha 1 suppresses proliferation and induces apoptosis in breast cancer cells through PTEN-mediated inhibition of PI3K/Akt/mTOR signaling pathway - Yan Guo; Hui Chang; Jing Li; Xin-yuan Xu; Lan Shen; Zhi-bin Yu; Wen-chao Liu (Apoptosis, 2015)

Ferrovibrio xuzhouensis sp. nov., a cyhalothrin-degrading bacterium isolated from cyhalothrin contaminated wastewater - Man Song; Long Zhang; Bin Sun; Hao Zhang; Hui Ding; Qiang Li; Suhui Guo; Xing Huang (Antonie van Leeuwenhoek, 2015)

Satellite-Based Investigation and Evaluation of the Observational Environment of Meteorological Stations in Anhui Province, China - Yu-Bin Li; Tao Shi; Yuan-Jian Yang; Bi-Wen Wu; La-Bao Wang; Chun-E Shi; Jian-Xia Guo; Cheng-Li Ji; Hua-Yang Wen (Pure and Applied Geophysics, 2015)

Activation of Dopamine D1 Receptors Regulates Dendritic Morphogenesis Through Rac1 and RhoA in Prefrontal Cortex Neurons - Juan Li; Jingjing Gu; Bin Wang; Minjuan Xie; Lu Huang; Yutong Liu; Lei Zhang; Jinhua Xue; Fukun Guo; Lin Zhang; Lu Zhang (Molecular Neurobiology, 2015)

Modeling demand/supply of water resources in the arid region of northwestern China during the late 1980s to 2010 - Xingran Liu; Yanjun Shen; Ying Guo; Shuo Li; Bin Guo (Journal of Geographical Sciences, 2015)

A hybrid strategy for comprehensive annotation of the protein coding genes in prokaryotic genome - Jia-Feng Yu; Jing Guo; Qing-Bin Liu; Yue Hou; Ke Xiao; Qing-Li Chen; Ji-Hua Wang; Xiao Sun (Genes & Genomics, 2015)

The Therapeutic Potential of Rho Kinase Inhibitor Fasudil Derivative FaD-1 in Experimental Autoimmune Encephalomyelitis - Yong-Fei Zhao; Xiang Zhang; Zhi-Bin Ding; Xing-Wang Yang; Hui Zhang; Jie-Zhong Yu; Yan-Hua Li; Chun-Yun Liu; Qing Zhang; Hong-Zhen Zhang; Cun-Gen Ma; Bao-Guo Xiao (Journal of Molecular Neuroscience, 2015)

Differential expression and regulation of Ido2 in the mouse uterus during peri-implantation period - Dang-Dang Li; Xin-Yuan Liu; Chuan-Hui Guo; Liang Yue; Zhan-Qing Yang; Hang Cao; Bin Guo; Zhan-Peng Yue (In Vitro Cellular & Developmental Biology - Animal, 2015)

In vivo construction of tissue-engineered cartilage using adipose-derived stem cells and bioreactor technology - Hongjun Kang; Shibi Lu; Jiang Peng; Qiang Yang; Shuyun Liu; Li Zhang; Jingxiang Huang; Xiang Sui; Bin Zhao; Aiyuan Wang; Wenjing Xu; Quanyi Guo; et al. (Cell and Tissue Banking, 2015)

Epidemical features of HAdV-3 and HAdV-7 in pediatric pneumonia in Chongqing, China - Ying Wo; Qing-Bin Lu; Dou-Dou Huang; Xiao-Kun Li; Chen-Tao Guo; Hong-Yu Wang; Xiao-Ai Zhang; Wei Liu; Wu-Chun Cao (Archives of Virology, 2015)

Effect of pore structure on seismic rock-physics characteristics of dense carbonates - Jian-Guo Pan; Hong-Bin Wang; Chuang Li; Jian-Guo Zhao (Applied Geophysics, 2015)

The CD8α gene in duck (Anatidae): cloning, characterization, and expression during viral infection - Qi Xu; Yang Chen; Wen Ming Zhao; Zheng Yang Huang; Xiu Jun Duan; Yi Yu Tong; Yang Zhang; Xiu Li; Guo Bin Chang; Guo Hong Chen (Molecular Biology Reports, 2015)

Methylopila henanense sp. nov., a novel methylotrophic bacterium isolated from tribenuron methyl-contaminated wheat soil - Ya-Nan Wang; Wen-Yu Tian; Wei-Hong He; Guo-Can Chen; Ming-Li An; Bin Jia; Li Liu; Yang Zhou; Shuang-Jiang Liu (Antonie van Leeuwenhoek, 2015)

Systematic discovery and characterization of stress-related microRNA genes in Oryza sativa - Kai Bin Xie; Xue Zhou; Tian Hai Zhang; Bao Long Zhang; Li Ming Chen; Guo Xiang Chen (Biologia, 2015)

Recombination in truncated genome sequences of porcine circovirus type 2 - Libin Wen; Fengzhi Wang; Kongwang He; Bin Li; Xiaomin Wang; Rongli Guo; Jianping Xie (Archives of Virology, 2015)

Long-term morphological response to dredging including cut-across-shoal in a tidal channel-shoal system - Yu-Hai Wang; Chong-Hao Wang; Li-Qun Tang; Da-Bin Liu; Chuan-Sheng Guo; Chun-Jing Liu; Hui-Ming Zhao (Ocean Dynamics, 2014)

Molecular cloning and expression analysis of ferritin, heavy polypeptide 1 gene from duck (Anas platyrhynchos) - Qi Xu; Yang Chen; Yang Zhang; Yi Yu Tong; Zheng Yang Huang; Wen Ming Zhao; Xiu Jun Duan; Xiu Li; Guo Bin Chang; Guo Hong Chen (Molecular Biology Reports, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Experimental Study on Slope Runoff, Erosion and Sediment under Different Vegetation Types - Xia Zhang; Guo Qiang Yu; Zhan Bin Li; Peng Li (Water Resources Management, 2014)

The variability of the snow and ice melt in alpine rivers in northwestern China - Chang-bin Li; Jia-guo Qi; Lin-shan Yang; Wen-jin Yang; Gao-feng Zhu; Shuai-bing Wang (Journal of Mountain Science, 2014)

Engrailed-2 is down-regulated but also ectopically expressed in clear cell renal cell carcinoma - Cai-yong Lai; Bin Pan; Yun Luo; Wei-bo Liang; Jie Chen; Dong-ming Ye; Ji-Nan Guo; Li Li; Ze-xuan Su (Molecular Biology Reports, 2014)

Identification of a novel COL4A5 mutation in a Chinese family with X-linked Alport syndrome using exome sequencing - Yi Guo; Jinzhong Yuan; Hui Liang; Jingjing Xiao; Hongbo Xu; Lamei Yuan; Kai Gao; Bin Wu; Yongchang Tang; Xiaorong Li; Hao Deng (Molecular Biology Reports, 2014)

Haemocyte Apoptosis of the Tiger Shrimp Penaeus monodon Exposed to Cadmium - Jian-An Xian; Bin Li; Hui Guo; Yu-Tao Miao; Jian-Min Ye; Li-Na Feng; Chao-Xia Ye; Xun-Bin Pan; An-Li Wang; Xuan-Ming Hao (Bulletin of Environmental Contamination and Toxicology, 2014)

Effect of temperature decrease on hemocyte apoptosis of the white shrimp Litopenaeus vannamei - Bin Li; Jian-An Xian; Hui Guo; An-Li Wang; Yu-Tao Miao; Jian-Min Ye; Chao-Xia Ye; Shao-An Liao (Aquaculture International, 2014)

HIRA is essential for the development of gibel carp - Meng-Yu Wang; Qiu-Hong Guo; Xin-Zheng Du; Li Zhou; Qian Luo; Qiao-Hui Zeng; Jia-Lin Wang; Hao-Bin Zhao; Yu-Feng Wang (Fish Physiology and Biochemistry, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Identification of differentially expressed genes in American cockroach ovaries and testes by suppression subtractive hybridization and the prediction of its miRNAs - Wan Chen; Guo-Fang Jiang; Shu-Hong Sun; Yong Lu; Fei Ma; Bin Li (Molecular Genetics and Genomics, 2013)

Effects of PTHrP on chondrocytes of sika deer antler - Bin Guo; Shou-Tang Wang; Cui-Cui Duan; Dang-Dang Li; Xue-Chao Tian; Qu-Yuan Wang; Zhan-Peng Yue (Cell and Tissue Research, 2013)

Molecular cloning and characterization of two pathogenesis-related β-1,3-glucanase genes ScGluA1 and ScGluD1 from sugarcane infected by Sporisorium scitamineum - Ya-chun Su; Li-ping Xu; Ban-tong Xue; Qi-bin Wu; Jin-long Guo; Lu-guang Wu; You-xiong Que (Plant Cell Reports, 2013)

Expression and regulation of Runx3 in mouse uterus during the peri-implantation period - Zhi-Kun Bai; Bin Guo; Xue-Chao Tian; Dang-Dang Li; Shou-Tang Wang; Hang Cao; Qu-Yuan Wang; Zhan-Peng Yue (Journal of Molecular Histology, 2013)

Pea aphid promotes amino acid metabolism both in M edicago truncatula and bacteriocytes to favor aphid population growth under elevated CO 2 - Huijuan Guo; Yucheng Sun; Yuefei Li; Bin Tong; Marvin Harris; Keyan Zhu‐Salzman; Feng Ge (Global Change Biology, 2013)
Rising atmospheric CO 2 levels can dilute the nitrogen ( N ) resource in plant tissue, which is disadvantageous to many herbivorous insects. Aphids appear to be an exception that warrants further study. The effects of elevated CO 2 (750 ppm vs. 390 ppm) were evaluated on N assimilation and transamination by two M edicago truncatula genotypes, a N‐fixing‐deficient mutant ( dnf1 ) and its wild‐type control (Jemalong), with and without pea aphid ( Acyrthosiphon pisum ) infestation. Elevated CO 2 increased population abundance and feeding efficiency of aphids fed on Jemalong, but reduced those on dnf1 . Without aphid infestation, elevated CO 2 increased photosynthetic rate, chlorophyll content, nodule number, biomass, and pod number for Jemalong, but only increased pod number and chlorophyll content for dnf1 . Furthermore, aphid infested Jemalong plants had enhanced activities of N assimilation‐related enzymes (glutamine synthetase, Glutamate synthase) and transamination‐related enzymes (glutamate oxalate transaminase, glutamine phenylpyruvate transaminase), which presumably increased amino acid concentration in leaves and phloem sap under elevated CO 2 . In contrast, aphid infested dnf1 plants had decreased activities of N assimilation‐related enzymes and transmination‐related enzymes and amino acid concentrations under elevated CO 2 . Furthermore, elevated CO 2 up‐regulated expression of genes relevant to amino acid metabolism in bacteriocytes of aphids associated with Jemalong, but down‐regulated those associated with dnf1 . Our results suggest that pea aphids actively elicit host responses that promote amino acid metabolism in both the host plant and in its bacteriocytes to favor the population growth of the aphid under elevated CO 2 .

Agricultural Technologies for Enhancing the Phytoremediation of Cadmium-Contaminated Soil by Amaranthus hypochondriacus L. - Ningyu Li; Zhian Li; Qinglin Fu; Ping Zhuang; Bin Guo; Hua Li (Water, Air, & Soil Pollution, 2013)

Novel triterpenoid saponins from the seeds of Celosia argentea L. - Qing Bin Wu; Yan Wang; Lin Liang; Qian Jiang; Mei Li Guo; Jun Jie Zhang (Natural Product Research, 2013)

Progressive modelling of the gravity-induced landslide using the local dynamic strength reduction method - Guo-qing Chen; Run-qiu Huang; Qiang Xu; Tian-bin Li; Ming-lei Zhu (Journal of Mountain Science, 2013)
The failure of slope is a progressive process, and the whole sliding surface is caused by the gradual softening of soil strength of the potential sliding surface. From this viewpoint, a local dynamic strength reduction method is proposed to capture the progressive failure of slope. This method can calculate the warning deformation of landslide in this study. Only strength parameters of the yielded zone of landslide will be reduced by using the method. Through continuous local reduction of the strength parameters of the yielded zone, the potential sliding surface developed gradually and evolved to breakthrough finally. The result shows that the proposed method can simulate the progressive failure of slope truly. The yielded zone and deformation of landslide obtained by the method are smaller than those of overall strength reduction method. The warning deformation of landslide can be obtained by using the local dynamic strength reduction method which is based on the softening characteristics of the sliding surface.

Predictive Models of Diffusive Nanoparticle Transport in 3-Dimensional Tumor Cell Spheroids - Yue Gao; Mingguang Li; Bin Chen; Zancong Shen; Peng Guo; M. Guillaume Wientjes; Jessie L.-S. Au (The AAPS Journal, 2013)

Alterations of liver histology and blood biochemistry in blunt snout bream Megalobrama amblycephala fed high-fat diets - Kang-le Lu; Wei-na Xu; Jun-yi Li; Xiang-fei Li; Guo-qing Huang; Wen-bin Liu (Fisheries Science, 2013)

Two type III polyketide synthases from Polygonum cuspidatum: gene structure, evolutionary route and metabolites - Yan-Wu Guo; Hui-Li Guo; Xing Li; Li-Li Huang; Bo-Ning Zhang; Xiao-Bin Pang; Ben-Ye Liu; Lan-Qing Ma; Hong Wang (Plant Biotechnology Reports, 2013)

Anxiolytic Actions of Motilin in the Basolateral Amygdala - Bin Feng; Jin-cheng Liu; Jun Zhang; Ken-ichi Ozaki; Yan-yan Guo; Ding-hua Yi; Xiao-qiang Li; Ming-gao Zhao (Molecular Neurobiology, 2013)

Association between PIN1 promoter polymorphisms and risk of nasopharyngeal carcinoma - Yan Lu; Guo-Liang Huang; Xing-Xiang Pu; Yu-Xiang He; Bin-Bin Li; Xing-Yan Liu; Zigang Dong; Zhiwei He (Molecular Biology Reports, 2013)

RETRACTED ARTICLE: Mesothelial cells differentiate into fibroblast-like cells under the scirrhous gastric cancer microenvironment and promote peritoneal carcinomatosis in vitro and in vivo - Zhi-Dong Lv; Hai-Bo Wang; Qian Dong; Bin Kong; Jian-guo Li; Zhao-Chuan Yang; Hui-Li Qu; Wei-Hong Cao; Hui-Mian Xu (Molecular and Cellular Biochemistry, 2013)

Prediction of soil organic matter using artificial neural network and topographic indicators in hilly areas - Peng-Tao Guo; Wei Wu; Qing-Kai Sheng; Mao-Fen Li; Hong-Bin Liu; Zheng-Yin Wang (Nutrient Cycling in Agroecosystems, 2013)

Spatially explicit estimation of domestic water use in the arid region of northwestern China: 1985–2009 - Bin Guo; Yaning Chen; Yanjun Shen; Weihong Li; Chengben Wu (Hydrological Sciences Journal, 2013)

Effects of PGR and ESRα genotypes on the pregnancy rates after embryo transfer in Luxi cattle - Ke-Qiong Tang; Wu-Cai Yang; Bin Pai; Shu-Jing Li; Long Chen; Li-Guo Yang (Molecular Biology Reports, 2013)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Characterization of pilP, a gene required for twitching motility, pathogenicity, and biofilm formation of Acidovorax avenae subsp. avenae RS-1 - He Liu; Wen-Xiao Tian; Muhammad Ibrahim; Bin Li; Guo-Qing Zhang; Bo Zhu; Guan-Lin Xie (European Journal of Plant Pathology, 2012)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Pseudomonas nitritireducens sp. nov., a nitrite reduction bacterium isolated from wheat soil - Ya-Nan Wang; Wei-Hong He; Hua He; Xun Du; Bin Jia; Zhi-Peng Zeng; Ming-Li An; Guo-Can Chen (Archives of Microbiology, 2012)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

Mapping QTLs with epistatic effects and QTL × treatment interactions for salt tolerance at seedling stage of wheat - Yun-Feng Xu; Diao-Guo An; Dong-Cheng Liu; Ai-Min Zhang; Hong-Xing Xu; Bin Li (Euphytica, 2012)

Estimating transgene copy number in precocious trifoliate orange by TaqMan real-time PCR - Li Wen; Bin Tan; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Quantitative assessment of the effect of MTHFR polymorphisms on the risk of lung carcinoma - Yao Zhang; Guo Qiang Chen; Yong Ji; Bin Huang; Wei Sheng Shen; Li Chun Deng; Lei Xi; Xiang Ming Cao (Molecular Biology Reports, 2012)

Quantifying the Effects of Conservation Practices on Soil, Water, and Nutrients in the Loess Mesa Ravine Region of the Loess Plateau, China - Xiang-Zhou Xu; Mei-Juan Li; Bin Liu; Shang-Fu Kuang; Shi-Guo Xu (Environmental Management, 2012)

Gene expression profiles of two intraspecific Larix lines and their reciprocal hybrids - Ai Li; Meng-Die Fang; Wen-Qin Song; Cheng-Bin Chen; Li-Wang Qi; Chun-Guo Wang (Molecular Biology Reports, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

DNA Methylation in Genomes of Several Annual Herbaceous and Woody Perennial Plants of Varying Ploidy as Detected by MSAP - Ai Li; Bao-Quan Hu; Zhen-Yi Xue; Li Chen; Wei-Xing Wang; Wen-Qin Song; Cheng-Bin Chen; Chun-Guo Wang (Plant Molecular Biology Reporter, 2011)

Plasma Paraoxonase-1, Oxidized Low-Density Lipoprotein and Lipid Peroxidation Levels in Gout Patients - Xing-Liang Jiang; Min Li; Jing-Guo Zhou; Qi-Bin Yang; Li-Jun Du; Juan Du (Cell Biochemistry and Biophysics, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Association of a LSP1 gene rs3817198T>C polymorphism with breast cancer risk: evidence from 33,920 cases and 35,671 controls - Min-Bin Chen; Chen Li; Wen-Xiang Shen; Yu-Jiang Guo; Wei Shen; Pei-Hua Lu (Molecular Biology Reports, 2011)

Calcitonin gene-related peptide released from endothelial progenitor cells inhibits the proliferation of rat vascular smooth muscle cells induced by angiotensin II - Li Fang; Mei-Fang Chen; Zhi-Lin Xiao; Yin Liu; Guo-Long Yu; Xiao-Bin Chen; Xiu-Mei Xie (Molecular and Cellular Biochemistry, 2011)

Effects of low nitrogen and drought stresses on proline synthesis of Jatropha curcas seedling - Wen-Guo Wang; Rui Li; Bin Liu; Liang Li; Sheng-Hua Wang; Fang Chen (Acta Physiologiae Plantarum, 2011)

Effect of ploidy increase on transgene expression: example from Citrus diploid cybrid and allotetraploid somatic hybrid expressing the EGFP gene - Shi-Xiao Xu; Xiao-Dong Cai; Bin Tan; Ding-Li Li; Wen-Wu Guo (Protoplasma, 2011)

The accelerating effect and mechanism of a newly functional bio-carrier modified by redox mediators for the azo dyes decolorization - Jianbo Guo; Li Kang; Jing Lian; Jingliang Yang; Bin Yan; Zaixing Li; Chun Liu; Lin Yue (Biodegradation, 2010)

Biodegradation of ethanethiol in aqueous medium by a new Lysinibacillus sphaericus strain RG-1 isolated from activated sludge - Shungang Wan; Guiying Li; Taicheng An; Bin Guo; Lei Sun; Lei Zu; Ailing Ren (Biodegradation, 2010)

Genomic structure and evolution of the Pi2/9 locus in wild rice species - Liangying Dai; Jun Wu; Xunbo Li; Xuejun Wang; Xionglun Liu; Chatchawan Jantasuriyarat; Dave Kudrna; Yeisoo Yu; Rod A. Wing; Bin Han; Bo Zhou; Guo-Liang Wang (Theoretical and Applied Genetics, 2010)

Effects of salvianolic acid B on proliferation, neurite outgrowth and differentiation of neural stem cells derived from the cerebral cortex of embryonic mice - GuoQing Guo; Bin Li; YuanYuan Wang; AiJing Shan; WeiZai Shen; Lin Yuan; ShiZhen Zhong (Science China Life Sciences, 2010)

Erratum to: A genome-wide scan for quantitative trait loci affecting serum glucose and lipids in a White Duroc × Erhualian intercross F2 population - Rongrong Chen; Jun Ren; Wanbo Li; Xiang Huang; Xueming Yan; Bin Yang; Yinggong Zhao; Yuanmei Guo; Huirong Mao; Lusheng Huang (Mammalian Genome, 2010)

Expression of the apoptosis-related proteins caspase-3 and NF-κB in the hippocampus of Tg2576 mice - Yan-Li Niu; Wei-Juan Zhang; Ping Wu; Bin Liu; Guo-Tao Sun; Dong-Ming Yu; Jin-Bo Deng (Neuroscience Bulletin, 2010)

Seasonal changes of energy fluxes in an estuarine wetland of Shanghai, China - Haiqiang Guo; Bin Zhao; Jiquan Chen; Yaner Yan; Bo Li; Jiakuan Chen (Chinese Geographical Science, 2010)

Anti-influenza-virus activity of total alkaloids from Commelina communis L. - Fei-Hong Bing; Jun Liu; Zhi Li; Guo-Bin Zhang; Yi-Fan Liao; Jing Li; Chang-Yuan Dong (Archives of Virology, 2009)

Antitumor effect of the seashell protein Haishengsu on Ehrlich ascites tumor: an experimental study - Ji-Zhu Liu; Shou-Guo Chen; Zhang Bin; Chun-Bo Wang; Guang-Yao Li; Le-Xin Wang (Journal of Natural Medicines, 2009)

Screening and identification of natural antisense transcripts in Helicobacter pylori by a novel approach based on RNase I protection assay - Bin Xiao; Wei Li; Gang Guo; Bo-Sheng Li; Zhen Liu; Bin Tang; Xu-Hu Mao; Quan-Ming Zou (Molecular Biology Reports, 2009)

Highly efficient transformation of the GFP and MAC12.2 genes into precocious trifoliate orange (Poncirus trifoliata [L.] Raf), a potential model genotype for functional genomics studies in Citrus - Bin Tan; Ding-Li Li; Shi-Xiao Xu; Gai-En Fan; Jing Fan; Wen-Wu Guo (Tree Genetics & Genomes, 2009)

Salicylic acid activates artemisinin biosynthesis in Artemisia annua L. - Gao-Bin Pu; Dong-Ming Ma; Jian-Lin Chen; Lan-Qing Ma; Hong Wang; Guo-Feng Li; He-Chun Ye; Ben-Ye Liu (Plant Cell Reports, 2009)

Biological control of grapevine crown gall: purification and partial characterisation of an antibacterial substance produced by Rahnella aquatilis strain HX2 - Fan Chen; Jin-Yun Li; Yan-Bin Guo; Jian-Hui Wang; Hui-Min Wang (European Journal of Plant Pathology, 2009)

A genome-wide scan for quantitative trait loci affecting serum glucose and lipids in a White Duroc × Erhualian intercross F2 population - Rongrong Chen; Jun Ren; Wanbo Li; Xiang Huang; Xueming Yan; Bin Yang; Yinggong Zhao; Yuanmei Guo; Huirong Mao; Lusheng Huang (Mammalian Genome, 2009)

Isolation via enrichment and characterization of 14 dinucleotide microsatellite loci in one catfish, Glyptosternum maculatum and cross-amplification in other related taxa - Baoying Guo; Congxin Xie; Hongjing Li; Lei Shan; Huanling Wang; Bin Huo; Yan Zhang; Qing Zhou (Conservation Genetics, 2009)

Heavy metal contamination in soil alongside mountain railway in Sichuan, China - Hao Liu; Li-Ping Chen; Ying-Wei Ai; Xia Yang; Yan-Hua Yu; Yuan-Bin Zuo; Guo-Yong Fu (Environmental Monitoring and Assessment, 2009)

The subpleural pulmonary microvasculature in newborn yak (Bos grunniens) - Xiaoxia Du; Hongxian Yu; Jinglian Yan; Ying Liu; Jianqiang Guo; Xiaohua Du; Jianhong Zhao; Yu Wang; Dongyang Liu; Renge Li; Haitao Zhao; Bin Liu (Veterinary Research Communications, 2009)

A genetic linkage map construction for sesame (Sesamum indicum L.) - Li-Bin Wei; Hai-Yang Zhang; Yong-Zhan Zheng; Hong-Mei Miao; Tian-Zhen Zhang; Wang-Zhen Guo (Genes & Genomics, 2009)

Identification of Small Noncoding RNAs in Helicobacter pylori by a Bioinformatics-Based Approach - Bin Xiao; Wei Li; Gang Guo; BoSheng Li; Zhen Liu; KeRan Jia; Ying Guo; XuHu Mao; QuanMing Zou (Current Microbiology, 2009)

Isolation and characterization of three Sphingobium sp. strains capable of degrading isoproturon and cloning of the catechol 1,2-dioxygenase gene from these strains - Ji-Quan Sun; Xing Huang; Qiao-Ling Chen; Bin Liang; Ji-Guo Qiu; Shinawar Waseem Ali; Shun-Peng Li (World Journal of Microbiology and Biotechnology, 2009)

A novel type III polyketide synthase encoded by a three-intron gene from Polygonum cuspidatum - Lan-Qing Ma; Xiao-Bin Pang; Hai-Yan Shen; Gao-Bin Pu; Hua-Hong Wang; Cai-Yan Lei; Hong Wang; Guo-Feng Li; Ben-Ye Liu; He-Chun Ye (Planta, 2009)

An age-dependent proliferation is involved in the postnatal development of interstitial cells of Cajal in the small intestine of mice - Feng Mei; Jiang Zhu; Sheng Guo; De-shan Zhou; Juan Han; Bin Yu; Shi-feng Li; Zhong-yong Jiang; Cheng-jie Xiong (Histochemistry and Cell Biology, 2009)

Death and proliferation of chondrocytes in the degraded mandibular condylar cartilage of rats induced by experimentally created disordered occlusion - Kai Jiao; Mei-Qing Wang; Li-Na Niu; Juan Dai; Shi-Bin Yu; Xiao-Dong Liu; Guo-Wei Wang (Apoptosis, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Closing the carbon budget of estuarine wetlands with tower‐based measurements and MODIS time series - YANER YAN; BIN ZHAO; JIQUAN CHEN; HAIQIANG GUO; YONGJIAN GU; QIANHONG WU; BO LI (Global Change Biology, 2008)

Closing the carbon budget of estuarine wetlands with tower‐based measurements and MODIS time series - YANER YAN; BIN ZHAO; JIQUAN CHEN; HAIQIANG GUO; YONGJIAN GU; QIANHONG WU; BO LI (Global Change Biology, 2008)
Compared to other ecosystems, estuarine ecosystems have distinct carbon flux dynamics – the lateral carbon flux incurred by tidal activities, and methane generation under the anaerobic conditions of wetland soils. The conventional estimation of gross primary production (GPP) based on the light use efficiency (LUE) model used for non‐wetland terrestrial ecosystems, therefore, cannot be applied directly to estuarine wetland ecosystems. In this paper, we estimated the 2005's annual carbon budget of an estuarine wetland on Chongming Island, Shanghai, and partitioned the losses of carbon due to lateral tidal dynamics and anaerobic methane production using an innovative technique. The average GPP calculated from eddy covariance between March and November was 261.79 μmol m −2 day −1 , whereas that from the LUE model was 58.84 μmol m −2 day −1 . The correlation coefficient between GPP simulated from the LUE model and that calculated from flux tower data was low in the growing season ( R 2 =0.55). We hypothesized that tidal activities and uncounted methane release were responsible for the difference, which can be predicted from measurements of remote sensing products such as land surface water index (LSWI), evapotranspiration (ET), and tide height (TH). We developed an integrated GPP model by combining the LUE model and an autoregression model to estimate carbon budget. The average GPP from the modified model increased to 263.38 μmol m −2 day −1 , and R 2 for the correlation between the simulated and calculated data increased to 0.88, demonstrating the potential of our technique for GPP estimation and quantification of seasonal variation in estuarine ecosystems. The approach developed in this study has great potential for correcting unavoidable errors when estimating carbon budget of coastal wetlands. Furthermore, global warming is expected to accelerate sea level rise, which may enhance the effect of tidal activities and increase the difficulty in estimating coastal carbon budgets using conventional methods.

Identification and verification of microRNA in wheat (Triticum aestivum) - Weibo Jin; Nannan Li; Bin Zhang; Fangli Wu; Wuju Li; Aiguang Guo; Zhiyong Deng (Journal of Plant Research, 2008)

Simulations of the East Asian subtropical westerly jet by LASG/IAP AGCMs - Lanli Guo; Yaocun Zhang; Bin Wang; Lijuan Li; Tianjun Zhou; Qing Bao (Advances in Atmospheric Sciences, 2008)

The concentrations, distribution and sources of PAHs in agricultural soils and vegetables from Shunde, Guangdong, China - Yong Tao Li; Fang Bai Li; Jun Jian Chen; Guo Yi Yang; Hong Fu Wan; Tian Bin Zhang; Xiao Duo Zeng; Jian Ming Liu (Environmental Monitoring and Assessment, 2008)

Total Internal Reflection Fluorescence Spectroscopy for Investigating the Adsorption of a Porphyrin at the Glass/Water Interface in the Presence of a Cationic Surfactant Below the Critical Micelle Concentration - Yao-Ji Tang; Ying Chen; Min-Na Yao; Zhe-Xiang Zou; Guo-Bin Han; Yao-Qun Li (Journal of Fluorescence, 2008)

Climatic change during the last 4000 years in the southern Tarim Basin, Xinjiang, northwest China - Wei Zhong; Ji Bin Xue; Qiang Shu; Li Guo Wang (Journal of Quaternary Science, 2007)
In this study, a ca. 4000 cal. yr ancient lacustrine (or wetland) sediment record at the southern margin of Tarim Basin is used to reconstruct the history of climate change. Six radiocarbon dates on organic matter were obtained. δ 18 O and δ 13 C of carbonate, pollen and sediment particle size were analysed for climate proxies. The proxies indicate that a drier climate prevailed in the area before ca. 1010 BC and during period 1010 BC–AD 500 climate then changed rapidly and continuously from dry to moist, but after about AD 500 climate generally shows dry condition. Several centennial‐scale climatic events were revealed, with the wettest spell during AD 450–550, and a relatively wetter interval between AD 930–1030. Pollen results show that regional climate may influence human agricultural activities. Spectral analysis of mean grain size (MGS) proxy reveals statistically pronounced cyclic signals, such as ca. 200 yr, ca. 120 yr, ca. 90 yr, ca. 45 yr and ca. 33 or 30 yr, which may be associated with solar activities, implying that solar variability plays an important role in the decadal‐ and centennial‐scale climate variations in the study area. Copyright © 2007 John Wiley & Sons, Ltd.

Studies on optimization of nitrogen sources for astaxanthin production by Phaffia rhodozyma - Hui Ni; Qi-he Chen; Hui Ruan; Yuan-fan Yang; Li-jun Li; Guang-bin Wu; Yang Hu; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Mechanism of Lysophosphatidylcholine-Induced Lysosome Destabilization - Jin-Shan Hu; Ying-Bin Li; Jiong-Wei Wang; Lin Sun; Guo-Jiang Zhang (The Journal of Membrane Biology, 2007)

Phylogeography and Origin of Sheep Breeds in Northern China - Yue-Hui Ma; Shao-Qi Rao; Shen-Jin Lu; Guan-Yu Hou; Wei-Jun Guan; Hong-Bin Li; Xia Li; Qian-Jun Zhao; Jun Guo (Conservation Genetics, 2006)

Multi-Person Multiobjective Fuzzy Decision-Making Model for Reservoir Flood Control Operation - Yi-bin Yu; Ben-de Wang; Guo-li Wang; Wei Li (Water Resources Management, 2004)

Spatial changes of wind erosion-caused landscapes and their relation with wind field in China - Zhang Guo-ping; Liu Ji-yuan; Zhang Zeng-xiang; Zhao Xiao-li; Zhou Quan-bin (Journal of Geographical Sciences, 2002)